Le Contrôle des Prix de transfert par les Administrations Fiscales des États de l'Afrique de l'Ouest - Diallo, Mamadou Dian (Université Côte d'Azur, 2025)
Les prix de transfert sont les prix auxquels une entreprise transfère des biens corporels, des actifs incorporels ou rend des services à des entreprises associées situées dans différents pays. En Afrique de l'Ouest, la question des prix de transfert est devenue un enjeu majeur pour les autorités fiscales, dès lors que ces pratiques peuvent être utilisées pour transférer artificiellement des bénéfices vers des juridictions à faible fiscalité, réduisant ainsi les recettes fiscales locales. Les pays de l'Afrique de l'Ouest connaissent une forte présence d'entreprises multinationales, en particulier, dans les secteurs des mines, du pétrole, des télécommunications etc. La faiblesse des capacités de contrôle fiscal, combinée à la complexité des montages fiscaux, rendent difficile la lutte contre l'érosion de la base d'imposition et le transfert de bénéfices à l'étranger.L'imposition des entreprises multinationales est gouvernée par les principes dits, de « territorialité » et de « pleine concurrence ». Il résulte des standards internationaux, que chaque entité d'un groupe multinational doit s'acquitter de l'impôt dans son pays d'implantation, en déterminant son bénéfice local comme si ses transactions avec les autres entités qui lui sont liées étaient effectuées avec des entreprises indépendantes.La présente thèse a pour objectif de traiter du contrôle des prix de transfert par les autorités fiscales des pays de l'Afrique de l'Ouest, dans un contexte où la lutte contre l'évasion fiscale internationale est devenue un enjeu mondial. A cet égard, le projet BEPS initié en 2013 par le G20 a formulé des recommandations à l'endroit des autorités fiscales permettant de traiter efficacement les questions liées aux pratiques BEPS. Ce projet a été intégré dans les principes de l'OCDE applicables en matière de prix de transfert à l'intention des entreprises multinationales et des administrations fiscales, renforcé par le Manuel Pratique de l'ONU sur les prix de transfert à l'intention des pays en voie de développement. Il replace le principe de pleine concurrence au centre de la lutte contre les pratiques BEPS. Transfer pricing refers to the price at which a company transfers tangible or intangible assets, or provides services to associated companies located in different countries. In West Africa, the issue of transfer pricing has become a major challenge for tax authorities, as these practices can be used to artificially shift profits to low-tax jurisdictions, thereby reducing local tax revenues. West African countries have a strong presence of multinational companies, particularly in the mining, oil, and telecommunications sectors. Weak tax audit capacities, combined with the complexity of tax arrangements, make it difficult to combat base erosion and profit shifting abroad.The taxation of multinational companies is governed by the so-called ''territoriality'' and ''arm's length'' principles. International standards stipulate that each entity within a multinational group must pay tax in its country of establishment, determining its local profit as if its transactions with other related entities were conducted with independent companies.This thesis aims to address transfer pricing controls by tax authorities in West African countries, in a context where the fight against international tax evasion has become a global issue. In this regard, the BEPS project initiated in 2013 by the G20 has formulated recommendations for tax authorities to effectively address issues related to BEPS practices. This project was incorporated into the OECD Transfer Pricing Guidelines for Multinational Enterprises and Tax Administrations, reinforced by the UN Practical Handbook on Transfer Pricing for Developing Countries. It places the arm's length principle at the center of the fight against BEPS practices.
Keywords: Administration fiscale; Afrique de l'Ouest; Afrique occidentale; Arm's length principle; BEPS; Base d’imposition; Control; Contrôle; Entreprises multinationales; Indirect profit shifting; Multinational enterprises; Pricing; Principe de pleine concurrence; Prix; Prix de cession interne; Prix de transfert (manipulation); Procédures fiscales; Tax authorities; Transfer; Transfer pricing; Transfert; Transfert indirect de bénéfices; West Africa

L'abus de droit en matière fiscale - Silberman, Lauren (Université Paris 12, 2025)
La théorie de l’abus de droit se présente comme un correctif essentiel à l’exercice des droits et un outil pour rétablir l’équilibre entre les intérêts en présence qui sont, en matière fiscale, ceux des contribuables, de l’administration fiscale et de la collectivité. L’abus de droit dépend du droit auquel une limite est apportée, limite pouvant être fixée par le législateur et selon une politique déterminée. Le législateur français a autonomisé la notion d’abus de droit en matière fiscale par la création d’une procédure spéciale de rectification assortie d’une majoration automatique punitive. La multiplication des dispositifs anti-abus d’assiette, qui s’applique dans le cadre de la procédure de rectification de droit commun, et qui n’entrainent pas l’application automatique d’une pénalité, a mené à une évolution de la notion d’abus de droit en matière fiscale. Ces dispositifs encadrent l’exercice de la liberté de choisir la voie la moins imposée, et se distinguent par leur régime et leur sanction. Corrélativement, l’Union européenne a développé sa propre notion d’abus de droit en matière fiscale, d’abord pour apprécier la compatibilité des dispositifs nationaux au droit primaire de l’Union, puis pour encadrer l’exercice des avantages offerts par le droit dérivé. Elle a ainsi dégagé une définition de l’abus de droit dont les critères diffèrent selon le droit abusé. L’OCDE s’est également intéressée à la notion d’abus en matière fiscale dans le cadre de la lutte contre l’érosion de la base d’imposition et le transfert de bénéfices. Son approche, plus pragmatique, se concentre sur les comportements des contribuables et de redevables qui doit être conforme non pas à la législation, mais à la politique fiscale et à l’équité fiscale entre les Etats et les opérateurs sur le marché mondial. L’Union européenne a adopté la même conception de l’abus de droit en matière fiscale par l’adoption d’un paquet de mesures de lutte contre la fraude et l’évasion fiscales. L’approche comportementale et économique de l’abus de droit coexiste aujourd’hui avec l’approche stricte et répressive du droit fiscal français. Cette coexistence a mené à la multiplication des dispositifs anti-abus d’assiette qui font entrer dans le champ de l’abus des comportements identifiés comme abusifs parce que non conformes à la conception internationale et européenne de l’équité fiscale. La notion de fictivité s’est élargie au profit de la notion de validité pour faire entrer dans son champ des comportements autrefois considérés comme de l’optimisation fiscale. Cette nouvelle approche de l’abus de droit en matière fiscale est source d’incertitudes pour les contribuables et les redevables et permet de s’interroger sur l’étendue de la notion d’abus de droit en matière fiscale. The theory of abuse of rights is an essential corrective to the exercise of rights, and a tool for restoring the balance between the interests involved, which, in tax matters, are those of the taxpayer, the tax authorities and the community. Abuse of rights depends on the law to which a limit has been set, a limit that can be set by the legislator according to a specific policy. The French legislator has given autonomy to the notion of abuse of rights in tax matters. It has created a provision to penalize abuse of rights, with a special rectification procedure and an automatic punitive surcharge. But it has also created anti-abuse provisions which apply within the framework of the ordinary rectification procedure and which do not entail the automatic application of a penalty. While all of these measures provide a framework for exercising the freedom to choose the path of least resistance to taxation, they differ in terms of their regimes and penalties. The European Union has also developed its own concept of abuse of rights in tax matters, firstly to assess the compatibility of national provisions with EU primary law, and then to provide a framework for the exercise of the advantages offered by secondary legislation. It has thus established a definition of abuse of rights, the criteria for which differ according to the law being abused. The OECD has also turned its attention to the notion of tax abuse as part of the fight against tax base erosion and profit shifting. Its more pragmatic approach focuses on the behavior of taxpayers and liables, which must be consistent not with legislation, but with tax policy and tax fairness between countries and operators on the global market. The European Union has adopted the same concept of abuse of rights in tax matters, with the adoption of a package of measures to combat tax fraud and evasion. Today, the behavioral and economic approach to abuse of rights coexists with the strict and repressive approach of French tax law. This coexistence has led to a proliferation of anti-abuse provisions that bring into the scope of abuse behaviors identified as abusive because they do not conform to international and European concepts of tax fairness. The notion of fictitiousness has been broadened in favor of the notion of validity, bringing within its scope behaviors previously considered as tax planning. This new approach to abuse of rights in tax matters is a source of uncertainty for taxpayers and liables and raises questions about the scope of the notion of abuse of rights in tax matters.
Keywords: Abus de droit; Abuse of rights; Anti-Abuse mesures; Choice of the path of least taxation; Choix de la voie la moins imposée; Dispositifs anti-Abus; Droit fiscal; Fraude et évasion fiscales; Fraude fiscale; Freedom of movement; Liberté de circulation; Optimisation fiscale; Tax fraud and evasion; Tax planning

La monnaie électronique dans les espaces bancaires européens, sous régionaux africains et OHADA - Fougou, Pierre Damien (Université de Bordeaux, 2025)
En tant qu’innovation majeure, la monnaie électronique s’est imposée dans l’écosystème financier en permettant aux agents économiques de répondre à des besoins distincts mais complémentaires tant en Europe qu’en Afrique. A cet effet, l’analyse de la monnaie électronique à l’aune de ces deux espaces géographiques, et précisément de trois espaces bancaires que sont l’UE, l’UMOA et la CEMAC, a notamment permis de mettre en lumière les différentes dynamiques qu’entraîne cet instrument moderne. En Europe, la monnaie électronique constitue une réponse pragmatique aux micropaiements dans une économie largement bancarisée. En Afrique, elle représente, bien plus qu’une simple solution aux micropaiements, un levier essentiel d'inclusion financière pour des populations majoritairement non bancarisées. Cette thèse propose une analyse juridique comparative de la monnaie électronique dans ces deux espaces géographiques, révélant des contextes socio-économiques contrastés ainsi que des perspectives radicalement différentes malgré une appréhension juridique commune. Afin de mener une analyse intégrant à la fois l’évolution juridique et technologique de la monnaie électronique et des moyens de paiements numériques, l’on consacrera la première partie de l’analyse à étudier les critères de qualification de la monnaie électronique, ce qui permettra de souligner que les espaces bancaires concernés par l’étude disposent d’une appréhension juridique commune en la matière, tout en ayant des appropriations technologiques différentes qui s’illustrent par des formes de monnaie électronique distinctes selon que l’on se trouve en Europe ou dans les espaces bancaires UMOA et CEMAC. Ensuite, l’analyse se poursuivra avec l’étude des innovations technologiques et des mutations juridiques qui ont eu lieu avec l’émergence de la monnaie électronique. Cette analyse sera également le pilier de la posture prospective dans laquelle s’inscrit cette thèse car elle permettra non seulement d’asseoir les réflexions sur la nécessaire évolution des critères monétaires face à l’émergence des moyens de paiements numériques, mais également de plaider pour un changement de paradigme qui consistera principalement à réduire l’ampleur du monopole monétaire traditionnel, et à instaurer une concurrence plus dynamique entre moyens de paiement. Dans cette démarche prospective ayant pour objectif d’améliorer l’efficacité des moyens de paiement et de garantir une inclusion financière plus optimale, l’on proposera également que soit attribué un cours légal à la monnaie électronique en Afrique, et que soit mis sur pied un jeton de monnaie électronique de banque centrale s’appuyant sur la technologie des registres distribués, et ce, afin de favoriser l’intégration économique africaine. En somme, la monnaie électronique constitue bien plus qu'une simple innovation technique. Elle est et peut devenir un véritable vecteur de transformation profonde des systèmes financiers et du droit monétaire. Son encadrement juridique doit donc continuer à évoluer pour accompagner son développement exponentiel. En Afrique particulièrement, les régulateurs gagneraient à en faire un instrument privilégié d'inclusion financière et d'intégration économique régionale, et ce, en optant pour des réformes juridiques et institutionnelles ambitieuses. Cette recherche propose ainsi de repenser les fondements du droit bancaire et monétaire non seulement afin d’adapter la monnaie électronique aux réalités d’une économie de plus en plus numérisée et moins centralisée, mais surtout afin de faire de cet instrument moderne un outil propice aux besoins d’intégration économique en Afrique. As a major innovation, electronic money has established itself in the financial ecosystem by enabling economic agents to meet distinct yet complementary needs in both Europe and Africa. To this end, the analysis of electronic money through the lens of these two geographical areas, and specifically of three banking zones – the EU, WAMU, and CEMAC – has notably highlighted the various dynamics generated by this modern instrument. In Europe, electronic money represents a pragmatic response to micropayments in a largely banked economy. In Africa, it constitutes far more than a simple solution for micropayments; it serves as an essential lever for financial inclusion among predominantly unbanked populations. This thesis offers a comparative legal analysis of electronic money in these two geographical areas, revealing contrasting socio-economic contexts as well as radically different perspectives despite a common legal understanding. In order to conduct an analysis that integrates both the legal and technological evolution of electronic money and digital payment methods, the first part of the analysis will be devoted to examining the qualification criteria for electronic money. This will underscore that the banking zones covered by the study share a common legal understanding of the matter, while having different technological appropriations that are illustrated by distinct forms of electronic money depending on whether one is in Europe or in the WAEMU and CEMAC banking zones. Subsequently, the analysis will continue with the study of technological innovations and legal transformations that have occurred with the emergence of electronic money. This analysis will also serve as the cornerstone of the forward-looking approach that underpins this thesis, as it will not only ground reflections on the necessary evolution of monetary criteria in the face of emerging digital payment methods, but will also advocate for a paradigm shift consisting primarily of reducing the scope of the traditional monetary monopoly and establishing more dynamic competition among payment methods. Within this forward-looking approach aimed at improving the efficiency of payment methods and ensuring more optimal financial inclusion, it will also be proposed that electronic money be granted legal tender status in Africa, and that a central bank electronic money token be established based on distributed ledger technology, in order to promote African economic integration. In sum, electronic money represents far more than a mere technical innovation. It is and can become a genuine vector for profound transformation of financial systems and monetary law. Its legal framework must therefore continue to evolve to support its exponential development. In Africa particularly, regulators would benefit from making it a privileged instrument for financial inclusion and regional economic integration, by opting for ambitious legal and institutional reforms. This research thus proposes to rethink the foundations of banking and monetary law not only to adapt electronic money to the realities of an increasingly digitized and less centralized economy, but especially to make this modern instrument a tool conducive to the needs of economic integration in Africa.
Issue: 2025BORD0334
Keywords: Afrique; Bank; CEMAC; Communauté Economique et Monétaire de l'Afrique Centrale; EU; Electronic money; Espace bancaire; Monnaie électonique; OHADA; Organisation pour l'harmonisation en Afrique du droit des affaires; Pays de l'Union européenne; UE; UMOA; Union économique et monétaire Ouest africaine; WAMU

An evaluation of China’s securitization regulatory system - Cao, Lei (Université de Montréal, 2025)
Since its innovation as a modern financial product in the 1970s, securitization has swept the global financial market. In 2000s, in order to ease China’s concentrated debt risks in the banking system and to improve the country’s imbalanced financial system, the Chinese government started to promote a trial program of securitization. An associated regulatory system was then created to facilitate the development of the Chinese securitization markets. Unlike regulations drafted and applied in North America, where an ex-ante regulatory analysis procedure and an ex-post evaluation system are installed, the current Chinese securitization regulation system is built mainly upon a basis of trial and interim rules. In other words, Chinese regulations regarding securitization were not comprehensively assessed before their adoption and there has been no systemic ex-post evaluation of the current securitization regulatory system in the past 20 years. This raises the question of whether the Chinese securitization regulation system facilitates the achievement of its regulatory objectives. The author purports to answer this question using three tools: The theory of regulation, legal historical analysis of law, and comparative law. To begin the analysis, the author designs an analytical framework based on the theory of regulation to evaluate Chinese regulations on securitization. In this evaluative framework, perspectives and criteria are stipulated to guide and draw the boundary of the evaluation. While applying the analytical framework, the author reviews the development of the Chinese securitization regulatory system over the past 20 years. The author studies the historical context of regulations established and regulatory modifications adopted in order to assess whether the logic embedded in the current Chinese securitization regulatory system is still valid. To better evaluate the Chinese securitization regulatory system, the author also applies a micro comparison of certain Chinese securitization regulations with their counterparts in North America. The purpose of this comparison is also to understand whether the Chinese characteristics in Chinese securitization regulations facilitate the achievement of its regulatory objectives. At the end of this assessment, the author provides a report to find the merits and disadvantages of Chinese securitization regulatory system. Due to the evaluative nature of this research, no demonstrated solutions are proposed in this report. Depuis sa création dans les années 1970, la titrisation s’est répandue à travers le marché financier mondial. Dans les années 2000, le gouvernement chinois a commencé à promouvoir le programme de titrisation afin d'atténuer les risques liés à la concentration de la dette dans le système bancaire et d'améliorer un système financier déséquilibré. La règlementation associée a été mise en place pour faciliter le développement du marché chinois de la titrisation. Contrairement aux régles créées et appliquées en Amérique du Nord, qui suivent une analyse ex ante —c’est-à-dire avant leur adoption — et une évaluation ex post — soit après leur application pendant une certaine période, le système de réglementation de la titrisation actuellement en vigueur en Chine a été élaboré sur la base d’essais et de mesures provisoires. Autrement dit, la Chine ne s’est pas fondée sur une analyse ex ante approfondie, et n’a mené aucune évaluation systémique ex post de ses réglementations de la titrisation au cours des vingt dernières années. Ce système chinois de réglementation de la titrisation facilite-t-il ou non la réalisation de ses objectifs réglementaires ? L'auteur tente de répondre à cette question à partir de trois outils : la théorie de la réglementation, l’analyse historique du droit et le droit comparé. Pour commencer, l’auteur conçoit un cadre analytique basé sur la théorie de la réglementation pour évaluer les dispositions chinoises en matière de titrisation. Dans ce cadre d’évaluation, des perspectives et des critères sont proposés pour guider et délimiter l’évaluation. À la lumière de ce cadre analytique, l’auteur replace la réglementation chinoise de la titrisation dans son contexte historique et retrace les modifications apportées au cours de deux dernières décennies. Il s’agit ainsi d’évaluer si la logique qui a présidé à l’adoption de ces règles reste valide dans le contexte actuel. Mais pour mieux saisir les caractéristiques de la réglementation chinoise de la titrisation, l’auteur ajoute à cette analyse historique interne à la Chine des micro-comparaisons de la titrisation chinoise et de ses règles avec leurs homologues nord-américains dans différentes sections de cette thèse. C’est ainsi qu’il sera possible de voir si les caractéristiques chinoises de la réglementation en matière de titrisation facilitent ou non la réalisation de ses objectifs. Au terme de cette recherche évaluative, l’on proposera un rapport qui mettra en lumière les avantages et les inconvénients du système chinois. En raison de sa nature évaluative, cette thèse ne proposera aucune solution aux inconvénients repérés.
Keywords: China; Chine; Evaluation of Chinese; Financial Regulation; Marchés chinois; Réglementation financière; Securitization; Securitization Markets; Securitization Regulation; Titrisation; Titrisation (réglementation)

La régularisation fiscale en France des avoirs étrangers non déclarés - Goudarzi, Laurent (Université Paris-Saclay, 2025)
La procédure de régularisation fiscale en France des avoir étrangers non déclarés témoigne du combat de l'administration fiscale contre l'omission des déclarations des comptes bancaires et autres actifs situés hors de l'État de résidence des contribuables.À grand renfort de moyens matériels et humains ainsi que d'un arsenal juridique efficaces assurant une synergie des autorités compétentes à déceler une telle fraude, la présente étude traite également des enjeux et autres failles gravitant autour de cette procédure de mise en conformité fiscale.Dans cette optique, il convient de s'intéresser aux causes de la fraude fiscale et la favorisant, de s'interroger sur la volonté persistante à vouloir dissimuler ses avoirs à l'administration fiscale et enfin, de démontrer en quoi les mécanismes instaurés de dissuasion contre une telle fraude tendent conformément aux valeurs démocratiques. The procedure for the tax regularization of undeclared foreign assets in France testifies to the tax authority its fight against the omission of declarations of bank accounts and other assets located outside the tax residence of taxpayers.With the help of material and human resources as well as an effective legal arsenal ensuring a synergy of the competent authorities to detect such fraud, the present study also deals with the issues and other loopholes revolving around this tax compliance procedure.With this in mind, it is necessary to look at the causes of tax fraud and encourage it, to question the persistent desire to hide one's assets from the tax authorities and finally, to demonstrate how the mechanisms put in place to deter such fraud tend in accordance with democratic values.
Issue: 2025UPASH005
Keywords: Avoirs étrangers; Bank canvassing; Bank secrecy; Compliance; Compliance (droit); Démarchage bancaire; Foreign assets; Fraude fiscale; Lanceur d'alerte; Secret bancaire; Tax fraud; Whistleblower

L'obligation d'information du banquier : essai d'une théorie générale - Koyangana Mawoyi, Gracia (Université Paris-Saclay, 2025)
L'obligation d'information du banquier peine à trouver un cadre juridique cohérent. L'objectif principal de cette étude est de proposer l'essai d'une théorie générale de l'obligation d'information du banquier en abordant les questions qui dominent cette notion notamment les interrogations sur son contenu, sa nature et son régime. En effet, l'étude de la notion d'obligation d'information permet d'appréhender son contenu et sa nature marqués par un courant pluraliste qui tend à la multiplication des diligences d'information du banquier et donc à la multiplication des obligations d'information du banquier. Le contenu de l'obligation d'information du banquier va de l'information documentaire au conseil en passant par la mise en garde et l'éclairage selon le type d'opération envisagée et la qualité du bénéficiaire.Par ailleurs, la nature de l'exigence d'information du banquier traduit d'une part, une confusion entre les notions de devoir et d'obligation en droit positif alors qu'une distinction existe entre les deux notions conduisant en principe au régime de responsabilité contractuelle pour une obligation et au régime de responsabilité extracontractuelle pour un devoir. D'autre part, une imprécision peut être relevée concernant la nature extracontractuelle ou contractuelle de l'obligation d'information. Aussi, la pluralité de contenus et de natures de l'obligation d'information du banquier emporte des interrogations sur la cohérence de la notion.Cependant, cette pluralité témoigne de la volonté affichée de protection de la clientèle du banquier au regard de la fonction décisionnelle attachée à l'obligation d'information du banquier qui sert avant tout à contraindre le banquier à apporter des informations aux bénéficiaires, clients ou cautions, afin qu'ils puissent décider au mieux pour leurs intérêts. La recherche d'une cohérence du droit positif est également attendue par rapport au régime de l'obligation d'information du banquier.La controverse pendante ici tient à l'application de la responsabilité contractuelle à l'inexécution de l'obligation d'information du banquier même lorsque celle-ci est intervenue avant la signature du contrat. Cet état du droit positif est l'enjeux central qui fonde le raisonnement prônant la nature contractuelle de l'obligation d'information du banquier. Toutes ces considérations tendent à démontrer que l'obligation d'information du banquier est véritablement une notion fonctionnelle puisque la compréhension de la physionomie de l'obligation d'information se trouve dans la volonté du droit positif, notamment par l'action du juge, qui tend à apporter une solution aux difficultés concrètes rencontrées par les créanciers de l'obligation d'information.
Issue: 2025UPASH002
Keywords: Bank; Banque (responsabilité); Divulgation d'informations; General theory; Information disclosure; Obligation d'information documentaire; Obligation d'éclairer; Obligation de conseil; Obligation de mise en garde; Obligation to advise; Obligation to enlight; Obligation to provide documentary information; Obligation to warn; Théorie générale

A framework for bank resolution in Namibia - Eiseb, Bryan Karl Gunther (University of Pretoria, 2025)
Banks are regarded as special financial institutions because, apart from the various critical intermediary and other functions they fulfil in a financial system, the hallmark of their business models is receiving deposits from the public and using such deposits for extending loans against interest from which they make profit. Unlike other companies, banks are however vulnerable to loss of public confidence and remain exposed to various risks and failure. Banks are thus critically important actors in domestic and global financial systems, - thus their safety is critical to the maintenance of financial stability. As a result, banks are subject to stringent regulation and supervision to ensure their safety. Despite prudential regulation, the failure of banks remains a reality. If the risk of bank failure is not adequately addressed through appropriate regulation and supervision, , it may result in a financial crisis like the 2008 Global Financial Crisis (2008 GFC). Because banks play a special role in an economy and their failure may have an adverse impact on financial stability and depositors, this thesis aligns with the view expressed by academics and international organisations that there is a need for a special regime (lex specialis) to deal with the failure of banks since normal insolvency procedures are not suitable for this purpose. f. This is because bank failures require swift, timely intervention by a supervisor to resolve failing banks in an orderly and optimal manner to ensure the maintenance of financial stability, depositor protection and relegating bailouts with taxpayers’ money as a last resort. A very notable lesson that emanated from the 2008 GFC is the criticality of special resolution frameworks for banks; the need to balance the interests of shareholders, creditors, and depositors, while promoting financial stability objectives. As a result, the need for special resolution frameworks for banks which empowers Resolution Authorities with adequate resolution tools and powers to resolve a failing bank timeous and orderly , has become a legislative imperative in contemporary financial systems. To deal with bank failures in Namibia, the Banking Institutions Act, 2 of 1998 (the BIA 1998) contained provisions that allowed for the assumption of control and liquidation of a failed bank. However, the newly enacted Banking Institution Act 13 of 2023 (the BIA 2023 which repealed the BIA 1998) has changed that position and introduced a single provision in section 70 that provides for bank resolution. Until now, prior to the introduction of this very new statutory provision, all bank failures in Namibia were dealt with under the limited supervisory tools of the BIA 1998. This study seeks to determine whether section 70 of the BIA 2023, is sufficiently aligned with international best practice as captured in the Financial Stability Board’s Key Attributes of Effective Resolution Regimes for Financial Institutions (FSB KAs), issued in 2011, as updated in 2014 and 2024. Alternatively, if the regime introduced by the BIA 2023 does not adequately align with the FSB KAs it is then considered whether the new Namibian bank resolution framework requires to be strengthened further to better align it with the FSB KAs. To consider possible further reforms to the new Namibian bank resolution regime, this thesis considers the resolution frameworks in Germany and Nigeria by way of comparative studies to observe best practices.
Keywords: Bank; Financial stability; Key Attributes; Namibia; Resolution

A comparative statutory analysis of the causes of bank failures in Zimbabwe - Tsaura, Oscar (North-West University, 2025)
Zimbabwean financial sector has experienced significant periods of financial distress as depicted by numerous bank failures since 1980. Bank failure occurs when a financial institution experiences significant financial distress, rendering it incapable of fulfilling its obligations to depositors, shareholders and other stakeholders. In other words, bank failure is when a financial institution undergoes substantial financial distress rendering it unable to meet its obligations as they become due. In this thesis, the researcher adopted the definition of bank failure which refers to a situation where a bank is in financial distress and is recapitalised either by the central bank or a strategic investor, acquired by another institution, surrenders its license or the license is suspended, or it closes its operations altogether. This thesis reveals that in Zimbabwe bank failures can be attributed to various factors including the failure of regulatory and supervisory systems to detect irregularities in the operations of banking institutions. In addition, poor corporate governance practices such as inadequate oversight, inexperienced management, undue influence by dominant shareholders, nonperforming loans, excessive risk-taking, abusive related party transactions and noncompliance with laws are commonly cited as causes of bank failures in Zimbabwe. Bank failures often pose negative implications to the banking sector and banking stakeholders such as depositors and investors. This owes to the fact that banks serve as intermediaries that facilitate the avenues for deposits and extend credit services to individuals and the production sector of the economy. It is submitted that the proper functioning of banks requires effective and adequate regulatory supervision. Failure to provide robust and effective regulation of banks could lead to bank failures. This thesis presents a comparative analysis of the banking statutory framework of Zimbabwe and those of the UK and South Africa to determine if the banking laws in Zimbabwe are robust enough to prevent bank failures. The thesis reveals that the banking statutory framework in Zimbabwe is not robust enough to curb bank failures in times of stress because it lacks effective regulatory oversight. This thesis further reveals that poor banking regulation, inconsistent enforcement, weak regulatory insolvency procedures, and inadequate supervision framework are some of the weaknesses in the current banking statutory framework which needs to be rectified in order to combat bank failures effectively in Zimbabwe. The Banking Act does not fully incorporate the international best standards on bank supervision to prevent bank failures. Consequently, the banking statutory framework in Zimbabwe does not comprehensively and effectively provide for the prevention of bank failures like those of the UK and South Africa. The robustness of the banking statutory framework is in providing adequate and effective regulatory provisions and enforcement mechanisms that curb bank failures in Zimbabwe. The researcher proposes the adoption of a new model, the Zimbabwean twin peaks model, comprising the Zimbabwean Prudential Regulatory Authority and the Zimbabwean Financial Sector Conduct Authority. It is argued that if the adoption of the twin peaks model is considered and robustly implemented, it can prevent the causes of bank failures in Zimbabwe.
Keywords: Bank failure; Banking legislation; Banking statutory framework; Banks; Curatorship; Financial regulations; Financial stability; Fraud; Money laundering; Political instability; Zimbabwe

Essays on banking and society - Heyert, Axelle (Université de Strasbourg, 2025)
This dissertation examines the relationship between banking and society. It contributes to a better understanding of how banking affects society and, in turn on how society shapes banking practices. The first chapter studies the impact of inflation on trust in banks. Chapter two deals with the effect of trust in banks on financial inclusion. The third chapter investigates whether financial inclusion influences life satisfaction. Chapter four delves into how female bank leadership affects firm credit. The final chapter focuses on the influence of bank leaders’ age on sustainable lending. Overall, this dissertation highlights the important role of banks in societal development and the major influence of society in shaping banking practices.
Keywords: ACCESS TO CREDIT; Accès au crédit; Banking; Banks; Banques; Bonheur; Confiance; Financial inclusion; Gender; Genre; Inclusion financière; Inflation; Life satisfaction; Prêts durables; Sustainable lending; Trust in banks

A trans-border African crypto asset licence to promote economic growth and deepen financial inclusion - Van der Lith, Johann Daniel (University of Pretoria, 2025)
Financial technology (Fintech) is a rapidly growing industry, both locally and globally. In various ways, Fintech is undeniably transforming financial services and products in every possible part of the financial sector by changing how people access and use financial services. By using innovative technologies, such as distributed ledger technology and cloud technology, and combining large data sets, including alternative data sets, better products can be provided that can be hyper-personalised for market segments and improve access and participation in respect of financial services. Fintech is solving issues that touch the consumer, through a bottom-up approach, considering the retail consumer as a starting point, in contrast to the common traditional finance evolution from the institutional investors to the retail consumer in a top-to-bottom approach. What is exciting about what Fintech can do for Africa, is that it can move inefficiencies in services and product life cycles to become efficiencies and move the frontiers for already efficient products and services. Fintech, therefore, provides an opportunity to improve the archaic and pave the way for the future. This study focuses mainly on crypto assets to limit its scope. It first examines the Fintech landscape in Africa, more specifically, the activity level in each selected comparative country, namely Mauritius, Kenya, Zambia, Namibia and South Africa, and how the activity benefits or can potentially benefit the economy in the host country and lead to the deepening of financial inclusion. It further examines the regulatory frameworks in those countries. The study examines the regulatory approach taken and the local activity, exploring some of the risks identified in each country, and considers the requirements that regulators chose to implement to mitigate these risks, as well as the current state of regulatory frameworks. Consideration is given as to whether similarities in both the risks and the mitigation requirements exist and how this can be aligned across jurisdictions. Recently, international standard-setting bodies have increased their focus on ensuring the alignment and cooperation of regulatory approaches globally. In light of the call for alignment and increased collaboration through policy recommendations and guidance, and or regulators to provide comprehensive and effective regulatory approaches without stifling innovation, this study considers the theoretical possibility of allowing certain Fintech companies, specifically crypto asset service providers (subject to specified conditions) to operate across jurisdictions with a trans-border licence. This study examines Europe’s Markets in Crypto Assets Regulation, as it was the first of its kind continental-wide framework for crypto assets, offering numerous lessons to be learned from this framework. The Commonwealth Model Law on Virtual Assets is also considered, as it is intended to assist member countries in implementing Virtual Asset and Virtual Asset Service Provider regimes in their respective jurisdictions, as they deem appropriate. Lastly, the study will explore what a theoretical trans-border regulatory framework containing prudential and market conduct requirements could look like and what embedded supervision tools, for instance, through forensic nodes or zero-knowledge proofs, could be utilised to ensure that all the regulators participating as part of a licencing panel receive real-time data and have a full view of the level of compliance with the requirements imposed by the joint framework and can proactively and intrusively act, when needed. The proposed trans-border regulatory framework aims to support crypto asset service providers with multi-jurisdictional strategies in Africa in scaling their operations, with a focus on building Africa as a global Fintech hub. The proposed framework aims to achieve this through a harmonised regulatory framework that simplifies compliance, increases efficiencies, enhances innovation, allows for scalability, and better risk management. In addition to the goal of positioning Africa as a globally recognised Fintech hub, the harmonised framework aims to realise the purported benefits of the technologies utilised by crypto asset service providers, thereby deepening financial inclusion and promoting inclusive economic growth through increased access and participation, as well as lower costs.
Keywords: Crypto assets; Embedded supervision; Financial inclusion; Financial technology; Regulatory frameworks

Essai sur l'optimisation fiscale : exploration des mécanismes d'optimisation fiscale à travers l'étude des groupes de sociétés - Bakhtous, Siham (Université de Perpignan Via Domitia, 2025)
Cette étude explore les contours et les tensions de l'optimisation fiscale dans un monde globalisé et numérisé, à travers le prisme des groupes de sociétés. En retraçant l'histoire de l'impôt, elle met en lumière les transformations profondes du système fiscal mondial, où les stratégies fiscales transfrontalières se sont progressivement développées, en dehors des prévisions des législations nationales. Bien qu'enraciné dans le principe fondamental de la liberté de choisir la voie fiscale la moins imposée, l'optimisation fiscale a évolué en réponse aux mutations économiques, juridiques et technologiques, donnant lieu à des pratiques parfois controversées qui se situent aux frontières de la légalité et de l'éthique. À l'intersection du droit, de l'économie et de la politique fiscale, l'optimisation fiscale dépasse le simple objectif de réduction de la charge fiscale : elle reflète un processus global où la mobilité des capitaux et des actifs immatériels perturbe les règles fiscales classiques. Bien que souvent conformes à la législation, ces pratiques d'optimisation fiscale dites « agressives » perturbent l'équilibre des systèmes fiscaux mondiaux, contribuant à un phénomène préoccupant : l'érosion de la base d'imposition et le transfert de bénéfices vers des juridictions à faible fiscalité. Cette dérive a mis en évidence les défaillances des systèmes fiscaux nationaux, incapables de suivre le rythme des mutations économiques et de réguler efficacement les pratiques des multinationales. En déconstruisant les mécanismes sous-jacents de l'optimisation fiscale agressive, cette recherche invite à une critique constructive de l'arsenal législatif actuel. Elle souligne l'urgence de repenser les instruments fiscaux dans un contexte où la mobilité du capital et des actifs immatériels redéfinit les règles du jeu économique et de restaurer un équilibre entre les exigences d'efficacité économique des multinationales et la nécessité de garantir une justice fiscale à la hauteur des enjeux mondiaux
Keywords: Base erosion; Digital; Droit fiscal (droit international); Déductions fiscales; Groupes de sociétés; Impôts; Numérique; Optimisation; Optimization; Profit shifting; Restructuration; Restructuring; Réductions fiscales; Tax; Transfert des bénéfices; Érosion de la base d'imposition; Évasion fiscale

Impact of the basel accords on small indigenous banks in developing countries : the case of Zambia - Rolls II, Douglas Walter (University of Pretoria, 2025)
The purpose of this thesis is to evaluate the impact of the Basel Accords on small indigenous banks in developing countries, with particular concentration on small Zambian banks. The problem statement intends to investigate whether implementing the three Basel Accords is conducive to the growth of small banks in Zambia. The study further aims to determine whether the present approach to legal regulation of small banks in Zambia is appropriate. The methodology is based on desk-bound research and examination of both primary sources and secondary sources of material such as books, journals, and relevant articles. The study is impacted by the dearth of secondary research work and the difficulty of getting information from sources like the Zambian central bank and other information centres. While Basel I and II seem to have stabilised the Zambian financial sector, the Basel III Accord appears to have impacted negatively on many small banks to the extent that they have been forced into merger and acquisition arrangements with larger foreign banks to fund their undercapitalised positions to survive. It also emerges that the Zambian financial system is strongly linked to the international global economy; regionalisation with organisations like SADC and COMESA being the first stages in the process. This situation is likely to introduce increased instability in the Zambian financial sector by making banks more vulnerable to the vagaries of the international financial markets. It is thus recommended that the Zambian central bank should be more proactive in lobbying for better conditions for small banks from the Basel Committee for Banking Supervision and other international financial regulatory bodies; it should also avoid “cutting and pasting” rules from other jurisdictions to avoid possible distortions in the banking sector. It should also encourage further development of primary and secondary markets in low-cost paper and provide small banks with long-term, low-interest loans to support their growth. The Bank of Zambia, the Zambian central bank, should consider establishing a separate Act financial services Act for small banks to better regulate them. The central bank should also seek out non-Basel Accord solutions for small banks including re-examining the positive aspects of the infant-industry argument. Lastly, it should introduce a formal system for classifying banks in Zambia. At the international level, it is suggested that the global standard-setting bodies should undergo radical reforms to ensure that they are in tandem with the problems that banks in developing countries face as well as allow them to have a say in global standard setting. It is recommended that global standard-setting bodies apply simpler rules for smaller banks. The impact of the Basel Accords on small indigenous banks in developing countries and Zambia, in particular, is important because of the role that small banks play in developing economies in growing small and medium-sized businesses that are often ignored by large foreign banks. It is also important that small banks are allowed to grow into large and medium-sized banks to effectively compete against foreign multinational banks. Institutions based on neoliberal ideals appear to only serve Western businesses’ interests despite their call for all countries to create a level playing field. Due to the dearth of empirical research, there are several gaps in the work that may provide opportunities for further research in this important area of the law.
Keywords: Banking supervision; Basel accords; Basel committee; Developing countries; Financial regulatory framework; Small banks

La compliance en droit bancaire et financier, une fonction juridique et managériale - Amoussou, Henry (Université de Reims Champagne-Ardenne, 2024)
La compliance s’est traduite par une floraison des obligations, des techniques et des procédures, portées par des règles de ''droit dur'' et de ''droit souple''. Leurs mises en œuvre ont été confiées à de nouveaux acteurs. Dans le domaine bancaire et financier, loin de dénaturer la conformité et la régulation, la compliance les renforce en étendant les obligations de cartographie des risques et de vigilance aux risques de corruption et environnementaux. Cependant, le blanchiment de capitaux et le financement du terrorisme restent les risques dominants. Ils sont au cœur de la compliance, notamment au regard de l'activité de sanctions de l’Autorité de contrôle prudentiel et de résolution (ACPR). La prévention de ce risque impose la mise en application des dispositifs normatifs que sont les principes de cartographie des risques et de vigilance. Au-delà de la conformité aux principes normatifs (juridique), la compliance mobilise toutes les fonctions de l’entreprise au niveau opérationnel (management). Ces fonctions opérationnelles sont relatives aux procédures d’alerte, de signalements, de contrôles, de sanctions et constituent des dispositifs procéduraux. Pouvant être qualifiée en ce sens, de « fonction juridique et managériale », la compliance pousse à envisager autrement les régimes de responsabilités en milieu bancaire et financier, fondés sur des défaillances ''obligationnelles'', tant juridiques que managériales. Cela renvoie à l’épineuse obligation de connaissances en management requises pour les juristes et les autorités d’une part, et d'autre part, au caractère inextricable des fonctions juridiques et managériales (d’où les formations en droit des affaires et management).
Keywords: Compliance; Conformité; Droit bancaire; Droit financier

Essays on Corporate Finance and Corporate Governance - Ding, Zijun (McMaster University, 2024)
This thesis includes three essays that examine the effects of firm policies on labor costs, corporate culture, and stock markets. The first essay studies the impact of major customers on supplier firms’ performance, and I find that supplier firms are willing to collaborate with their major customers while keeping low financial leverages. The cooperation with major customers results in higher productivity and strategic alliance, which could explain the reduction in the labor share of supplier firms. In my study, labor share is defined as the ratio of labor costs to total revenue. Compared to firms without major customers, supplier firms with at least one major customer would reduce labor shares on average by 33% in absolute terms. The findings contribute to the growing literature on the global trend of labor share reduction. The second essay examines the effect of market competition on corporate openness, which is a particular aspect of corporate culture. Corporate openness reflects how open firms are when facing new ideas and experiences, and measures firms’ willingness to innovate and cooperate. I conclude that market competition improves firms’ corporate openness through good corporate governance. Furthermore, corporate social responsibility activities are seen as a positive social outcome of corporate openness. As to economic consequences, less open firms would experience stock return reductions when the market competition is high. The third essay studies the firms listed on Chinese stock exchanges that established an internal whistleblowing mechanism. The results show that the employee whistleblowing system prevents firms from misconducting and leads to reduced stock price crash risk. Furthermore, a cooperative corporate culture helps the internal whistleblowing system decrease crash risk, while an unfair organizational climate exerts the opposite influence. Overall, this study contributes to the emerging literature on the governance role of whistleblowing.

Selected legal aspects of money-laundering control in trade-finance instruments - Makuyana, Tsanangurai (University of South Africa, 2024)
The traditional perception that trade-finance instruments are less susceptible to the risk of money laundering has changed due to the increasing threat of trade-based money laundering (TBML). In the process of facilitating trade-finance transactions, financial institutions may be entrapped in the dangers of TBML and be abused for criminal gains. In this regard, the institutions play a significant role in ensuring that only legitimate trade is facilitated through trade finance without being tainted by TBML. Despite that, vulnerabilities for the vice have been discovered in the trade-finance sector. This study employs a macro-comparative approach in examining how selected jurisdictions respond to the problem of TBML in trade-finance instruments. It analyses the vulnerabilities of documentary credits, documentary collections, demand guarantees and standby letters of credit to the potential risk of TBML. The thesis compares the response of the South African AML regime with that of the English, the US and Singapore AML regimes to the threat of TBML in the selected trade-finance instruments. The study reveals, inter alia, that there is not much difference between the South African AML regime and the AML regimes of the comparative jurisdictions in terms of the legislative response to the challenge of TBML in trade-finance transactions. However, the difference is apparent when it comes to the varied institutional responses to the problem within the jurisdictions considered in this thesis. While South African AML authorities have not made any official pronouncement against TBML in trade finance, those from other comparative jurisdictions have done so. The latter have also gone a step further to produce best practice reports on TBML for banks and other financial institutions involved in trade-finance transactions to enable the institutions to prepare for the challenge. However, similar to the South African position, there has not been any legislative change in the comparative jurisdictions to provide for TBML in specific terms. This means that these jurisdictions also deal with TBML using current AML legislation, which was designed originally for cash-based money-laundering operations. Therefore, the institutions and laws under the South African AML regime are relevant in the combatting of TBML. However, they may require some modifications to appropriately counter the challenge. The study makes various policy and best practice recommendations to strengthen the South African AML regime against TBML in trade-finance transactions.
Keywords: AML Regime; Bankers Association for Finance and Trade; Black Market Peso Exchange; Customer Due Diligence; Demand Guarantees; Documentary Collections; Documentary Credits; English AML Regime; FinCEN; Financial Action Task Force; Financial Intelligence Centre Act 38 of 2001; Financial Intelligence Unit; International Best Practices; International Chamber of Commerce; International Trade; Money Laundering; Money-Laundering Control; Prevention of Organised Crime Act 121 of 1998; RBA; Red-Flag Indicators; SAMLIT; Singapore AML Regime; South African AML Regime; Standby-Letters of Credits; TBML; Trade Finance; Trade-Based Money Laundering; Trade-Finance Instruments; Trade-Finance Principles; Trade-Finance Transactions; US AML Regime; World Customs Organisation; the Wolfsberg Group

The use of blockchain for collecting value-added tax on online cross-border trade in digital goods - Kabwe, Ruddy Kapasula (University of Pretoria, 2024)
The collection of value-added tax from the cross-border supply of digital goods remains a challenge for tax authorities around the world. South Africa is no different. The traditional methods of collecting VAT from the supply of digital goods relies on the honesty of the consumer and on the supplier to account for and remit VAT to the tax authorities in the jurisdiction where the goods are consumed. The traditional collection models are often unreliable, inefficient, burdensome, and expensive for the consumers and the suppliers. The adoption of blockchain technology as a model to collect VAT on the cross-border supply of digital goods has the potential to alleviate the compliance burden on consumers and suppliers of digital goods, improve the efficiency of tax administration, and reduce VAT fraud. Importantly, blockchain technology can create trust between tax authorities, suppliers of digital goods, and consumers. This thesis critically discusses the advantages and disadvantages of implementing blockchain technology for the collection of VAT on the cross-border supply of digital goods in South Africa. This thesis unpacks the consideration factors for policymakers in the implementation of blockchain technology for the collection of VAT on cross-border trade in digital goods. The thesis makes recommendations for the South African VAT Act to be amended to make provision for the collection of VAT by utilising blockchain technology.
URI: https://repository.up.ac.za/handle/2263/97005
Keywords: Anonymisation; Blockchain technology; Decentralisation; Digital goods; Private blockchain; Smart contracts; Taxpayer privacy; Value-added tax

La titrisation - Chambon, Benoît (Université Paris-Est, 2024)
Près de dix ans après la crise des subprimes les opérations de titrisation connaissent un nouvel essor. Ce dernier fait suite notamment à des travaux de la Commission européenne qui, dès 2015, a fait part de son intention de réviser le corpus applicable à ces transactions dans la cadre de son plan d'action pour la construction de l'Union des Marchés de Capitaux. C'est ainsi qu'en 2017 un règlement portant sur les opérations simples transparentes et standardisées a été publié au journal officiel de l'Union européenne. Ce texte a vocation à être complété par un autre règlement relatif à l'opposabilité des cessions de créances. Au niveau international les règles de rétention de fonds propres applicables visant les expositions de titrisations ont été amendées afin de mieux prendre en compte les risques y attachés. En France le régime applicable à la gestion d'actif et au financement par la dette a été remanié. On peut se demander comment ces évolutions normatives ont influencé la manière dont les risques systémiques et idiosyncratiques sont créés, transférés et couverts dans le cadre des opérations de titrisation. Almost ten years after the subprime crisis, securitization transactions are experiencing a new boom. The latter follows notably work of the European Commission which, as early as 2015, announced its intention to revise the legal framework applicable to these transactions as part of its action plan for the Capital Market Union. This led in 2017 to the publication in the Official Journal of the European Union of a regulation on simple, transparent and standardized transactions. This text is intended to be supplemented by another regulation on the enforceability of assignments of receivables. At the international level, the capital retention rules applicable to securitization exposures have been amended to take better account of the risks associated to said exposures. In France, the legal framework applicable to asset management and debt financing has been revised. One can wonder whether the normative developments have influenced the way systemic and idiosyncratic risks are created, transferred and hedged in securitization transactions.
Keywords: Idiosyncratic risks; Risque idiosyncratique; Risque systémique; Securitization; Systemic risks; Titrisation

Les jetons participatifs : contribution au droit de la finance participative - Aliyev, Novruz (Université de Rennes, 2024)
Au-delà de l’aspect numérique, Satoshi, fondateur anonyme du bitcoin, évoque l’organisation de « Pair à Pair » (P2P). Elle correspond à l’algorithmique répartie sur laquelle le registre décentralisé de ces nouveaux actifs se fonde. Mais le Règlement MiCA exclut la finance décentralisée et ne donne aucune définition satisfaisante des crypto-actifs. On étend cette observation aux actifs numériques, insuffisamment cernés en droit français. L’analyse de l’organisation P2P s’impose. On a identifié chez certains jetons une organisation participative, distincte des groupements et des contrats-coopération. Elle se caractérise par un degré et une forme d’indépendance nouvelle ainsi que par une socialité orientée vers un objet de nature impersonnelle, ouverte vers l’extérieur et sans structure (ni groupements ni contrats). Elle façonne ainsi la structure d’émission et la forme représentative et négociable de ces jetons. Ils sont des écrits représentant un bien ou un service et non un droit à l’encontre d’une personne émettrice. Ils sont émis dans une organisation participative : sans partage de pertes, de bénéfices, de chiffres d’affaires ou d’autres fruits. Leur qualification civiliste est le produit et non le fruit, contrairement aux titres financiers. L’organisation participative, elle, s’analyse comme un système, une nouvelle catégorie juridique que l’ordre juridique peut accueillir. L’ouverture du système vers l’extérieur nécessite la négociabilité des jetons. Elle concourt à la financiarisation de l’économie réelle. Comme la structure d’émission de ces jetons participatifs, leur infrastructure polycentrique de négociation appelle une régulation par l’organisation. Ces jetons sont aussi hybrides parce que participatifs et monétaires, et en tant que tels peuvent être considérés comme des unités de financement ; nouvelle définition de la monnaie que l’on propose, pour ne pas la réduire à sa seule fonction de paiement. Les jetons participatifs perturbent la summa divisio entre la monnaie et les instruments financiers ainsi que le concept même de droit subjectif.
Keywords: Crypto; Crypto-Actifs; Cryptomonnaie; Decentralised finance; Distributed ledger technology.; Finance décentralisée; Financement participatif; Jeton; Jetons-monnaie; Monnaie; Registre réparti; System; Système; Token

Les financements sur une blockchain : nouveaux défis du droit financier à l'aune de la finance décentralisée - Bonnet, Joris (Université de Strasbourg, 2024)
Alors que la finance traditionnelle peine à se renouveler, les nouveaux applicatifs de finance décentralisée proposent des services financiers basés sur des protocoles innovants, codés et entièrement gérés par les utilisateurs. Les classifications historiques de la finance sont largement inefficaces et des catégories telles que celle des instruments financiers ne permettent pas de construire un encadrement pertinent. Celles-ci doivent être dépassées pour pouvoir encadrer de façon plus inclusive tous les actifs décentralisés. La communication financière est rendue désuète et nécessite une refonte pour prendre en compte les nouvelles motivations des investisseurs et les impératifs environnementaux. Traditional finance is struggling to renew, new decentralized finance applications offer financial services based on coded protocols entirely managed by users. Historical classifications of finance are largely ineffective and categories such as financial instruments do not allow to construct a relevant framework. These must be overcome to be able to regulate all decentralized assets in a more inclusive manner. Financial communication has become obsolete and requires an overhaul to consider the new motivations of investors and environmental imperatives.
Keywords: Actif décentralisé; Asset; Blockchain; Chaine de blocs; Contract; Contrat; Crypto money; Crypto monnaie; Cryptoactif; Cryptomonnaie; DAO; DEEP; DLT; DeFi; Decentralized asset; Decentralized finance; Droit des affaires; Droit financier; Finance décentralisée; Finances; Financial law; Fundraising; ICO; Jeton; Levée de fonds; STO; Security; Token

Girişim şirketlerinin finansmanının hukuki çerçevesi - Günay, Yavuz Selim (Ankara Hacı Bayram Veli Üniversitesi, 2024)
Girişimcilik hem ülkemiz hem de dünya ekonomisi için, ekonomik gelişme sağlaması, istihdamı artırması gibi bir çok sebeple, son derece önemlidir. Girişimcilik ekosisteminde uygulanan finansman yöntemleri, sözleşmeler, hukuk kuralları gibi unsurlar dinamik ve esnek yapısı dolayısıyla geleneksel yöntem ve kurallardan ayrışmaktadır. Girişimcilerin banka kredisi gibi geleneksel finansman yöntemlerine erişememesi dolayısıyla kitle fonlaması, gölge pay, aile ve arkadaşlar, girişim sermayesi ve melek yatırımcı gibi yenilikçi finansman yöntemleri ortaya çıkmıştır. Bu finansman yöntemlerinden en yaygın ve yapısal olarak kullanılanı girişim sermayesidir. Girişim sermayesi, çeşitli fonlar ve şirketlerden toplanan kaynakların, büyüme potansiyeli gösteren ve gelecek vadeden girişim şirketlerine, pay karşılığı yatırım yapılmasını ifade etmektedir. Girişim şirketleri bakımından finansman haricinde de bir çok faydası bulunan girişim sermayesi, Türk hukukunda SPK tarafından GSYO ve GSYF yapıları altında düzenlenmiştir. Girişim sermayesi uygulamasında en çok sorun teşkil eden hususlardan biri ise girişimci ile yatırımcı ilişkileridir. Girişimci ile yatırımcı arasında hem yatırım öncesinde hem de yatırım sonrasında bilgi asimetrisinin ve menfaat farklılaşmasının söz konusu olması, girişimci ile yatırımcı arasında yönetilmesi zorunlu hale gelen bir menfaat çatışması yaratmaktadır. Bu menfaat çatışmasının olumsuz etkilerinin en aza indirilememesi ve yönetilememesi sadece girişim şirketi için değil ülke ekonomisi için de olumsuz sonuçlar doğuracaktır. Girişimci ile yatırımcı arasındaki bu menfaat çatışmasının pay devir sözleşmesi, pay sahipleri sözleşmesi, paya dönüştürülebilir borçlanma araçları gibi çeşitli sözleşmesel düzenlemelerle yönetilmesi mümkündür. Ayrıca, girişimci ile yatırımcının kendi aralarında gerçekleştirecekleri sözleşmesel kurumsal yönetim düzenlemeleri de girişimci ile yatırımcı arasındaki menfaat çatışmasının yönetilmesinde etkili olacaktır. Entrepreneurship is important for both our country and the world economy for many reasons such as providing economic development and increasing employment. Elements such as financing methods, contracts and legal rules applied in the entrepreneurship ecosystem differ from traditional methods and rules due to their dynamic and flexible structure. Since entrepreneurs cannot access traditional financing methods such as bank loans, innovative financing methods such as crowdfunding, phantom share, venture capital and angel investors have emerged. The most widely and structurally used of these financing methods is venture capital. Venture capital refers to the investment of resources collected from various funds and companies in return for shares in promising venture companies with growth potential. Venture capital, which has many benefits other than financing for venture companies, is regulated by the CMB under the structures of GSYO and GSYF in Turkish law. One of the most problematic issues in venture capital implementation is the relationship between the entrepreneur and the investor. The fact that there is information asymmetry and interest differentiation between the entrepreneur and the investor both before and after the investment creates a conflict of interest between the entrepreneur and the investor that must be managed. Failure to minimize and manage the negative effects of this conflict of interest will have negative consequences not only for the venture firm but also for the national economy. It is possible to manage this conflict of interest between the entrepreneur and the investor through various contractual arrangements such as share transfer agreements, shareholders' agreements, convertible debt instruments. In addition, contractual corporate governance arrangements between the entrepreneur and the investor will also be effective in managing the conflict of interest between the entrepreneur and the investor.

Vergi ceza hukukunda muhasebe hileleri ve hukuki sonuçları - Parlak, Mehmet Ali (İstanbul Üniversitesi, 2024)
Bu çalışma, Vergi Usul Kanunu'nun 359. maddesinin (a) fıkrasının birinci bendinde düzenlenen "hesap ve muhasebe hileleri yapmak" hükmünün, suç ve cezada kanunilik ilkesini karşılayıp karşılamadığı temelinde suçun kapsamı, özellikleri, unsurları ve sonuçlarının doktrin, içtihat ve mevzuat hükümleri ışığında incelenmesini konu edinmektedir. Muhasebe hilesi geniş anlamda, işletmelerde meydana gelen değer hareketlerinin belgelendirilmesinden faaliyet sonuçlarının raporlanmasına kadar olan süreçte, işlemlerin gerçeği yansıtmayacak şekilde değiştirilmesidir. Bu itibarla muhasebe hilesi muhasebe, denetim, ticaret hukuku gibi farklı disiplinlerin inceleme alanlarına giren genel bir kavramdır. Bunun yanında vergi kaçakçılık fiili olarak vergi hukuku doktrininde de önemli bir yer tutan tartışma konusudur. Vergi hukukundaki tartışmalar, hükümdeki muhasebe hilesi kavramının tanımsız, torba suç, kaçakçılık suçlarının en geneli ve işlevsiz bir suç olup olmadığına yöneliktir. Bu tartışmaların kaynağı kanun koyucunun maddede suçun kurucu unsurlarına yer vermemesi ve herhangi bir soyut tipe dair belirleme yapmamasıdır. Bu bakımdan çalışmada farklı disiplinler bakımından muhasebe hilesinin kapsamı, yöntemleri, sebep ve sonuçları karşılaştırmalı olarak ele alınmış; tümden gelim yöntemiyle vergi hukukundaki muhasebe hilesi suçunun içeriği tespit edilmeye çalışılmıştır. Çalışmada ulaşılan sonuç; "hesap ve muhasebe hileleri yapmak" hükmünün suçu tanımlamak bakımından "belirlilik" ilkesini karşılamadığıdır. Dolayısıyla adli ve idari mercilerin subjektif değerlendirmelerinin önüne geçilmesi, hukuki kesinlik ve eşitliğin temini, hukuki güvencenin sağlanabilmesi ve normun işlerlik kazanabilmesi için bir düzenlemeye ihtiyaç duyulmaktadır. This study examines the scope, characteristics, elements and consequences of the crime in the light of doctrine, jurisprudence and legislation on the basis of whether the provision of "committing accounting and accounting fraud" regulated in the first paragraph of paragraph (a) of Article 359 of the Tax Procedure Law meets the principle of legality in crime and punishment. It is about to be examined. Accounting fraud, in broad terms, is changing transactions in a way that does not reflect reality, from the documentation of value movements in businesses to the reporting of activity results. In this respect, accounting fraud is a general concept that falls into the fields of investigation of different disciplines such as accounting, auditing and commercial law. Discussions in tax law are about whether the concept of accounting fraud in the provision is undefined, an omnibus crime, the most general of smuggling crimes, and whether it is a dysfunctional crime. The source of these discussions is that the legislator does not include the constitutive elements of the crime in the article and does not specify any abstract type. In this regard, the scope, methods, causes and consequences of accounting fraud in terms of different disciplines were discussed comparatively in the study; The content of the crime of accounting fraud in tax law has been tried to be determined by deductive method. The result reached in the study; The provision of "committing account and accounting fraud" does not meet the principle of "specificity" in terms of defining the crime. Therefore, a regulation is needed to prevent subjective evaluations of judicial and administrative authorities, to ensure legal certainty and equality, to provide legal assurance and to make the norm functional.
Tez N°857786
Keywords: Accounting; Finance; Fraud; Fraude fiscale; Maliye; Tax fraud

L'application du droit des obligations en droit fiscal : (contribution à l'étude de l'autonomie et du réalisme du droit fiscal) - Bretaudeau, Valérie (Université Paris 1, 2023)
Le postulat est l’existence d’un principe d’application du droit des obligations en droit fiscal. Puis, la réflexion a porté sur la consécration du principe, soit son existence et son expansion. Concernant son existence, l’origine du principe impliquait de revenir brièvement sur les controverses relatives à l’autonomie et au réalisme du droit fiscal et d’affirmer, à la suite de la doctrine, que ni l’une, ni l’autre n’existait. En effet, le droit fiscal est un droit de superposition. Ainsi, sauf exceptions, il est soumis aux autres disciplines juridiques dont le droit des obligations. Il serait aussi d’interprétation stricte. La thèse mettra en évidence que l’éventail des procédés d’interprétation est large et que le droit fiscal, n’est pas seulement interprété de manière stricte. En outre, une interprétation large du droit fiscal n’exclut pas l’application du droit des obligations, notamment. Quant aux manifestations du principe de l’application du droit des obligations en droit fiscal, et grâce à des exemples, elles se matérialisent par les renvois au droit civil aussi bien à ses définitions qu’à ses qualifications. S’agissant de l’expansion du principe en question, l’accent est mis sur ses deux origines, législative et jurisprudentielle. Là encore des exemples choisis illustreront les propos. Ensuite, la thèse s’intéresse aux fondements des exceptions à l’application du droit des obligations en droit fiscal. Il y a les règles spéciales de la fiscalité, d’une part. Il y a lutte contre la fraude et l’évasion fiscale, d’autre part.
Keywords: Droit des obligations; Droit fiscal; Impôt; Obligations (droit)

La régulation du lobbying en droit économique - Mbaka, Axel (Aix-Marseille Université, 2023)
La question de l’encadrement juridique du lobbying a longtemps été oubliée par le droit Français. Pendant un temps, seuls le droit pénal et l’autorégulation formaient les contours du faisable. Inspirée d’exemples étrangers, la loi n°2016-1691 du 9 décembre 2016 relative à la transparence, à la lutte contre la corruption et à la modernisation de la vie économique, dite « loi Sapin 2 », a renversé le paradigme en créant des obligations de transparence pour les lobbyistes et les pouvoirs publics. Pour contrôler le respect de ces obligations, la loi a aussi créé la Haute Autorité pour la Transparence de la Vie Publique (HATVP). Toutefois, à peine née, la régulation du lobbying est confrontée aux défis contemporains du droit économique. À l’heure des autorités de régulation, de la privatisation du pouvoir normatif et de la résurgence des nations, que peut encore la régulation du lobbying ?
Keywords: Contrôle de l'État; Droit économique; Economic law; Interest representatives; Lobbying; Loi Sapin 2; Lutte contre la corruption; Regulation; Représentants d'intérêts; Régulation; Sapin 2 law; Transparence; Vie publique

Le Conseil d'État et la régulation des marchés financiers - Sevagamy, Romuald (Université de Montpellier, 2023)
La contribution à la régulation des marchés financiers par différents acteurs tels que l’Autorité des marchés financiers (AMF), les institutions européennes ou le juge judiciaire, a fait l’objet d’importants travaux. Toutefois, la juridiction administrative n’a pas reçu les mêmes honneurs. Dans le cadre du contentieux de la régulation des marchés financiers, la compétence du Conseil d’État a été davantage décriée que saluée. En effet, d’aucuns ont pu soutenir que les difficultés résultant du dualisme juridictionnel en matière financière, justifieraient la suppression de la compétence de l’ordre administratif. La compétence unique de l’ordre judiciaire pour connaître des décisions individuelles de l’AMF, telles que les sanctions, étant présentée comme un remède à la complexité du contentieux de la régulation financière. Si bien que l’on est amené à se demander si la présence du juge administratif dans cette matière est véritablement indispensable. En d’autres termes, se pose la question de savoir si le Conseil d’État est nécessaire à la régulation des marchés financiers. La présente thèse a pour ambition d’apporter une réponse résolument affirmative. Depuis la création de l’AMF, la compétence en premier et dernier ressort du juge administratif a été étendue de manière importante. Ce dernier étant désormais compétent pour connaître des recours contre les décisions individuelles, prises à l’encontre des professionnels des marchés. La jurisprudence administrative constitue également une source d’enrichissement significative du droit de la régulation financière. En effet, tant les garanties procédurales que les règles de fond, qui encadrent le pouvoir de sanction de l’AMF, ont été consolidées par le juge administratif. Ainsi, le Conseil d’État s’est affirmé en tant qu’acteur incontournable de la régulation des marchés financiers.
Keywords: Administrative litigation; Administrative penalties; Autorité des marchés financiers; Contentieux administratif; Dualisme juridictionnel; Financial markets regulation; Jurisdictional dualism; Office du juge; Office of the judge; Places financières; Régulation des marchés financiers; Sanctions administratives

A comparative evaluation of the South African income tax regime for investments using trusts - Herbst, Hendri (Stellenbosch University, 2023)
This study evaluates the South African income tax regime for investments using trusts. It considers whether reforms are required, and if so, how can this be done to create a tax framework that will encourage investment, limit tax avoidance and curb capital outflows, while considering South Africa’s unique context and challenges.
Keywords: Income tax; Investments; Taxation; Trusts and trustees

Le particularisme de la répression pénale de la fraude fiscale - Cocly, Camille (Université de Saint-Etienne, 2023)
Le particularisme de la répression pénale de la fraude fiscale ressort de l’agrégation d’une pléthore de particularismes générés par la mise en œuvre d’un dispositif singulier de déclenchement des poursuites pénales. Le pouvoir discrétionnaire de l’administration fiscale de mettre en œuvre le dispositif de déclenchement des poursuites pénales pour fraude fiscale, plus connu sous l’appellation de verrou de Bercy, aura des répercussions sur toutes les étapes de la procédure pénale à l’instar d’un effet papillon. L’administration fiscale est en mesure de mettre en œuvre trois types de procédures administratives en cas de fraude fiscale : une procédure de recherche, une procédure de sanction et une procédure de recouvrement. Par conséquent, le recours à la répression pénale n’intervient qu’à titre subsidiaire afin de garantir le succès des procédures fiscales. Dans le cadre de la répression pénale de la fraude fiscale, dès lors que seule l’administration fiscale est en mesure de déclencher des poursuites pénales, la mise en œuvre du droit de punir est décidée par cette autorité administrative qui n’est pas indépendante car subordonnée au pouvoir exécutif en la personne du ministre du Budget. En conséquence, la répression pénale se retrouve détournée de son objectif primordial de rétribution afin de servir les impératifs budgétaires de l’administration fiscale dictés par le pouvoir exécutif. Outre un tel détournement, cette répression pénale sera exercée de façon inégalitaire puisqu’elle ne sera amenée à punir que les justiciables qui n’auront pas conclu une transaction avec l’administration. Le verrou de Bercy, en tant que pouvoir de faire obstacle à la répression pénale, s’il permet à l’administration de recouvrer l’impôt par transaction, il lui permet également de protéger les proches du pouvoir exécutif de poursuites pénales pour fraude fiscale. Le particularisme de la répression pénale de la fraude fiscale se nourrit de la réaction du législateur et de l’autorité judiciaire face à l’immoralisme qui s’évince du pouvoir de l’administration de permettre la mise en mouvement de l’action publique. En ce qui concerne le législateur, il va prendre un ensemble de mesures pour moraliser la vie politique, dont l’objectif est d’assurer la transparence sur les patrimoines des membres du pouvoir exécutif et des responsables politiques, de sanctionner plus sévèrement la fraude fiscale en renforçant la répression pénale de cette infraction. S’agissant de l’autorité judiciaire, si l’on peut remarquer une certaine détermination des autorités de poursuites à mettre en mouvement l’action publique lorsqu’elles sont saisies par l’administration fiscale, il convient de remarquer pareillement une certaine opiniâtreté du juge pénal à prononcer des condamnations pour fraude fiscale. D’autre part, les autorités de poursuites sont en mesure de s’affranchir des exigences procédurales du verrou de Bercy afin de poursuivre la fraude fiscale sous les qualifications de droit commun d’escroquerie et de blanchiment. Cependant, le constat de la faiblesse des peines d’emprisonnement prononcées ainsi que les possibilités d’aménagement de leur exécution soulèvent le curieux paradoxe d’une justice déterminée à condamner la fraude fiscale sans pour autant faire subir au fraudeur la violence légitime qu’il mérite. On peut se poser la question de savoir si une telle démarche moraliste de l’autorité judiciaire ne contribue pas à garantir le paiement de la dette fiscale. Cette réflexion est corroborée par l’avènement de la justice pénale négociée pour fraude fiscale, cadre dans lequel l’autorité judiciaire, à l’instar de l’administration fiscale, instrumentalise la répression pénale afin de recouvrer l’impôt.
Keywords: Bercy; Criminal-fiscal; Dispositions pénales; Droit; Droit fiscal; Fraud; Fraude; Fraude fiscale; Impôts; Instrumentalisation; Instrumentalization; Law; Lawsuits; Lock; Poursuites; Poursuites judiciaires; Pénal-fiscal; Taxes; Verrou

La fin de la fiscalité locale - Nazon, Romaric (Université de Montpellier, 2023)
Les impôts locaux avec pouvoir fiscal pour les collectivités territoriales sont progressivement démantelés par des allègements fiscaux de l'État qui aboutissent à la suppression de ces impôts. Le financement de la décentralisation dépend dès lors de plus en plus du partage de recettes fiscales nationales. L'impossible autonomie fiscale locale pousse à repenser les relations fiscales complexes entre l'État et les collectivités. La recréation d'un pouvoir fiscal local passerait par la concertation et la codécision entre l'État et les collectivités locales mais aussi, notamment, avec la crise de la démocratie représentative, entre des élus locaux et des citoyens. Cependant, la verticalité caractérise aujourd'hui les relations entre ces acteurs.
Keywords: Collectivités locales; Collectivités territoriales; Decentralization; Décentralisation; Décentralisation administrative; Finances publiques locales; Fiscalité locale; Impôt local; Local public finance; Local tax system; Territorial collectivities

La fraude à la loi en droit fiscal - Bach, Laurène (Université de Bordeaux, 2023)
Face aux crises et aux scandales financiers des dernières années, les préoccupations budgétaires des États ont évolué. En marge de la lutte contre la double imposition, il est apparu nécessaire de lutter contre les stratégies fiscales frauduleuses pour préserver la base imposable des États. D’abord reconnue par la jurisprudence européenne et française, la lutte contre la fraude à la loi s’est intensifiée avec l’ambitieux projet BEPS de l’OCDE. Les diverses initiatives se sont concrétisées par l’adoption de la directive « ATAD », la signature d’un instrument multilatéral reprenant les actions du projet BEPS ou encore l’instauration d’une nouvelle procédure d’abus de droit en droit interne. Il en a résulté une multiplication des moyens de lutte contre la fraude à la loi.Alors que la démarche poursuivie par les États était celle de la convergence au service de la lutte contre la fraude à la loi, l’intégration de nouveaux fondements en droit interne et les divergences rédactionnelles présentes au sein de ces fondements ont entraîné une fragmentation apparente de la notion de fraude à la loi, ainsi que des interrogations sur l’articulation des différents fondements désormais applicables.Toutefois, en comparant et en analysant le sens de chacun des termes employés dans les différents fondements, une définition unifiée de la fraude à la loi peut être retenue autour de deux critères : une volonté déterminante d’obtenir un avantage fiscal et le détournement de l’intention des auteurs des textes. Par ailleurs, une première grille d’articulation peut être développée à partir de critères d’articulation issus des éléments distinctifs des fondements de lutte contre la fraude à la loi. Cette dernière devra ensuite être confirmée par les différentes instances ainsi que la jurisprudence tant interne, qu’européenne.
Keywords: Abus de droit; Anti-abuse clause; Articulation; Clause anti-abus; Droit fiscal; Fraude; Fraude à la loi; Montage; Substance; Tax avoidance; Tax law evasion; Tax planning

Contribution à l'amélioration du cadre juridique du processus de passation des marchés publics au Cameroun - Dicka, John Eric (Université Paris-Saclay, 2023)
Un des maux endémiques de certains pays africains est la faiblesse du dispositif législatif et réglementaire de l'achat public, face aux nombreux et variés défis de développement et de satisfaction de l'intérêt général. Partout dans le monde, la gestion de la commande publique est sujette à des dérives (corruption, détournements de deniers publics, sous-consommation des crédits publics, favoritisme, collusion, etc.), tant les enjeux sont majeurs pour l'État, les entreprises, et l'économie. Mais le rôle de l'achat public réduit à l'assainissement de la dépense publique progresse et épouse de plus en plus la sphère de la gouvernance et d'autres missions d'intérêt général ; Si dans ce secteur sensible, certains États réussissent mieux que d'autres à calibrer et concilier ces objectifs, cela tient en grande partie à leur appareil légal et réglementaire et à la capacité des administrations comme des juridictions à l'appliquer. Ainsi ce sujet, quoique centré sur le droit camerounais, traite d'une problématique bien plus large qui concerne plusieurs États et dont les analyses comparatives faites dans ce travail avec d'autres systèmes proches, justifient un lien commun et profond.À partir du contexte d'application et des faiblesses Recensées du cadre normatif camerounais au niveau de la phase de conclusion de l'achat public, il s'agit d'étayer un constat : le droit camerounais des marchés publics ne semble pas permettre que les marchés publics soient conclus en garantissant à l'administration une certaine efficacité d'action dans l'atteinte de ses objectifs variés.Si ce constat aura pour effet d'identifier ces principaux enjeux, il doit se servir d'une analyse sérieuse de la politique et de l'idéologie des marchés au Cameroun que révèle avec force le processus de passation, afin de déboucher sur des moyens conséquents devant assurer aux textes leur capacité à concilier les fonctions initiales des marchés publics avec celles qui semblent de plus en plus émerger ces derniers temps ; le tout, en conférant aux textes des garanties d'effectivité dans ce sens.L'exemple (ou le contre-exemple ?) du Cameroun doit permettre de mettre en lumière des phénomènes très répandus à travers le monde, à savoir l'ineffectivité d'un dispositif légal et réglementaire et bien plus l'inadéquation normative par rapport aux objectifs d'intérêt général inhérents à l'action publique. L'étude ne tend donc pas seulement au constat statique d'une situation insatisfaisante et dommageable pour le pays, bien plus il vise une analyse valable par-delà les frontières du Cameroun : un droit positif aux multiples finalités - à mettre en lumière -, dont l'impact est insuffisant sur la pratique, et une proposition d'outils juridiques et de management public pour y remédier.
Issue: 2023UPASH010
Keywords: Afrique centrale; Approvisionnement public; Cadre juridique; Cameroon; Cameroun; Contribution; Intégration économique; Legal framework; Marchés publics; Marchés publics (droit); Passation; Process; Processus; Public contracts; Public procurement

Droit à l'eau et partenariats internationaux : réflexions aux confluences des droits de l'homme et du droit international économique - Meireles, Gustavo Fernandes (Université Paris-Saclay, 2023)
L'eau représente un besoin vital pour l'homme. Sous l'effet du changement climatique et en raison de sa mauvaise utilisation, sa disponibilité pour l'utilisation humaine est gravement menacée. En outre, mobiliser les moyens techniques pour en assurer l'accès est coûteux. En conséquence, l'accès à l'eau constitue un enjeu largement investi par les programmes de développement mis en avant par les institutions internationales, à l'instar des Objectifs du Millénaire définis en 2000 et des Objectifs de développement durable de 2015. Les partenariats y sont proposés comme des moyens adaptés pour pallier les déficits d'infrastructures, notamment dans des États en développement. Solution particulièrement encouragée par la Banque mondiale et d'autres institutions financières internationales, la participation privée par le biais de partenariats internationaux est prônée comme une solution de nature à associer les entités publiques généralement chargées des services de l'eau et de l'assainissement avec les entreprises du secteur ayant un savoir-faire reconnu en vue de développer l'accès à l'eau potable. Alors que les partenariats internationaux ont joué un rôle de premier plan dans l'agenda de développement pour favoriser l'accès à l'eau, sont-ils des instruments adaptés pour réaliser le droit à l'eau ? Le droit à l'eau n'a été reconnu que de manière progressive dans le système onusien de protection des droits de l'homme. L'étude met en perspective l'originalité des partenariats internationaux dans le secteur de l'eau et souligne la difficulté à les inscrire dans le cadre normatif qui s'impose pour la réalisation du droit à l'eau. Les partenariats internationaux constituent des ensembles complexes d'instruments juridiques mis en place pour l'accès à l'eau. Malgré des avancées récentes en faveur de la consolidation de la responsabilité des entreprises en matière de de droits de l'homme, la pratique témoigne de ce qu'ils sont insuffisants pour mettre en œuvre pleinement le droit à l'eau.
Keywords: Accès à l'eau; Droit à l'eau; Droit à l'eau (droit international); Droits de l'homme; Développement; Développement durable; Partenariats internationaux; Personnes morales (responsabilité); Responsabilité des entreprises

Prospects for an African continental model multilateral tax agreement for the co-ordination of cross-border corporate tax challenges - Fehun Aren, Marie-Louise (University of Pretoria, 2023)
This study explores the creation of an African Continental Model Multilateral Tax Agreement (MMTA) to address the limitations of current bilateral tax treaties and enhance existing African Regional Economic Community (REC) frameworks for more effective taxation of cross-border business profits. Focusing on critical international taxation framework issues such as taxing rights allocation, Permanent Establishment criteria, and tax dispute resolution, it compares African REC MMTA provisions with those in non-African agreements to identify key weaknesses and propose improvements. The proposed MMTA aims to ensure equitable taxing rights, update nexus rules to capture both physical and digital businesses, and provide robust dispute resolution mechanisms to foster investment. It advocates for harmonized tax policies and tax agreements across African RECs to minimize tax competition, promote intra-African trade, and support regional economic integration under the African Continental Free Trade Area (AfCFTA). By aligning with the Abuja Treaty’s objectives, the framework seeks to enhance revenue mobilization and sustainable economic development in Africa. This research provides a roadmap for creating a tailored multilateral tax treaty that balances diverse regional interests, addressing Africa’s development financing needs while promoting cross-border taxation efficiency.
Keywords: AfCFTA; African Continental Free Trade Area; Continental model; International taxation frameworks; Multilateral tax agreement; Revenue mobilisation; Tax treaties

Earnings Management and Default Risk - Nguyen, Loan (Victoria University of Wellington, 2023)
This thesis comprehensively investigates the relationship between default risk (DR) and earnings management (EM) by addressing inconsistencies in prior research regarding the level and direction of EM in response to varying levels of DR. The thesis extends beyond severe financial distress to include firms with low and medium levels of distress. It examines the non-monotonic relationship between DR and EM, considering accrual earnings management (AEM), real earnings management (REM), and total earnings management (TEM). The thesis also examines the impact of DR on the relative use of REM versus AEM. The moderating effect of the global financial crisis (GFC) on the relationship between DR and EM is also explored.Using a sample of 29,228 firm-year observations from 4,514 US-listed firms during 2001-2019, the study employs both the traditional two-step and the more recent one-step approaches to identify EM. Sensitivity analysis is conducted, including and excluding mining firms.The findings reveal a non-monotonic relationship between DR and REM, with a concave pattern observed for all measures of REM. Initially, REM increases as DR rises, but it subsequently declines with further increases in DR. AEM, on the other hand, shows a convex or monotonically decreasing relationship with DR, although statistical significance is not consistently observed. The results for TEM align with those of REM, indicating the dominance of REM in TEM. These findings remain consistent when excluding mining industry observations and using different measures for EM and DR.The implications of these findings are significant for managers, firms, regulators, lenders, investors, and other stakeholders. The non-monotonic relationship between DR and REM offers insights for decision-making and determining appropriate levels of EM during varying levels of DR. Regulators can utilise this relationship to identify potential risk areas and develop effective regulations. Lenders can assess financial statements more vigilantly, and investors can make more accurate risk assessments and informed investment decisions. The robustness of the results and the inclusion of different EM measures provide valuable insights to auditors, analysts, and government professionals, enhancing their understanding of the complexities and risks associated with EM during varying levels of DR.The study also uncovers that the relative use of AEM and REM is complimentary, but the impact of DR dampens the increase in REM for a given increase in AEM. This result holds across primary and alternative measures of DR and is of significant interest to managers, firms, regulators, and other stakeholders. It provides insights into the interplay between AEM and REM, enabling informed decisions about EM strategies under different levels of DR. Regulators can leverage this information to identify potential risk areas and develop effective regulations to mitigate EM practices that could lead to financial instability. Lenders and investors benefit from understanding how DR affects the relative use of AEM and REM, enabling them to assess financial statements and manage investment risk more accurately. The study’s findings contribute to a deeper understanding of EM dynamics and have practical implications for various stakeholders in the financial ecosystem.Furthermore, the thesis investigates EM measures during the GFC and the moderating effect of the GFC on the relationship between DR and EM. The inclusion of REM and TEM, in addition to AEM, provides a comprehensive understanding of how firms managed their earnings during the GFC, offering insights into the effectiveness and implications of different EM strategies during a financial crisis. It confirms the decline of AEM during the GFC, reinforcing existing knowledge about the impact of the crisis on EM practices. Additionally, it identifies a negative impact of the GFC on REM and TEM, providing further evidence of the challenges and changes in EM strategies faced by firms during the economic crisis. The study also finds an insignificant moderating effect of the GFC on the relationship between DR and REM, as well as DR and TEM, shedding light on EM variation across different economic stages.Overall, this thesis contributes to the EM literature by examining the non-monotonic impact of DR on EM measures, comparing different approaches to identify EM, exploring the moderating effect of DR on the relative use of AEM and REM, and investigating EM measures during the GFC. The insights from this research assist managers in decision-making, firms in adapting financial management strategies, regulators in developing policies, lenders in risk assessment, and investors in understanding the complexities and risks associated with EM. The findings have practical implications for various stakeholders in the financial realm, guiding decision-making, regulatory efforts, risk assessment, and investment strategies.Keywords: earnings management, accruals earnings management, real earnings management, default risk, global financial crisis, one-step approach, two-step approach.

L'immobilier, une source de revenus captifs soumise à une fiscalité punitive, confirmant l'inconsistance du droit de propriété - Guenfici, Alexandre (Université de Perpignan, 2023)
Le point de gravité fixant mutuellement Nation et Citoyen est le sol. Sur ce sol est institué un droit, celui de la propriété foncière privée, un lien juridique primordial unissant Citoyen et Nation. Au cours de l'histoire ce point de fixation qu'est la propriété foncière devient également économique, l'État fondant une grande partie de ses recettes fiscales sur le propriétaire et son patrimoine immobilier. Dans une société moderne où la propriété est intriquée avec son rendement économique, cette propriété se mue en un placement économique subissant désormais une fiscalité punitive, voire confiscatoire. La fiscalité immobilière montre cette appropriation par l'État d'une grande partie des fruits de la propriété privée ; transformant cet objet en un simple droit d'occupation, voire un droit de garde, chargé d'obligations sans plus de droits réels. D’un droit réel à un droit personnel la fiscalité immobilière, par le jeu de l'impôt sur les revenus et de celui sur le patrimoine, transforme ce droit en une obligation fiscale. Dans cette relation nécessairement léonine entre propriétaire immobilier et État, ce dernier propose des régimes de faveur encourageant à investir dans l'immobilier. Ces incitations emprisonnent dans une relation de longue durée l'investisseur, puis l'investissement réalisé, l'État modifie en cours de relations les clauses de ces régimes à son plus grand profit. Or, le contribuable s'engageant dans cette relation n'est pas informé que ces règles peuvent changer d'une manière unilatérale, sans préavis et rétroactivement. Ce modus operandi est particulièrement illustré par la location meublée, la location para-hôtelière, l'impôt sur la fortune immobilière et la transmission de ces biens et activités via le pacte Dutreil. Ce dispositif Dutreil, donné comme un pacte, ne garantit aucune sécurité lors de son exécution ; d'autant que rédigé par une seule partie, le contribuable, l'autre, l'État, n'intervient qu'a posteriori pour éventuellement le remettre en cause
Keywords: Fiscal; Fiscalité; Fiscalité immobilière; Immobilière; Location; Propriété immobilière et impôt; Real estate; Rental; Transmission

Mandatory Environmental, Social and Governance (ESG) Regulations: ESG Performance, Corporate Finance, and Investment - Michael, Emmanuel (Victoria University of Wellington, 2023)
This thesis investigates the relationship between cross-country mandatory environmental, social and governance (ESG) regulations and firm-level outcomes, such as ESG performance, corporate finance, and investment, for both developing and developed countries. ESG performance is initially examined to determine whether mandatory ESG regulations affect it and to what extent. Second, the study investigates the impact of mandatory ESG on corporate finance and investment. Lastly, the study explores whether mandatory ESG regulations affect firm-level outcomes based on countries' governance and economic systems, and industries. The study uses a large sample of 69,010 firm-years across 73 countries, over the period 2005 – 2020 to address the foregoing issues. In addressing the impact of mandatory ESG regulations on ESG performance, the study employs a difference-in-differences (DiD) design. The DiD technique can isolate the effect of regulatory shocks to firm-level outcomes. According to the DiD analysis conducted, cross-country mandatory ESG improves firm-level ESG performance in developed countries, but not in developing countries. The study also concludes that mandatory ESG regulations have a positive impact only on ESG components in developed countries and have a more dominant impact on environmental (E) component. The findings are robust to a range of checks and test cases, including a triple DiD design set-up and propensity score-matched sample. The study employs an investment Euler equation framework and generalised method of moments (GMM) estimators to explore how mandatory ESG impacts corporate finance and investment. Euler frameworks account for the dynamic nature of investment, whereas GMMs account for endogenous dynamics in dynamic models. The study demonstrates that mandatory ESG increases corporate investment by increasing firms' access to external funds. The findings are robust to a battery of tests, including a triple DiD design set-up, propensity score-matched sample and the parallel trends assumption. Using an investment Euler equation framework and the GMM estimators, the study explores whether the impact of mandatory ESG on corporate finance and investment is dependent on a country's governance and economic system. When mandatory ESG is affected by country factors such as governance systems and economic well-being, the effect of mandatory ESG on investment via internal finance channel persists, according to the study. However, while consistent results are found in developed countries, inconsistent results are found in developing countries. According to the study, oil, gas, and mining firms are likely to respond effectively to mandatory ESG regulations because of increased scrutiny and pressure. Overall, the findings from the study imply that cross-country mandatory ESG has had a positive impact on corporate ESG performance, finance, and investment. For firms located in developed countries, these findings hold consistently, while for those located in developing countries, the opposite holds true. Also, the study reveals that firms in the oil, gas, and mining industries effectively respond to regulatory requirements. As a result, this study provides policy makers and accountants with an understanding of how mandatory ESG impacts firm ESG activities and performance, which is crucial for regulatory reforms.
Keywords: Corporate Finance; Cross-Sectional Analysis; Developed countries; Developing countries; Economic Models and Forecasting; Finance; Financial Economics; Investment; Investment Euler equation; Mandatory ESG disclosure regulations; Panel Data Analysis; Sustainability Accounting and Reporting; Time-Series Analysis

Le droit de la résolution des défaillances bancaires : contribution à l'étude du traitement administratif des établissements de crédit peu solides ou défaillants - Moreau, Victoria (Université Côte d'Azur, 2023)
Si on eut un temps pu s'interroger sur la nécessité de régir les défaillances bancaires, l'intérêt de telles dispositions a été réaffirmé depuis les années 2000. Dans ce contexte, le législateur européen, désireux d'assurer la stabilité financière, a mis en place une véritable Union bancaire, dont le second pilier est composé d'un Mécanisme de résolution unique destiné à prévenir et à traiter les défaillances bancaires. Ont ainsi été conçus différentes procédures et instruments dits de résolution, pouvant être mis en œuvre par des autorités administratives spécialisées. Or, la notion de résolution bancaire est une notion qui semblait jusqu'alors inconnue. Pourtant, les dispositions qui la gouvernent ne semblent pas véritablement la définir, et lui octroient la nature de Mécanisme, qui parait inadaptée. En effet, en observant l'ensemble des éléments qui compose ce Mécanisme, il ne fait nul doute que le législateur ne s'est pas contenté de créer un dispositif de gestion des défaillances bancaires, mais est allé plus loin en élaborant un véritable droit sui generis. L'existence de ce droit doit être affirmée pour permettre à celui-ci d'être pleinement efficient. Il produit par ailleurs des effets considérables tant sur les sujets de droit qu'il gouverne, que sur les acteurs avec qui ceux-ci interagissent. Ces effets originaux participent à l'efficacité de la prévention et du traitement des défaillances bancaires. S'ils peuvent en ce sens être salués, certains risques doivent néanmoins être relevés, notamment à l'aune des droits fondamentaux. La jurisprudence naissante en la matière - mais déjà très instructive -, laisse présager un droit en évolution et aux enjeux multiples, qui fera sans nul doute l'objet d'un intérêt grandissant.
Keywords: Bank resolution; Banques (réglementation); Credit institution; Droits fondamentaux; Défaut de paiement; Entités systémiques; Etablissement de crédit; Faillites bancaires; Financial stability; Fondamental rights; Résolution bancaire; Stabilisation économique; Stabilité financière; Systemic entity

Le droit de visite et de saisie de l'article L. 16 B du Livre des procédures fiscales- contribution à l'étude de la protection du domicile par le juge judiciaire - Papagiannoulas, Anastasios (Université Paris-Saclay, 2023)
Le droit de visite et de saisie de documents de l'article L. 16 B du LPF constitue entre les mains de l'Administration fiscale une mesure d'enquête coercitive portant atteinte à l'inviolabilité du domicile. Validé par le Conseil constitutionnel, et par la Cour européenne des droits de l'homme, qui ont toujours considéré que les nécessités de la répression des infractions fiscales et de la fraude fiscale justifiaient l'attribution de telles prérogatives à l'Administration fiscale, le régime des visites fiscales se caractérise par les fortes garanties procédurales dont dépend la protection du domicile. Au premier rang de ces garanties se trouve le contrôle du juge judiciaire. L'ensemble des garanties en question a été particulièrement renforcé après l'arrêt Ravon de la Cour européenne des droits de l'homme, qui a subordonné le contentieux des visites fiscales au droit à un procès équitable. Leur aptitude à répondre aux exigences d'un équilibre subtil est la clé de la prépondérance des garanties procédurales en la matière. Celles-ci permettent, d'une part, de tempérer un déséquilibre structurel au stade d'autorisation et d'exécution des visites fiscales, qui se caractérisent par leur nature unilatérale et qui mettent sous pression le respect du domicile, tandis que, d'autre part, elles stimulent l'équilibre déjà présent après la visite fiscale, moment auquel la personne bénéficie du droit à un recours juridictionnel. A côté de ces garanties, les lacunes, tout aussi procédurales, du régime n'ont pas permis de davantage promouvoir cette difficile conciliation et de mieux protéger le domicile. A travers leurs effets négatifs, le renforcement des garanties procédurales réapparaît comme la condition indispensable d'amélioration de cette protection. Cette prépondérance des garanties procédurales se retrouve au sein du contrôle des visites fiscales par le juge judiciaire. Ce contrôle est réel et sérieux et peut ainsi être qualifié d'effectif. Pour autant, sa structure ne se calque pas pleinement sur les garanties de procès équitable. Ainsi, l'efficacité du contrôle du juge judiciaire est réduite. La prise en compte des garanties procédurales résurgit comme la condition indispensable de protection du domicile. Parallèlement avec le juge judiciaire civil, ad hoc compétent en matière de visites fiscales, le juge pénal renonce à contrôler cette mesure, bien que son contrôle soit une garantie indispensable et de nature à consolider les garanties procédurales et à mieux préserver le domicile. Son contrôle se caractérise également par une méconnaissance des garanties nécessaires pour assurer le caractère équitable du procès pénal.Le dénominateur commun de l'ensemble du régime des visites fiscales est la force des garanties procédurales, afin de protéger le domicile. Par ailleurs, ce régime a fonctionné comme un point de départ de leur extension, notamment en matière de perquisitions pénales. Un fond commun de garanties procédurales, assurant la protection du domicile, a priori et a posteriori, se forge progressivement et donne les garanties entourant les visites fiscales demeurent le noyau.
Keywords: Contrôle juridictionnel; Domicile (protection); Droits de la défense; Défense (procédure civile); Fraude fiscale; Fundamental defense rights; Garanties procédurales; Home protection; Inviolabilité; Judicial authority; Judicial control; Juge civil; Juge judiciaire; Juge pénal; Perquisition; Perquisitions et saisies; Procedural guarantees; Procès équitable; Respect du domicile; Saisie; Seizure; Visite fiscale

The adoption of international financial reporting standards and foreign direct investment inflows: the moderating effect of the institutional environment in Africa - Simbi, Chipo (Rhodes University; Faculty of Commerce, Accounting, 2023)
Globalisation has created a need for an international accounting language to facilitate the smooth flow of trade across countries. In 2003, in an effort to establish a global financial reporting language, the International Accounting Standards Board (IASB) developed a single set of high-quality accounting principles known as the International Financial Reporting Standards (IFRS). Over the last decade, several African countries have adopted IFRS, and Africa has become the second-largest adopting continent after Europe. IFRS promotes improved quality of disclosure of accounting transactions, reduces information asymmetry between preparers and users of financial information, lowers the cost of investing, and breaks down information barriers to cross-border investment. Researchers suggest many benefits of IFRS adoption for macroeconomic indicators such as Foreign Direct Investment (FDI). The reduction in information acquisition and processing costs which translates into the reduction in investment costs, has been cited by most researchers. Researchers have argued, however, that the economic benefits of IFRS in Africa depend on the strength of the institutional environment. They also argue that the Western environment in which the IFRS was developed differs from the African environment. Thus, the universal approach of the IASB may not be appropriate due to the historical, social, economic and political context of African countries. The impact of the adoption of IFRS by African countries requires further examination, particularly as a weak institutional environment confronts many African countries. Three research questions are designed for this study; (1) Is there a significant change in FDI inflows for IFRS adopters in selected African countries after the adoption? (2) Is there a significant change in FDI inflows due to the institutional environment? (3) Does the institutional environment in IFRS-adopting countries moderate the effect of IFRS on FDI in selected African countries? The present study is underpinned by the new institutional theory, the information asymmetry theory, the eclectic theory and the signalling theory, each of which provide reasons why African countries have adopted IFRS. Nine hypotheses are developed, based on the research questions, and tested using the Systems General Method of Moments and the Difference-in-Difference method. The study uses data from 26 African countries, 15 adopting and 11 non-adopting countries, over the period 1996 - 2018. First, the study establishes that the adoption of IFRS positively and significantly affects FDI inflows into the selected sample of African countries. Second, the study concludes that legal enforcement, accounting and auditing standards enforcement, and language origin positively and significantly impact FDI inflows into these countries. Legal origin, however, has a positive but insignificant association with FDI inflows. Third, legal enforcement, historical ties, accounting and auditing enforcement and the quality of the institutional environment are found to moderate the effect of IFRS adoption on FDI inflows. These results indicate that IFRS is a crucial determinant of FDI inflows into African countries, but a supportive institutional environment is needed for African countries to attract FDI inflows after adoption. The results contribute to the accounting and finance literature on FDI into African countries, and may assist the investment community to assess the institutional risk associated with investing in IFRS adopting African countries.
http://hdl.handle.net/10962/419230
Keywords: Accounting; Auditing; Difference in differences; FDI; Foreign direct investment; Generalized method of moments; IFRS adoption; Institutional infrastructure; International Financial Reporting Standards; Investments

La protection des renseignements personnels du consommateur dans un système bancaire ouvert : étude comparative entre le droit canadien et le droit québécois ainsi que le droit de l'Union européenne et le droit français - Rakotomandimby, Lauriane (Université Laval, 2023)
Dans un marché bancaire oligopolistique, marqué par un nombre limité d'institutions bancaires et financières offrant des services bancaires de plus en plus innovants et attractifs à une quantité innombrable de consommateurs, le système bancaire ouvert a engendré la multiplicité de ces services, grâce aux entreprises de technologie financière qui se présentent comme des concurrentes de taille face aux banques traditionnelles. Désormais, le consommateur peut procéder à des transactions électroniques, dont celles relatives au paiement ou au transfert électronique de fonds, sans devoir passer au comptoir de sa banque traditionnelle. Depuis la mise en place du Règlement général sur la protection des données et de la Directive révisée sur les services de paiement au niveau de l'Union européenne, les entreprises commerciales peuvent avoir accès aux renseignements personnels, dont les données financières des clients de banques, notamment pour initier un paiement, par le truchement des interfaces de programmation d'applications. Toutefois, le traitement des renseignements personnels des consommateurs par les entreprises commerciales augmente le risque de vol d'identité, étant donné la présence d'une quantité impressionnante de données sur le Web, sans un contrôle adéquat pour en assurer la confidentialité. Les conséquences d'une fuite de ces données sont pourtant non négligeables, aussi bien à l'égard de la banque, de la personne concernée que de l'État qui doit en assurer une protection optimale. Devant ce phénomène où le consommateur est vulnérable, l'État intervient pour le protéger et contrebalancer le déséquilibre dans sa relation contractuelle avec les prestataires de services financiers.
Keywords: Approche comparée; Confidentialité des données; Consommateur; Droit comparé

L'efficacité du recouvrement par l'Etat des recettes fiscales de la taxation sur la consommation : Etude du cas de la TVA au Togo - Tchitare, Mawèdéou (Université de Montpellier, 2022)
Le but de notre étude est de parvenir à un recensement puis à une typologie des difficultés en matière fiscale au Togo, précisément en termes de TVA, notamment le vécu quotidien entre l'Administration et les contribuables. Ainsi arriverons-nous, au travers des données tirées de nos différentes sources, à apporter des solutions aux difficultés ainsi répertoriées en incitant vivement l'Etat à la revalorisation et à la récupération des recettes fiscales inhérentes à la ressource TVA. L'intérêt porté à la TVA découle de l'importance de cet impôt au regard du volume des recettes fiscales étatiques. The aim of our study is to get to a census and to a typology of difficulties as far as fiscal system is concerned in Togo precisely concerning VAT, especially the experienced of relations between the Civil Service and the taxpayers. Thus, we will get trough some drawn data of our various sources, to bring solutions to problems thereby catalogued by urging vividly the state to the redress, to the revaluation, and to the recovery of fiscal incomes inherent to the VAT resource. The interest in VAT arises from the importance of this tax in relation to state's tax revenues.
Issue: 2022UMOND030
Keywords: Consumption taxing; Efficacité; Efficiency; Fiscal receipts; Recettes fiscales; Recouvrement; Recouvrement de l'impôt; Recovery; TVA; Taxation sur la consommation; Taxe sur la valeur ajoutée; Togo; VAT

Une analyse juridique comparative de la criminalité financière du point de vue du Royaume d'Arabie Saoudite et de la France - Radeef, Alhassan (Université Côte d'Azur, 2022)
La recherche s'est concentrée sur la lutte contre la criminalité financière, en interrogeant ce qu'est la criminalité financière et la pertinence de sa lutte. Dans ce contexte, l'examen critique des politiques anti-crimes financiers au Royaume part de l'hypothèse qu'initialement, les efforts internationaux pour lutter contre les crimes financiers se sont concentrés principalement sur certaines formes spécifiques. Il s'agit notamment du blanchiment d'argent et du financement du terrorisme, même si tout crime financier est presque certainement à un impact négatif sur les économies concernées. Pour se faire, notre recherche a adopté une approche comparative de la lutte juridique contre les crimes financiers dans l'Arabie Saoudite et la France, avec un accent particulier sur le rôle des intermédiaires financiers dans certaines formes spécifiques de crimes.Pour mener à bien l'analyse tout au long de cette recherche, nous avons présenté la situation de lutte contre le crime économique et de la législation qui les accompagne dans chaque pays dans une perspective à la fois historique et juridique, en fournissant si nécessaire une critique de leur efficacité. Afin d'explorer comment les stratégies de criminalité économique de l'Arabie Saoudite pourraient être améliorées, notre recherche a adopté une approche comparative analysant les réponses politiques et législatives à la criminalité économique en France sur quatre chapitres distincts.les chapitres traitent du cadre théorique pour les marchés financiers, où nous aborderons dans la première partie la définition et les rôles des marchés financiers, leurs origines et ses différentes phases de développement, aussi bien en France qu'en Arabie Saoudite. Elle portera également sur une catégorie particulière d'acteurs sur ces marches : les intermédiaires financiers.La seconde partie de ce chapitre nous allons examiner la question suivante: quels sont les crimes et délits des intermédiaires? La finance et ses sanctions dans le système saoudien? Quelles sont les points de convergences et de divergences dans la qualification des crimes et leurs sanctions entre le législateur saoudien et français pour limiter les crimes et délits sur le marché financier ? The research focused on the fight against financial crime, questioning what financial crime is and the relevance of its fight. In this context, the critical examination of anti-financial crime policies in the Kingdom starts from the assumption that initially, international efforts to fight against financial crimes focused mainly on certain specific forms. These include money laundering and the financing of terrorism, although any financial crime is almost certainly to have a negative impact on the economies concerned. To do so, our research adopted a comparative approach to the legal fight against financial crimes in Saudi Arabia and France, with particular emphasis on the role of financial intermediaries in certain specific forms of crime.To carry out the analysis throughout this research, we have presented the situation of the fight against economic crime and the legislation that accompanies them in each country from both a historical and legal perspective, providing if necessary a criticism of their effectiveness. In order to explore how Saudi Arabia's economic crime strategies could be improved, our research adopted a comparative approach analyzing policy and legislative responses to economic crime in France in four separate chapters.the chapters deal with the theoretical framework for financial markets, where we will discuss in the first part the definition and roles of financial markets, their origins and their different phases of development, both in France and in Saudi Arabia. It will also focus on a particular category of players on these markets: financial intermediaries.The second part of this chapter we will examine the following question: What are the crimes and misdemeanors of intermediaries? Finance and its sanctions in the Saudi system? What are the points of convergence and divergence in the qualification of crimes and their sanctions between the Saudi and French legislators to limit crimes and misdemeanors on the financial market?
Keywords: Arabie saoudite; Criminal law; Criminalité des affaires; Droit financier; Financial intermediaries; Financial law; France; Infractions économiques et financières; Intermediaires finançiers; Loi criminelle; Marché financier; Stock market

Les monnaies virtuelles : essai sur l'intégration d'une nouvelle classe d'actifs dans les concepts fondamentaux du droit privé - Guillebon, Thibaud (Université de Bordeaux, 2022)
Les États et leur droit sont concurrencés par l’émergence d’une grande diversité d’objets numériques, que l’on a pris l’habitude de considérer comme des monnaies virtuelles. L’expression de monnaie virtuelle est d’abord apparue pour désigner les monnaies et actifs de jeux en ligne puis les systèmes de soldes prépayés et de fidélisation en ligne créés dans le cadre de réseaux commerciaux. Pour autant, le phénomène a pris une ampleur considérable avec l’apparition des crypto-actifs, catégorie qui désigne les crypto-monnaies (bitcoin, ether, monero…) et les jetons émis en blockchain (jetons d’usage, jetons financiers, stablecoins). Bien qu’ils soient nés hors des cadres étatiques, les ordres juridiques se saisissent de ces objets qu’ils soumettent à des réglementations existantes ou sui generis afin de cantonner les risques posés par leur développement tout en bénéficiant des retombées économiques positives. Compte tenu de l’instabilité qui affecte tant le marché des monnaies virtuelles que leur environnement juridique, une étude juridique d’ensemble du phénomène impose de suivre une démarche conceptuelle qui consiste à partir des propriétés de l’objet à qualifier afin d’en réaliser l’intégration dans les ordres juridiques. Dans ce cadre, les monnaies virtuelles peuvent être envisagées comme une nouvelle classe d’actifs numériques, émis par un acteur privé dans le cadre d’un système informatique, qui peuvent servir de substitut monétaire. Certains de ces actifs sont représentatifs d’une promesse juridique d’un émetteur ou d’un tiers. D’autres sont des choses, constitutives de valeurs et objets de propriété. À cette dualité correspond la summa divisio des biens incorporels qui oppose les droits incorporels et les propriétés incorporelles. C’est sur la base de cette division fondamentale qu’il est proposé d’insérer cette nouvelle classe d’actifs dans les concepts fondamentaux du droit privé.
Keywords: Actifs numériques; Biens; Bitcoin; Blockchain; Commodity money; Crypto-Currency; Crypto-Monnaie; Digital assets; Electronic money; Goods; In-game currency and assets]; Jetons; Mondes virtuels; Monnaie représentative; Monnaie électronique; Monnaie-marchandise; Monnaies et actifs de jeux; Propriété virtuelle; Representative money; Token; Virtual property; Virtual worlds

A interdisciplinaridade do Direito Societário e do Direito Tributário: da desvinculação do balanço societário para fins tributários. O lucro contábil das concessionárias de serviços públicos de transmissão de energia elétrica - Ippolito, Marcelo Baeta (Universidade de São Paulo, 2022)
O tema que envolve as diferenças entre o lucro contábil para fins societários e para fins tributários é sempre polêmico, ainda que o lucro, para fins societários, no Brasil, seja utilizado como ponto de partida para a determinação da base de cálculo do imposto sobre a renda das pessoas jurídicas. Nesta tese, entretanto, estas diferenças serão abordadas sob ângulos diferentes e com base em situações contemporâneas e pragmáticas que expõem, com maior profundidade e clareza, as razões e fundamentos delas, de modo que, a despeito da reconhecida contribuição da interdisciplinaridade envolvendo o direito societário e a contabilidade e, por outro lado, o direito societário e o direito tributário, tendo como objeto de conhecimento o referido lucro contábil, será possível, especialmente por conta das novas dificuldades trazidas pela introdução do novo padrão contábil no Brasil, provar a conveniência e a necessidade da desvinculação do lucro contábil e suas respectivas regras de apuração, nos termos da legislação societária, para efeito de consideração como ponto de partida, de acordo com as regras atuais, para apuração da base de cálculo do imposto sobre a renda das pessoas jurídicas. Nesse sentido, inicialmente, o caminho a ser trilhado no presente trabalho de pesquisa e desenvolvimento da tese de doutorado é determinado pela consideração do direito como objeto cultural, criado pelo homem e, como tal, para ser conhecido e apreendido, necessário se faz a sua expressão em linguagem. Por outro lado, importante abordagem do tema levará em consideração que há independência da linguagem em relação à realidade, bem como que a mesma linguagem constitui a realidade conceptual que, por sua vez, é a única passível de ser objeto de conhecimento. Portanto, é possível afirmar que uma das contribuições originais da tese corresponde a essa abordagem do lucro como uma realidade conceptual, constituída pela linguagem contábil, na medida em que será capaz de fornecer maiores subsídios e elementos para melhor se mensurar as dificuldades do compartilhamento desse objeto de conhecimento pelo direito societário e tributário, promovido pela interdisciplinaridade desses ramos do direito, especialmente quando a realidade conceptual que atende aos interesses específicos do direito societário se distanciou enormemente da realidade conceptual que se quer regular por meio do direito tributário, tendo em vista a aplicação de novas normas sintáticas, semânticas e pragmáticas da linguagem contábil. Para efeito de se demonstrar o distanciamento das realidades conceptuais correspondentes aos objetos de conhecimento do direito societário e tributário, a utilização das demonstrações financeiras das Concessionárias de Serviços Públicos de Transmissão de Energia Elétrica como parâmetro traz, também, originalidade à tese, correspondendo à prova efetiva de como a utilização do lucro contábil societário, também para fins tributários, pode gerar mais dificuldades para ambas as áreas do direito do que contribuições positivas.
Keywords: Accounting; Concessionaires; Concessionárias; Contabilidade; Interdisciplinaridade; Interdisciplinarity; Lucro; Profit; Public Utilities; Serviços Públicos

Os Títulos de Crédito de Securitização Setoriais: o caso das emissões de Certificados de Recebíveis Imobiliários e de Certificados de Recebíveis do Agronegócio - Cerqueira, Bruno Saraiva Pedreira de (Universidade de São Paulo, 2022)
Os Certificados de Recebíveis Imobiliários (CRI) e os Certificados de Recebíveis do Agronegócio (CRA) têm sido amplamente utilizados no mercado de capitais brasileiro nos últimos anos. Tais títulos, criados originalmente para o mercado de securitização imobiliária e do agronegócio, não necessariamente representam operações de securitização propriamente ditas mas integram uma forma de incentivo fiscal concedido aos referidos setores da economia brasileira. Com a edição da Lei nº 14.430, de 03 de agosto de 2022 passou a ser possível a emissão de outros títulos de crédito no âmbito das operações de securitização, persistindo ainda os CRA e os CRI e os seus respectivos incentivos. O presente trabalho procura estudar o regramento aplicável às emissões de CRA e de CRI, incluindo o enquadramento desses títulos como operações de securitização, considerando os conceitos clássicos existentes, e a avaliação dos atuais incentivos fiscais existentes. Adicionalmente, estudar-se-á os emissores dos CRA e dos CRI, as denominadas companhias securitizadoras, considerando a recente regulamentação editada pela Comissão de Valores Mobiliários, qual seja a Resolução nº 60, de 23 de dezembro de 2021.
Keywords: CRA; CRI; Certificat de créance; Créance agroalimentaire; Créance immobilière; Sectors securitization; Securitização; Titres de crédit; Titrisation; Títulos de crédito

Responsabilidade civil por falha informacional no mercado de valores mobiliários: pressupostos e análise crítica - Ferreira, Mariana Martins Costa (Universidade de São Paulo, 2022)
O presente estudo teve como objetivo analisar os pressupostos e efeitos do regime geral de responsabilidade civil aplicáveis às falhas informacionais no mercado de valores mobiliários. A tese sustenta que (i) a responsabilidade civil por falhas informacionais é extracontratual, (ii) a falha informacional - comissiva ou omissiva - pode causar danos residuais, em caso de dolo na subscrição, e danos informacionais, em caso de distorção do preço da aquisição ou da venda dos valores mobiliários, (iii) o dano informacional depende (a) da aquisição ou venda de valores mobiliário no período entre a falha informacional e a descoberta, e (b) da correção do preço dos valores mobiliários na descoberta da falha informacional, (iv) o nexo de causalidade pode ser demonstrado por meio de estudos econométricos, (v) com base em juízo de probabilidade lógica, o julgador deve determinar a suficiência do estudo econométrico para demonstrar o nexo de causalidade, (vi) o dano informacional é a diferença entre o preço de aquisição ou de venda e o preço hipotético que deveria ter se formado, se não tivesse ocorrido a falha informacional, (vii) tanto a companhia como os administradores podem ser responsabilizados por danos causados por falhas informacionais, (viii) os titulares de valores mobiliários que adquiriram valores mobiliários por preço inflacionado ou venderam valores mobiliários por preço deflacionado podem ser lesados pela falha informacional, (ix) a responsabilidade civil possui função compensatória e não dissuasória, (x) com base no regime geral, a responsabilidade civil por falha informacional no mercado de valores mobiliários não consegue nem atender à função compensatória, nem colaborar para o funcionamento do sistema de tutela dos investidores. Ao final, são apresentadas propostas de lege ferenda para aprimorar o sistema legal de tutela do investidor, em especial, as normas de direito processual e de direito material sobre a responsabilidade civil por falha informacional no mercado de valores mobiliários.
Responsabilité civile pour manque d'information sur le marché des valeurs mobilières : hypothèses et analyse critique
Keywords: Civil liability; Disclosure violations; Falha informacional; Mercado de valores mobiliários; Responsabilidade civil; Securities market

L'imposition des bénéfices des multinationales du numérique dans l'État de consommation - Rombourg, Florent (Université de Montpellier, 2022)
En cette année 2022, la création d'un nouvel ordre fiscal international semble se profiler. La solution OCDE Pilier 1 et Pilier 2 adoptée par près de 140 Etats marque en effet une rupture avec les cadres traditionnels de répartition des droits d'imposition. Les raisons ayant amené le Cadre inclusif de l'OCDE à agir sont connues. L'établissement stable et le principe de pleine concurrence ne permettraient plus dans une économie numérisée d'assurer une répartition équitable de la matière imposable entre États. Alors que les États à fiscalité privilégiée, abritant le siège de plus grands groupes d'entreprises, seraient les principaux bénéficiaires de cette situation, les États de consommation en seraient les principales victimes. L'entreprise d'une refondation du droit fiscal international serait d'autant plus urgente que la dégradation de l'alliance entre le citoyen et l'impôt ne cesse de s'accentuer à mesure que s'installent sur les marchés des acteurs puissants de l'Internet comme les GAFAM, NATU ou autres BATX. Le goût prononcé de ces entreprises multinationales « globales » pour le « libertarianisme », conduit en effet à douter du bien-fondé d'une centralisation des attributs régaliens au niveau de l'État, et laisse présager l'institution d'un monde nouveau qui se structurerait horizontalement en dehors de toute intervention étatique.Toutefois, il ne saurait être choisi la voie d'une rupture avec le système actuel sans une démonstration de l'obsolescence des bases juridiques de répartition des droits d'imposition. C'est ainsi que la présente thèse a pour objet d'étudier précisément les normes sur lesquelles reposent la répartition de la compétence fiscale et des profits entre sociétés apparentées, leur mobilisation par l'administration fiscale et leur interprétation par le juge administratif français, afin de déterminer si le jugement récurrent d'obsolescence dont elles sont victimes est fondé.
Keywords: Beps; Digital economy; Fairness; Permanent establishment; Pilier 1 et 2; Pillar 1 and 2; Prix de cession interne; Prix de transfert; Transfert pricing; Économie numérique; Équité; Établissement stable; Établissements stables

An examination of the challenges posed by the internet economy for the South African income tax regime - Odhiambo, Oluoch Rodney (University of South Africa, 2022)
The way of doing business has changed significantly since the turn of this century due to the growth of internet technology and the global digital economy. This growth has reduced the importance traditionally attached to tangible assets and physical location in both commerce and taxation. This implies that any country that relies on physical presence to trigger tax liability in today’s digital economy may be forced to reconsider the relevance, effectiveness, and efficiency of its income tax legislation. This thesis postulates that South Africa’s income tax law and the international taxation principles it relies on in taxing cross-border and digital transactions have not grown in tandem with the changing landscape of today’s digital economy. The thesis contends that South Africa will not receive its fair share of tax from giant multinational enterprises such as Google, Facebook, and Amazon which operate and trade in the country, if it does not amend its income tax laws to address the challenges posed by the internet economy. In examining the challenges posed by the internet economy to South Africa’s income tax regime, the thesis commences in Chapter 2 by discussing the growth of the digital economy and its implications for South Africa’s income tax system. Chapter 3 offers a critical analysis of South Africa’s income tax laws and the international principles on which they rely in taxing the digital economy. Chapter 4 discusses the measures that South Africa’s government has taken to tax its digital economy, while Chapter 5 compares how the Organization for Economic Cooperation and Development (OECD), the European Union (EU), Kenya, India, and New Zealand have dealt with the issue of taxing the digital economy and the lessons to be learned from these jurisdictions. The thesis concludes in Chapter 6 by proposing recommendations that South Africa could consider to make its income tax regime more efficient and effective in taxing transactions that take place in today’s digitised economy.
Keywords: Cryptocurrency; Digital economy; Digital tax; E-commerce; E-signature; Electronic commerce; Formulary apportionment; Income tax; Internet industry; Signature électronique; Taxation; Virtual currency

La confiance numérique dans le domaine bancaire - Julien, Marine (Université de La Rochelle, 2022)
La digitalisation progressive qu’ont connue les banques ces dernières années a permis a ces dernières d’offrir des services plus rapides, plus pratiques, et souvent plus proche des attentes de leur clientèle. Cependant, ces nouvelles pratiques sont également associées par certains à un accroissement des risques pour leurs données et patrimoines. Les banques sont ainsi contraintes de rechercher comment gagner, et garder, la confiance numérique de leur clientèle. Face à cette problématique, plusieurs leviers sont envisageables, mais c’est principalement par la règlementation qu’elle est actuellement traitée, au travers, notamment, du RGPD, du règlement eIdas et de la DSP 2. Mais la règlementation est-elle vraiment un vecteur de confiance numérique efficace ? Dans cette étude, il s’agit ainsi d’étudier le rôle de la confiance numérique et l’incidence de la règlementation sur celle-ci aux différentes étapes de la relation contractuelle. The progressive digitization that banks have experienced in recent years has enabled them to offer faster, more practical, services, and often closer to their customers’ expectations. However, these new practices are also associated by some of their clients with increased risks for their data and assets. Banks are thus forced to find ways to gain, and keep, the digital trust of their customers. Faced with this problem, several solutions are possible, but it is mainly by regulation that it is currently dealt with, through, in particular, the GDPR, the eIdas regulation and the PSD 2. But is regulation really an effective way to reinforce digital trust ? In this thesis, we study the role of digital trust and the impact of regulation on it at the different stages of the contractual relationship between a bank and its clients.
Issue: 2022LAROD002
Keywords: Banque électronique; Banques digitales; Confiance numérique; Digital Banking; Digital trust; ElDAS; GDPR; Identité numérique; Protection de l'information (informatique); RGPD

La réforme des administrations douanières : le cas du Tchad - Djargollo, Jairus (Université Côte d'Azur, 2022)
Cette thèse est consacrée à l’étude de la Réforme des administrations douanières pouvant se situer dans un contexte général, mais en s’affirmant tout de même sur un cas assez spécifique, concernant l’administration des douanes tchadiennes. C’est pourquoi, elle est intitulée : La Réforme des Administrations Douanières : Le Cas du Tchad.Les administrations des douanes à travers le monde, sont obligées de conduire des réformes, compte tenu de la mondialisation des échanges qui impose les principes de libre échange. C’est un combat en fait, engagé contre toute sorte des barrières douanières qui ont tendance à faire obstacle à ces échanges mondiaux. L’un des objectifs de ces réformes douanières est d’assoir une certaine politique de facilitation des échanges commerciaux internationaux. C’est pourquoi l’OMC et l’OMD collaborent étroitement dans ce sens. Elles sont aussi obligées de rechercher l’adhésion des Etats à travers le monde dans le but de mettre en œuvre le libre-échange. Cette adhésion s’exprime par la réforme des douanes qui sont au cœur des activités du commerce international. Le second objectif se situe sur le plan national, par rapport à l’objectif fixé par l’État Tchadien à travers cette réforme douanière. L’État du Tchad, cherche sur le plan national, la concrétisation de la réforme des douanes à travers un plan d’amélioration des finances publiques. Ce plan est appelé Plan d’Action pour la Modernisation de la Gestion des Finances Publiques(PAMFIP).Cette réforme est bien engagée, mais ne donne pas des résultats satisfaisants. Le choix de ce thème permet de comprendre les difficultés réelles qui se posent à cette réforme, afin de proposer des approches de solution. MOTS CLÉS: Réformes des douanes, Douane, Administration des douanes, Droit Douanier, Libre échange, Commerce International, pays en développement, intégration économique, accords internationaux, politisation et dépolitisation de l’administration. This thesis is devoted to the study of the Reform of customs administrations, which can be placed in a general context, but still asserting itself on a fairly specific case, concerning the Chadian customs administration. This is why it is entitled: The Reform of Customs Administrations: The Case of Chad.Customs administrations around the world are obliged to carry out reforms, given the globalization of trade which imposes the principles of free trade. It is a fight in fact, waged against all kinds of customs barriers that tend to obstruct this world trade. One of the objectives of these customs reforms is to establish a certain policy of facilitation of international trade. That is why the WTO and the WCO are working closely together in this regard. They are also obliged to seek the adhesion of states around the world in order to implement free trade. This adhesion is expressed by the reform of customs which are at the heart of international trade activities. The second objective is at the national level, in relation to the objective set by the Chadian state through this customs reform. The State of Chad is looking at the national level for the implementation of customs reform through a plan to improve public finances. This plan is called the Plan of Action for the Modernization of Public Finance Management (PAMFIP). This reform is well under way, but is not producing satisfactory results. The choice of this topic makes it possible to understand the real difficulties which arise with this reform, in order to propose approaches of solution.
Keywords: Administration (depoliticization); Administration (politicization); Administration douanière; Commerce international; Customs; Customs administration; Customs law; Customs officer; Customs reforms; Developing countries; Douanes; Douaniers; Droit douanier; Economic integration; Free Trade; International Agreements; International Trade

Le secret bancaire : une institution en déclin - El Mir, Jalal (Université Paris-Panthéon-Assas, 2022)
Le secret bancaire, ou le secret professionnel du banquier, est l’obligation de l’établissement de crédit de tenir confidentielle, toutes les informations relatives aux soldes, opérations, et à l’identité de son client. Issu du devoir de confidentialité du banquier envers son client, il engendre aussi une valeur économique d’où son institutionnalisation économique comme moyen d’attirer les capitaux. Face à des pratiques abusives de dissimulation dans les réseaux bancaires, des fonds monétaires provenant de trafic de stupéfiants, de blanchiment de capitaux ou en dernier ressort de financement de terrorisme, son champ d’application s’est vu restreint par des lois lui imposant des exceptions pour ajuster son application, et menant de ce fait à l’institutionnalisation juridique de la notion. Après la crise financière mondiale de 2008, son domaine d’application se retrouve envahi par une vague de la transparence dans le monde des affaires. La notion juridique du secret bancaire qui s’était institutionnalisée se retrouve en déclin par des mouvements juridiques consécutifs de neutralisation de ses effets. Mais, son intérêt juridique demeure primordial, et sa valeur subsiste du fait de son rattachement au droit fondamental de respect de la vie privée, mais aussi pour son intérêt dans la confirmation de la confiance dans l’industrie bancaire, consacrant la notion du secret bancaire comme une valeur juridique et une nécessité. Banking secrecy, or the professional secrecy of the banker, is the obligation of the banks to keep confidential all information relating to balances, transactions, and the identity of its client. A derivative from the banker's duty of confidentiality towards his client, it also generates economic value, hence its economic institutionalization as a mean of attracting capital. Facing abusive practices of concealment in banking networks, of funds resulting from drug trafficking, money laundering or as a last resort the financing of terrorism, its scope has been restricted by laws imposing exceptions to adjust its application, and thereby leading to the legal institutionalization of the concept of bank secrecy. After the global financial crisis of 2008, its scope is vastly impacted and reduced by the wave of transparency in business environment. The legal notion of bank secrecy, which became institutionalized, is in decline due to the consecutive legal acts of neutralizing its effects. Nonetheless, its legal interest remains vital, and its value lays on the fact of its attachment to the fundamental right of respect for private life. Also, for its interest in the confirmation of confidence in the banking industry, enshrining the concept of banking secrecy, as a legal value and a necessity.
Keywords: Act of foreign sovereignty; Bank secrecy; Banques; Confidentiality; Confidentialité; Droit à la vie privée; Extraterritorial law; Fait du prince étranger; Financial Transparency; General Data protection regulation (GDPR); Law Foreign Account Tax Compliance Act (FATCA); Loi Foreign Account Tax Compliance Act (FATCA); Loi d'application extraterritoriale; Privacy; Règlement général de la protection des données (RGPD); Secret bancaire; Secret professionnel; Transparence (droit); Transparence financière; Vie privée

La production du droit par les entreprises en Afrique. Le cas du droit de la monnaie mobile dans la sphère publique camerounaise-CEMAC - Onchi Ngongang, Vanelle Dimitri (Université Côte d'Azur, 2022)
Symptomatique de la transformation technologique du droit d’hier et représentatif du droit de demain, le mobile money, ne bouleverse pas seulement le paysage financier (en l’occurrence par la remise en cause du monopole bancaire, la fragmentation des opérations bancaires et la pénétration des acteurs non bancaires notamment les Opérateurs de Télécommunication Mobile dans le paysage financier). Il heurte surtout la conception monocentrique du droit, encore omniprésente et omnipotente dans notre champ d’étude. En effet, le mobile money encore qualifié de monnaie mobile nous permet de témoigner de façon brute et factuelle de la réalité du pluralisme juridique et d’exposer dans une construction cohérente les raisons de la genèse des foyers normatifs privés ainsi que de comprendre la coexistence de plusieurs ordres juridiques dans un espace. C’est dans ce cadre que les multiples crises (crises des institutions étatiques, crises de la loi, carence et inadéquation de loi, inintelligibilité des lois, inefficacité et ineffectivité du droit étatique) qui touchent la sphère étatique ont été indexées comme sources de coûts de transaction, d’imprévisibilité, d’insécurité juridique, poussant les acteurs privés en quête d’un minimum de sécurité juridique et d’un droit adapté à leurs besoins à se livrer à une production normative. Les normes privées de la monnaie mobile ainsi produites ont, en raison de leur pertinence et de leur effectivité été incorporées dans la sphère publique, rendant par la même occasion difficile toute analyse (sans risque de se tromper) pertinente sur les sources réelles des normes en vigueur dans la sphère publique. Cette incorporation normative qui matérialise le dialogue normatif permanent entre la sphère privée et la sphère publique nous a conduit à esquisser une théorie d’interaction normative inter sphériques. Cette dernière nous semble indispensable non seulement pour rendre compte des rapports entre les ordres juridiques, entre les sources étatiques et les sources non étatiques du droit mais également pour penser la conception et la production du droit de demain. This paper defends the theory of legal pluralism in Cameroonian-CEEAC (Economic community central African States) legal order and aims to demonstrate that the omnipresence of monism in this area is incapable of describing the real legal world and the law as it is. A preliminary question not always considered in the debate, regards the existence of legal pluralism or private ordering is why private actors issue norms? The paper begins by looking at a variety of reasons why private actors produce norms and discusses in detail the concepts of the hierarchy of norms and their legal validity. The paper points out the fact that public space faced crises of state institutions regarding separation of powers, parliamentary time, terrorism and secession. These crises drawn all the attention of public space and affect its normative reactivity in the sense of regulating new activities, social practices. This legal ordering sometimes produces ineffective and unintelligible norms. There is no doubt that a poorly design law and ineffective access to the law can affect economic activities. The emergence of private norms can be explained in two different ways. It could be argued that, confront to an inadequacy law, private actors decide to subject their activities to non-state law. Produce norms is therefore a unique opportunity to private actors to free themselves from the constraints of the legal insecurity since the inadequacy or lack of state law expose them to additional transaction costs. This paper doesn’t or never claimed complete autonomy from legal system. I shall conclude that far to compete with legal space, private ordering help to discipline private actors and to organize new activities. The paper tries to explain why Mobile Network Operators (MNO) produce mobile money norms and intends to demonstrate that an increasing number of mobile money rules issued by GSMA, and MNO can be found within a corpus of rules of legal orders. We will try to identify, among layers of legal corpus rules, legal norms which originally come from private ordering. One could observe that mobile money private norms had been recognized by public actors through legal transplants. Other question not always considered in the debate, regards the existence of private norms which had not been incorporated to the contents of positive law. The importance of private norms in the regulation of mobile money system is undeniable. The mobile money private norms are an important source of public legislation, they structure mobile money operators’ agreement. It is important to be aware of their existence of private norms which has not be incorporated on state legal orders. This paper also outlines the impact of technology, more specifically of mobile money on the financial landscape and above all, the access of non-banking players MNOs in the financial landscape. By its characteristics, mobile money is on the way to change landscape of financial inclusion for unbanked countries. A financial market has born or raised around mobile money and now, Bank and other financial institutions must compete with MNOs, owners of the Unstructured supplementary service Data: which is a critical platform required to provide mobile financial services and to enable mobile financial service operators to access potential mobile money clients or to send responses to clients and confirm transactions. This relatively new roles for MNOs generate competition issues particularly in the case where one MNO in dominant position on the voice market also plays an active role in providing mobile money services or mobile financial services. Finally, this paper aims to describe and explain the various normative interaction between a private ordering and a state order especially regarding pure theory of law. To do so, we study a high number of sector (lex mercatoria) where we can verify normative interaction between legal norms and private norms. We therefore manage to theorize this normative interaction.
Keywords: Banking law; Banques; Cameroun; Communauté Economique et Monétaire de l'Afrique Centrale; Droit; Gsma; Legal pluralism; Mobile money; Mobile network operators; Monnaie mobile; Monnaie électronique; Pluralisme juridique; Responsabilité Sociale de l'Entreprise; Social Responsibility of Corporation; Sources du droit; Téléphonie mobile privée; Établissement de paiement

Foreign Bank Penetration, Institutional Structures and Banking Sector Stability in Sub-saharan Africa - Abeka, Mac Junior (University of Cape Coast, 2022)
Link broken
Keywords: Bank penetration; Banking sector; Sub-Saharan Africa

A regulação macroprudencial no sistema monetário e financeiro internacional contemporâneo : características e externalidades - Baungarten, Bruna Teixeira (Universidade Federal do Rio Grande do Sul, 2022)
Com a Crise Financeira Global (CFG), dos anos 2007 e 2008, há espaço para inflexões na política macroeconômica dos países e nota-se a emergência da utilização de instrumentos macroprudenciais como meio para a limitação do risco sistêmico. Assim, forma-se um cenário onde a alta integração financeira e a atuação de bancos e outras instituições financeiras de forma transnacional se encontra com a crescente utilização de regulações financeiras em âmbitos nacionais, de forma descentralizada e não necessariamente harmonizada internacionalmente. Nesse sentido, esta tese busca investigar a ocorrência de externalidades, ou vazamentos financeiros internacionais que podem ocorrer a partir da implementação de medidas macroprudenciais em uma determinada economia. Assim, a pesquisa situa a temática no cenário do Sistema Monetário e Financeiro Internacional, identificando os movimentos que levaram à formação desse movimento regulatório. Uma análise exploratória acerca da experiência internacional com instrumentos macroprudenciais é conduzida de modo a identificar tendências temporais, continuidades, rupturas e diferenças entre grupos de países na condução da regulação financeira macroprudencial. Ademais, é realizada uma análise empírica que busca somar à literatura que investiga as externalidades internacionais associadas à implementação dessas regulações. Essa investigação é realizada utilizando técnicas de estimação de dados em painel para 40 países entre os anos de 2000 a 2018. Como principais resultados da tese destaca-se que: a) A partir da CFG há a emergência de uma agenda voltada para a estabilidade financeira que tem como pilar a utilização de instrumentos macroprudenciais e, esses instrumentos são largamente utilizados pelas economias nacionais; b) As Economias Avançadas aumentaram proporcionalmente mais a utilização de instrumentos macroprudenciais e, também, diversificaram mais a sua estratégia regulatória que as Economias Emergentes ou em Desenvolvimento; c) O exercício empírico encontra evidências que sugerem a ocorrência de externalidades internacionais decorrentes da implementação de medidas macroprudenciais e que estes efeitos se mantém e até ganham significância estatística de acordo com a relevância sistêmica da economia que implementa a regulação.
URI: https://lume.ufrgs.br/handle/10183/248038
Keywords: Financial Regulation; International Externalities; Macroprudential; Regulação econômica; Sistema Monetário Internacional; Sistema financeiro internacional

Bank Bail-ins in International Investment Law - Duque-Cordero, Luciano (Universität Wien, 2022)
The global financial crisis led to the introduction of special resolution regimes for financial institutions. The most prominent innovation of these resolution regimes is the so-called bail-in tool, which allows regulators to recapitalise financial institutions by expropriating shareholders and creditors. This thesis analyses the conditions under which a hypothetical bail-in of a financial institution would constitute a compensable breach of international investment law. It identifies the issues that are most likely to be relevant if a bail-in were to be litigated before an investment arbitration tribunal. The thesis first addresses jurisdictional issues, in particular the question of whether bail-inable instruments can even be considered an investment in procedural terms. The analysis then continues to substantive standards of protection. It deals comprehensively with the question of expropriation and related issues such as compensation, the right to regulate, and causation. It concludes with possible violations of the fair and equitable treatment standard.
https://phaidra.univie.ac.at/detail/o:1417287
Keywords: Bail-in; Bank resolution; Expropriation; International Investment Law; Investments

Climate change and development : the global administrative law of the UNFCCC financial mechanism - Larrea, Gonzalo (European University Institute, 2022)
This research deals with the legal responsibility of states to provide climate finance to developing countries in order to facilitate climate mitigation and adaptation. The research demonstrates that the area of climate finance has not escaped globalization, where global actors operating at a level beyond the state (the UNFCCC and several Climate Funds) have increasingly taken over some of the climate finance functions previously performed by states. Against this backdrop, the thesis also examines the role of international bodies in providing climate finance, assesses to what extent these bodies are accountable to affected local stakeholders, and puts forward recommendations to foster increased accountability. The research project employs Global Administrative Law (GAL) as a normative framework for assessing and fostering accountability. This thesis is relevant, first and foremost, as an examination of the extent to which global climate finance is adequate for addressing climate change impacts in developing countries. To this end, it engages in a detailed analysis of the international legal framework for climate change and of the relevant financial instruments. It also engages in a normative evaluation of these instruments using the standards proposed by GAL. In keeping with this, the research gives substance and a better definition to these standards. As such, the thesis has the potential to contribute not only to the literature on climate finance, but also to the literature on GAL. It also sheds light on the relationship between climate finance and GAL, a topic that has been largely neglected in the academic literature so far.
Accepted: 2022-03-02T09:10:59Z
Keywords: Climate Change; Climatic changes; Environmental Law

Le droit souple en droit financier - Joly, Pauline (Université Paris-Dauphine, 2021)
Le droit financier régit des activités régulées et est caractérisé par l’intervention d’acteurs publics et privés, les régulateurs et communautés professionnelles. Ces acteurs de la régulation participent à bâtir le cadre normatif des activités financières. Certaines de leurs normes sont privées de la force obligatoire classiquement attachée au Droit. L’importance de ce droit souple, ensemble de normes juridiques non impératives, distingue l’architecture normative du droit financier. Marqué par la diversité de ses formes, modes d’élaboration et auteurs, il est complexe de les identifier. Leur caractère commun réside dans leur force normative, située sous le seuil de l’obligatoriété. Sans être impératif, le droit souple financier produit des effets juridiques. Il oriente les comportements au travers de mécanismes psychosociaux ou d’autres propres au secteur financier et à sa régulation. Il produit aussi des effets en s’articulant à des dispositifs de droits spéciaux ou du droit commun.
Keywords: Autorité de régulation financière; Autorité de surveillance financière; Droit souple; Financial market; Force normative; Marché financier; Normative force; Normativity; Normativité; Regulation; Régulation; Soft law; Source of law; Sources du droit

Four Essays on Tax Transition Reform in Developing Countries - Adandohoin, Kodjo (Université Clermont Auvergne, 2021)
Ces dernières années, la plupart des pays en développement sont confrontés à la nécessité de concilier deux impératifs : d’une part, une demande sociale forte qui nécessite un besoin de ressources publiques supplémentaires, et d’autre part le désarmement tarifaire consécutif aux politiques d’ouverture commerciale, qui les prive de la majeure partie de leurs recettes budgétaires. D’où l’impérieuse nécessité pour ces pays d’assurer une transition dans la structure de leur prélèvement public c’est à dire de transférer la pression fiscale du commerce extérieur vers la fiscalité domestique. Cette thèse s’intéresse à cette problématique et vise à étudier les conditions de réussite d’un tel phénomène dans les pays en développement au travers de quatre essais empiriques. Le premier essai concerne le rôle de la TVA et des droits d’accises dans une première vague de transition. La TVA étant un impôt neutre et à très large assiette fiscale, cette dernière a été suggérée comme outil majeur pour réussir le transfert des ressources publiques du cordon douanier vers la fiscalité domestique et en complémentarité avec les droits d’accises. Nos investigations empiriques soutiennent cette assertion théorique et montrent que le couple TVA-accise joue bien ce rôle de substitut aux recettes de porte en quasi baisse suite au démantèlement tarifaire dans les pays. Néanmoins le rôle d’appui de la TVA et des droits d’accises est limité à partir d’un certain seuil de baisse des recettes de porte, qui traduit aussi le fait que le potentiel de mobilisation fiscale par la TVA dans ces pays est limité et qu’il faudra s’en préoccuper. Dans le second essai nous analysons la transition de seconde génération basée sur les impôts directs (impôts sur les revenus et impôts fonciers). Nous trouvons que les impôts directs sont des outils pauvres de transition fiscale dans les pays en développement. Pourtant, nous trouvons que le développement financier est un médiateur certain et incontestable à une politique de transition fiscale de seconde génération basée sur les impôts directs, car permettant de recouper l’information sur les revenus des contribuables et de générer des traces documentaires à l’administration fiscale, qui permettent d’envisager une mise à fiscalisation des contribuables, gage de recettes fiscales directes supplémentaires dans les pays. Dans le troisième essai, nous nous intéressons à l’effet de la mise en place d’une réforme de transition fiscale sur l’efficience dans la collecte des recettes en menant une étude de cas pour l’union économique et monétaire ouest africaine (UEMOA). Nos résultats supportent l’affirmative, en ce sens que la réforme accroit globalement une mobilisation efficiente des recettes dans la zone UEMOA. Cette efficience entrainerait par ailleurs avec elle une amélioration du climat des affaires dans la zone, suite à la mise en place de cette réforme. Enfin nous terminons cette thèse par un quatrième essai qui interroge quand à lui les impacts distributifs et de pauvreté d’une réforme de transition fiscale basée sur la TVA. Quoique les résultats montrent une incidence régressive de la réforme sur le revenu des ménages, une redistribution par la dépense aurait le mérite d’atténuer l’incidence sociale de cette stratégie de réforme sur le revenu des contribuables.
Keywords: 2SLS-IV model; Accises; Administration fiscale; Analyse des frontières stochastiques; Business climate; Climat des affaires; Computable general equilibrium; Contrôle Synthétique; Coordination fiscale; Corporate tax; Developing countries; Développement financier; Efficience; Efficiency; Effort fiscal; Excise; Exemptions; Exonérations; Financial development; Fiscalité; GMM; Harmonisation; Harmonization; Impôt foncier; Impôt sur le revenu; Impôt sur les sociétés; Income tax; Inequality; Internet; Inégalités; Micro-simulation; Modèle 2SLS-IV; Pauvreté; Pays en développement; Politique fiscale – Pays en voie de développement; Potentiel fiscal; Poverty; Probit and Logit; Probit et Logit; Propensity scores; Property tax; Réforme fiscale; Scores de Propension; Stochastic frontier analysis; Synthetic control; TVA; Tax administration; Tax coordination; Tax effort; Tax potential; Tax reform; Tax transition; Taxation; Taxes sur le commerce extérieur; Trade taxes; Transition fiscale; VAT; Équilibre général calculable

La concurrence fiscale étatique - Mondonneix, Alix (Université Côte d'Azur, 2021)
La concurrence fiscale étatique naît du climat de tension régnant entre les différents pays. En effet, les Etats n’ontpas les mêmes besoins budgétaires, ce qui engendre une bataille entre les systèmes fiscaux afin d’attirer le plusgrand nombre d’agents économiques. La concurrence fiscale étatique apparaît donc comme une compétition entreles Etats. Ce phénomène s’inscrit dans une économie mondiale globalisée et tend à se renforcer depuis une dizained’années. Pour les contribuables, cette concurrence fiscale permet de bénéficier d’avantages fiscaux dans la mesureoù elle conduit à une convergence des régimes fiscaux des Etats vers des taux d’imposition plus faibles.Toutefois, dans l’optimisation de leur imposition, certains opérateurs économiques utilisent des régimes fiscauxnationaux de manière déloyale. C’est ainsi qu’est née la concurrence fiscale dommageable. Celle-ci fait l’objet d’unelutte active par l’Union Européenne (UE), l’Organisation de coopération et de développement économiques(OCDE) et les Etats eux-mêmes.Une solution doit impérativement être trouvée, d’autant plus que le contexte évolue du fait notamment de la crisesanitaire et de l’essor de l’économie numérique. Si on assiste à un échec des tentatives d'harmonisation fiscale, desmesures de coordination pourraient réguler la concurrence fiscale étatique et l'amener vers plus de loyauté.La quête d'une concurrence fiscale loyale entre Etats n'est pas seulement une question d’équilibre des financespubliques, mais un enjeu majeur dans la survie des systèmes fiscaux et sociaux des pays.Si le concept de concurrence fiscale reposait sur des approches issues de doctrines économiques, celles-ci sontaujourd’hui insuffisantes. C’est alors que le droit s’affirme comme essentiel dans l’appréciation de cette notionnotamment pour l’encadrer, la contrôler et la sanctionner. The tax competition between States arises from the high level of tension between the different countries.Indeed, as States do not have the same budgetary needs, an intense rivalry grew between the tax systems.Their main goal is to attract the largest number of economic actors. The tax competition between Statesis a battle between countries for competitiveness. This phenomenon is a part of a global economy and isgaining increasingly in strength for over a decade. As a result of this, tax benefits are provided fortaxpayers because the tax competition between States leads to a race to the bottom.However, in order to reduce the amount of tax, some economic operators cheat and breach the nationaltax regimes. And so, the harmful tax competition is born. The European Union (EU), the Organisationfor Economic Cooperation and Development (OECD) and the States fight the latter fact.It is important to devise solutions that minimise harmful tax competition and remove the in-built biastowards taxation of less mobile basis, especially because the context is changing due to the health crisisand the development of the digital economy. Even though the tax harmonisation fails, somecoordination measures could be used to regulate the tax competition between States. Loyalty is the keyterm.The quest for a loyal tax competition between States is not a matter of government finances at least inbalance. It’s a major challenge to the durability of tax and social systems of each country.Although the concept of the tax competition between States is based on economic doctrines, thisapproach is now obsolete. The law approach is essential to apprehend this notion, particularly to frame,control and punish it.
Keywords: Capital mobility; Concurrence fiscale; Course vers le bas; Droit fiscal; Fiscalité; Household mobility; Mobilité des ménages; Mobilité du capital; Pays de l'Union européenne; Politique fiscale; Race to the bottom; Relations fiscales intergouvernementales; Tax policy; Taxation

Digital economy and international taxation : the digital revolution and its impact on the discourse of international tax law - Pereira da Silva Campos, Marcio Augusto (Université Paris 1 ; Universidade de Brasília, 2021)
The impacts of the economy’s digitalisation process on taxation have become the central theme of international tax law in recent years, causing several reactions among actors in this field. The OECD has become the main forum for debate, causing government bodies, taxpayers, and academia to gravitate around the organisation’s texts. Nonetheless, the digital economy tax debate has constantly changed, taking on new languages and adopting different perspectives. From a formal legal discussion concerned with characterising payments to apply international tax treaties, the debate moved to an economic perspective involving substance. Finally, it took on a manifest political connotation, resulting in a re-discussion of the international tax field itself. This thesis aims to understand how and why the digitalisation of the economy managed to impact the fundamentals that support the international tax field. The work adopts a legal, realistic, and discursive perspective to achieve its objective, understanding international tax law as a field formed from historically identifiable events. In this case, while a social phenomenon, international taxation is the central object of a project that manifests itself both in the institutional and intellectual plane. In turn, the digitalisation of the economy results from a technological revolution characterised by the centrality of informational phenomenology. Such centrality is responsible for a social transformation process affecting the tax field’s institutional and intellectual dimensions. In this scenario, actors in the field perceive their inability to deal with the new digital reality from the conceptual tools provided by the tax legal discourse. The result is a paradigm shift with the potential to affect not only the field’s social practice but its very significance within an intellectual project for constructing the human dimension.
Issue: 2021PA01D020
Keywords: Campo tributário internacional; Champ fiscal international; Digital economy; Digital revolution; Direito tributário internacional; Discours fiscal international; Discurso tributário internacional; Droit fiscal (droit international); Droit fiscal international; Economia digital; Economie numérique; Feno-menologia informacional; Fiscalité internationale; Informational phenomenology; International tax discourse; International tax field; International tax law; International taxation; Phénoménologie informationnelle; Revolução digital; Révolution numérique; Société numérique; Taxes internationales; Tributação internacional

La microfinance et appui au microentrepreneuriat : cas du Burundi - Nsengiyumva, Théogène (Normandie Université, 2021)
Les microentreprises (ME) jouent un rôle important dans les économies des pays en voie de développement (PVD). Elles constituent les sources principales de la création d’emplois et génèrent des ressources importantes pour leurs promoteurs. Elles contribuent aussi de manière non négligeable à la formation du produit intérieur brut (PIB) dans les PVD. L’accès au financement est alors un défi crucial à leur création et à leur développement. Malgré leur rôle indéniable dans le développement socioéconomique, elles accèdent toujours difficilement au financement bancaire, et ce, en dépit des politiques publiques de soutien menées à leur égard. Cette thèse vise à analyser les facteurs explicatifs du faible financement des microentreprises (ME) dans le cas du Burundi. Les données que nous avons exploitées dans cette thèse proviennent des deux bases. Celle issue des données collectées sur 3430 dossiers de crédits des institutions de microfinance (IMF) burundaises et celle réalisée auprès de 223 microentrepreneurs à partir d’une enquête. A l’aide du modèle probit, l’analyse économétrique a révélé que certaines caractéristiques des microentreprises et/ou de leurs promoteurs comme l’âge du microentrepreneur, la durée du crédit sollicité, la zone d’implantation de la microentreprise influent négativement sur l’accès au financement. D’autres caractéristiques telles que la nature de la garantie présentée, le profil du microentrepreneur ou son niveau de richesse jouent positivement sur le financement des microentreprises. L’étude a montré aussi que la microfinance reste un moyen efficace pour financer les microentreprises. Ainsi, la restructuration des fonds de garantie et l’engagement accru du gouvernement surtout en matière d’accompagnement sur le terrain améliorerait le financement des microentreprises. Microenterprises (ME) play an important role in the economies of developing countries (DCs). They are the main sources of job creation and generate significant resources for the formation of Gross Domestic Product (GDP) in these economies. Despite their undeniable role in development, they still have difficulty accessing external financing for debiting public support policies for them. This thesis aims to analyze the explanatory factors of the low funding of EM. It takes Burundi as a case study and assesses the key role of microfinance in supporting MOEs. To achieve this dual objective, this study used two databases: the one containing data collected on 3430 loan files of Burundian microfinance institutions and the one consisting of data collected from 223 microentrepreneurs by a survey. The analysis used the probit model and revealed that certain characteristics of microenterprises and / or their promoters such as the age of the microentrepreneur, the duration of the credit sought, the microenterprise location area have a negative impact on access to microenterprise financing. Other characteristics such as the nature of the guarantee presented, the profile of the microentrepreneur or its level of wealth play a positive role in financing microenterprises. The study also showed that microfinance remains in a strategically appropriate position to finance microenterprises. In final, the restructuration of the guarantee funds for nonagricultural microenterprises and the accompaniment of the government would make MFIs more effective in contributing to the financing of smallholder Enterprises.
Keywords: Burundi; Conditions économiques; Entrepreneurship; Financement; Financing; Microentrepreneuriat; Microentreprise; Microfinance; Microfinance institutions; Smallholder enterprises

Firm Performance, Financial Constraints, and Dual-Class Share Structure - Ahamed, Fatematuz Tamanna (Victoria University of Wellington, 2021)
This thesis addresses two aspects of financial constraints focusing, firstly, on the impact of financial constraints on firm performance and, secondly, on the impact of dual-class share structure on financial constraints. The first issue has been addressed in a large number of research studies, but the results are mixed. This study, therefore, conducts a meta-analysis of those earlier studies to provide a summary view of the results which, in contrast to narrative reviews of the empirical literature, provides an objective overview. The second issue examines the impact of dual-class share structures on financial constraints. The period of the global financial crisis is used to test the impact of the state of the economy on that relationship. To examine the impact of financial constraints on firm performance, 26 empirical studies with 189 effect sizes representing listed firms have been analysed. The study finds that overall there is a positive relationship between financial constraints and firm performance. The study also shows that the set of market-based measures of firm performance has a significant negative impact on the relationship, compared with the set of accounting-based measures. In terms of the financial constraints measure, the set of external financial constraints measures have a positive and highly significant impact on the relationship. The meta-regression analysis suggests that the choice of measure, regional difference, journal quality and publication status all have a significant impact on the relationship, and explain the variation in the association. To examine the impact of dual-class share structures on financial constraints the study analyses a sample of non-financial US firms over the period 2002-2018. Share structure is measured by the existence of a dual-class structure and also by excess voting rights and the proximity of the superior class shareholders in such structures. The study also shows that if financial constraints are measured by the WW index, irrespective of how dual-class share structure is measured, it increases the level of financial constraints. Similar results are obtained where financial constraints are measured by the KZ and SA indexes, except where dual-class share structure is measured by the proximity of superior class shareholders. The study also finds that if financial constraints are measured by the WW index, dual-class had a reduced impact during the period of the global financial crisis, thus, providing support for the propping theory. However, if financial constraint is measured by the SA index, dual-class share structure appears to have an increased impact during the GFC years. Among the additional tests, the HM index has been used as a measure of financial constraints, and the findings show that the impact of dual-class structures on financial constraints appears to be driven by their effect on debt constraints. The study also shows that firm age moderates the impact of dual-class share structures if financial constraints are measured by the WW index. The KZ, WW, and SA indexes are based on firm characteristics and, therefore, the study also tests for an impact of dual-class structures when financial constraint is measured by a text-based index, the BLM index. However, the results do not provide evidence of an impact in that case.
Keywords: Dual-class share structure; Financial Accounting; Financial Constraints; Firm Performannce; Meta analysis

Value Relevance of Integrated Reporting using a Novel Approach: Comparative Cross Country Evidence of Mandatory and Voluntary Implementers - Mohaimen, F. J. (Victoria University of Wellington, 2021)
This thesis examines the value relevance of accounting information under integrated reporting (IR) in a comparative mandatory and voluntary setting. A meta review is conducted of all published work focusing on integrated reporting since 2011, which provides detailed insight into the gaps in the IR literature. Multiplicative log-linear model is used in measurement, which is a novel technique that mitigates the shortcomings of traditional value relevance models. The findings show that value relevance of summary accounting information increases after the implementation of IR in the mandatory setting. In the voluntary setting, market effect and the existing reporting paradigm effect the value relevance of accounting information under IR. If the market is large and existing reporting requirements are robust voluntary adoption of IR has minimal to no effect. However, in smaller markets with less rigorous reporting environment, adoption of IR does result in increased value relevance of accounting information. Compared to traditional models, the multiplicative model provides estimates that are more stable over time and shows better explanatory power. Overall, the findings of this thesis show that capital providers value the information content of IR under specific circumstances. This thesis contributes to the IR and value relevance literature by providing the first comparative cross-country evidence of the effect of IR in the change in value relevance of reported accounting information. It provides policy relevant input to the standard setters of IR by demonstrating the effect of IR in the decision usefulness of summary accounting information. The thesis further provides robust evidence of the efficacy of using the multiplicative log-linear model in measuring value relevance instead of the traditional linear additive models.

La taxation des frais généraux en droit fiscal nigérien - Kimba Moussa, Hamidou (Université Cheikh Anta Diop, 2021)
Keywords: Droit fiscal; Frais généraux; Niger; Taxation; Taxe

Création d'un fonds Zakât international : nécessités et faisabilité d’une internationalisation du droit de la Zakât - Abrighach, Safae (Université de Strasbourg, 2021)
La Zakât, aumône légale des musulmans, fait partie des cinq piliers de l’Islam. Le verset 60 de la Sourate Tawbah fixe 8 catégories d'attributaires au profit desquels la Zakât peut être versée. En l'occurrence, il s'agit des pauvres, nécessiteux, personnes chargées de collecter la Zakât, personnes dont les sympathisants à l’islam, les esclaves, les insolvables, les voyageurs en détresse, et le sentier d'Allah. L’intitulé de « Création d’un Fonds Zakât International : Nécessités et faisabilité d’une internationalisation du droit de la Zakât » est une analyse d’un projet datant de 2008 et qui n’a pas abouti à sa réalisation. C’est pour inciter à la création d’un Fonds Zakât International que cette thèse a été rédigée. Il s’agit d’étudier les carences en question et d’en proposer des solutions efficaces. L’optique est de collecter la Zakât à l’international pour une meilleure éradication de la pauvreté. Zakat, legal alms for Muslims, is one of the five pillars of Islam. The Verse 60 of Sura Tawbah sets out eight categories of beneficiaries for whose benefit Zakât may be paid. In this case, it is the poor, needy, persons responsible for collecting the Zakât, persons whose sympathizers to Islam, slaves, insolvent, travelers in distress, and the path of Allah. The title ''Creation of an International Zakât Fund : Necessities and feasibility of an internationalization of the law of Zakat'' is an analysis of a project dating from 2008 and that did not lead to its realization. It is to encourage the creation of a Zakât International Fund that this thesis has been written. It is a question of studying the deficiencies in question and proposing effective solutions. The vision is to collect Zakât internationally for a better eradication of poverty.
Keywords: Dotation funds; Droit international (droit islamique); Fonds Zakât International; Fonds de dotation; Gouvernance; International Zakât Fund; Non-governmental organization; Oeuvres de bienfaisance; Organisation non gouvernementale; Waqf; Zakāẗ

Tributação na economia compartilhada - Braz, Jacqueline Mayer da Costa Ude (Universidade de São Paulo, 2021)
Este trabalho se propõe a estudar a tributação dos modelos de negócio que envolvem o conceito de economia compartilhada, que se liga à ideia de mercados de redistribuição, estilos de vida colaborativos e o sistema de produto e serviço, que busca substituir a propriedade pela posse dos bens. Esses modelos utilizam-se da tecnologia para aproximar pessoas que dificilmente se encontrariam offline para que elas possam firmar negócios jurídicos relacionados ao ideal de compartilhamento. As plataformas digitais, nesse contexto, funcionam como marketplaces, que agregam demanda e oferta e potencializam os resultados desses modelos de negócio. Desse modo, a partir da definição do conceito de economia compartilhada, os modelos de negócio foram mapeados, para que, em seguida, se pudesse compreender o papel das plataformas digitais, nesse contexto, e os negócios jurídicos que são celebrados por intermédio delas. Foram estudados os contratos firmados entre os usuários da plataforma e deles com a plataforma para, com base nisso, fosse examinada a tributação incidente. Concluiu-se pela impossibilidade de se estudar a tributação incidente sobre as atividades desenvolvidas pelas plataformas digitais de economia compartilhada apenas com a verificação do que ocorre com negócios jurídicos offline parecidos, estabelecendo a atividade preponderante e a tributação incidente por analogia. É preciso compreender o modelo de negócio, os contratos que são celebrados por seus usuários, além da relação jurídica que eles estabelecem com a plataforma e a consistência material do negócio jurídico, para, somente então, analisar a tributação incidente sobre as atividades econômicas desenvolvidas por intermédio dela. This work proposes to study the taxation of business models that involve the concept of sharing economy, which is linked to the idea of redistribution markets, collaborative lifestyles, and product and service system, which seeks to replace ownership of assets by their usage. These business models use technology to bring together people who would hardly meet offline so that they can establish legal business relationships that are connected to the idea of a sharing economy. In this context, digital platforms act as marketplaces that aggregate demand and supply, enhancing the results of these business models. This work defines the concept of a sharing economy and maps the existing business models so that one could understand the role of digital platforms in this context and the legal businesses that are concluded through them. The contracts signed between the users of the platform and theirs with the platform were studied and, based on this, the incident taxation could be examined. It was concluded that it is impossible to study the taxation on the activities developed by making an analogy between the digital platforms of sharing economy with similar offline legal businesses. It is necessary to understand each unique business model, the contracts that are signed by its users, the legal relationship that users establish with the platform, and the material consistency of the legal arrangement, only then to analyze the taxation on the economic activities developed through it.
Keywords: Contratos; Cooperativismo; Inovações tecnológicas; Negócio juridico; Sharing economy; Taxation; Tributação

Droit OHADA et développement économique au Cameroun de 1995 à 2020 : contribution historique à une théorie de l'analyse économique du droit en Afrique subsaharienne - Otabela Atangana, Hugues (Aix-Marseille Université, 2021)
Dans la décennie 1995 à 2005, 17 États d’Afrique subsaharienne se sont regroupés pour former une organisation d’intégration juridique, afin d’uniformiser leur droit des affaires et d’instaurer un courant de confiance pour les investissements. L’OHADA (Organisation pour l’Harmonisation en Afrique du Droit des Affaires) devait en découdre avec la situation d’insécurité juridique qui sévissait dans le continent en renforçant son attractivité économique, afin de faire émerger un pôle de développement en Afrique. Animée de l’idéologie panafricaniste, cette institution devait résolument se mettre au service du développement économique et de l’entreprise. Mais plus d’un quart de siècle après, on est en droit de se demander si elle atteint ses objectifs économiques. Les revendications des avocats anglophones de novembre 2016 au Cameroun qui fustigeaient l’imposition du droit OHADA au détriment de la Common Law, permet de jauger de la profondeur de la question. Ces mouvements corporatistes qui ont marqués le début de la crise sécessionniste, dévoilent le mimétisme juridique qui anime l'OHADA. Ce panafricanisme juridique qui l’incarnait, devait résolument se mettre au service de l’économie et de l’entreprise. Finalement, il a été supplanté par le mimétisme juridique. L’apport de l’OHADA dans le processus de développement économique du Cameroun reste faible et l’émergence d’un pôle de développement en Afrique est loin d’être amorcée. Cette réalité s’expliquerait par le fait que l’OHADA incarne une sorte d’acculturation juridique, d’où ses performances médiocres. L’opportunité d’une refonte profonde de ce modèle de communautarisation du droit des affaires mérite d’être soulevée
Keywords: Acculturation juridique; And legal mimicry.; Banks; Banques; Cameroun; Competencia; Competition law; Competitiveness; Compétitivité; Concurrence; Droit des affaires; Développement économique; Economic development; Entreprises; Financial markets; Incentive; Incitation; Innovation; Integration and economic agents; Intégration et agents économiques; Investissements; Investments; Legal acculturation; Legal pan-Africanism; Marchés financiers; OHADA; PIB réel; Panafricanisme juridique et mimétisme juridique.; Real GDP; Sécession

L'intermédiation financière et la théorie de la représentation - Gérard, Thomas (Université Paris Cité, 2021)
La réforme du droit des obligations a fait naître une distorsion entre la vision que le droit positif et la science juridique adoptent du mécanisme de la représentation. Afin d'y remédier, les activités ressortissant à l'intermédiation financière sont apparues comme un matériau d'étude approprié. Le vocable réunit les prestations prodiguées par les professionnels habilités à opérer sur les plates-formes de négociation d'instruments financiers et d'actifs numériques dans le cadre du traitement des ordres émanant de leurs clients. Si les intermédiaires financiers ne peuvent être considérés comme des mandataires dans la mesure où ils n'agissent pas au nom d'autrui mais en leur propre nom, les contrats qu'ils concluent avec leurs donneurs d'ordres n'en demeurent pas moins des contrats de représentation. Ces prestataires agissent en effet pour le compte d'autrui, mode d'action qui constitue l'essence du mécanisme de la représentation. En considération du principe de correspondance entre l'expression de l'intérêt du sujet et l'exercice d'un droit subjectif, il en résulte que celui qui, tel l'intermédiaire financier, exprime par sa volonté l'intérêt d'un autre sujet de droit exerce des prérogatives qui se rapportent aux droits subjectifs d'autrui. L'assise spécifique du pouvoir ainsi mis en œuvre éclaire le processus d'imputation à autrui des effets de l'action, que l'on présente comme le second versant de l'action pour le compte d'autrui. Compte tenu de la corrélation instaurée entre la titularité du droit subjectif exercé et l'imputation des conséquences qui en résultent, c'est en effet l'exercice des droits subjectifs d'autrui qui justifie l'imputation au titulaire de ces droits des effets de l'action. Fondée sur une dissociation entre la titularité et l'exercice des droits subjectifs, cette analyse de l'action pour le compte d'autrui la fait coïncider avec la conception moderne de la représentation. Si l'essence de la représentation se loge dans le mécanisme de l'action pour le compte d'autrui, le fait que l'agissement soit mené en nom propre ou au nom d'autrui doit être tenu pour une simple variable d'ajustement du phénomène représentatif. La teneur des obligations assumées par les prestataires habilités envers leurs donneurs d'ordres est inextricablement liée à leur qualité de représentant. L'obligation faite à l'intermédiaire financier d'exécuter la mission qui lui est confiée par son donneur d'ordres dépend étroitement de ce que le premier agit pour le compte du second, dont il met en œuvre les droits subjectifs. En tant qu'il constitue la traduction technique du pouvoir de représentation dévolu à cet intermédiaire, le mécanisme de l'action pour le compte d'autrui conduit à lui imposer des obligations de diligence et de loyauté partagées par tout représentant. Agissant pour le compte d'autrui, l'intermédiaire financier exerce un pouvoir de représentation ayant pour assise les droits subjectifs du représenté, ce dont il résulte qu'il assume des obligations communes à tout représentant. Préalablement analysée comme une simple variable d'ajustement du phénomène représentatif, l'intervention en son propre nom de l'intermédiaire financier ne saurait en altérer l'essence, ainsi que le confirme l'étude de l'influence d'un tel mode d'action sur le régime de l'obligation d'exécuter la mission assignée à l'intermédiaire. L'obligation de rendre compte incombant à l'intermédiaire financier obéit à la même logique. Si l'analyse de l'intermédiation financière atteste du particularisme du droit la régissant, la conception renouvelée de la représentation qu'elle a permis de formuler confirme dans le même temps l'absence d'autonomie du droit financier. Nous formons ainsi le vœu que l'étude ici menée puisse constituer le socle d'une réconciliation entre la science juridique et le droit positif susceptible d'éclairer la compréhension du mécanisme de la représentation à l'œuvre dans d'autres branches du droit. The reform of the law of obligations created a distortion between the vision that positive law and legal science adopt of the mechanism of representation. In order to remedy this, financial intermediation activities have emerged as suitable study material. The term combines the services provided by professionals authorized to operate on trading platforms for financial instruments and digital assets as part of the processing of orders from their clients. While financial intermediaries cannot be considered as agents insofar as they do not act in the name of others but in their own name, the contracts they conclude with their principals nonetheless remain representation contracts. These service providers act on behalf of others, a mode of action which constitutes the essence of the mechanism of representation. Considering the principle of correspondence between the expression of the subject's interest and the exercise of a subjective right, it follows that the one who, such as the financial intermediary, expresses by his will the interest of another subject of law exercises prerogatives which relate to the subjective rights of others. The specific base of power thus implemented sheds light on the process of attributing the effects of action to others, which is presented as the second aspect of action on behalf of others. In view of the correlation established between the ownership of the subjective right exercised and the attribution of the resulting consequences, it is in fact the exercise of the subjective rights of others which justifies the attribution to the holder of these rights of the effects of the action. Based on a dissociation between ownership and the exercise of subjective rights, this analysis of action on behalf of others makes it coincide with the modern conception of representation. If the essence of the representation is lodged in the mechanism of the action on behalf of others, the fact that the action is carried out in own name or in the name of others must be considered as a simple variable of adjustment. of the representative phenomenon. The content of the obligations assumed by authorized service providers towards their principals is inextricably linked to their quality of representative. The obligation imposed on the financial intermediary to perform the mission entrusted to it by its principal depends closely on whether the first acts on behalf of the second, whose subjective rights it implements. In so far as it constitutes the technical translation of the power of representation vested in this intermediary, the mechanism of action on behalf of others leads to the imposition of obligations of diligence and loyalty shared by all representatives. Acting on behalf of others, the financial intermediary exercises a power of representation based on the subjective rights of the principal, which means that he assumes obligations common to all representatives. Previously analyzed as a simple adjustment variable of the representative phenomenon, the intervention in its own name of the financial intermediary cannot alter its essence, as confirmed by the study of the influence of such a mode of 'action on the regime of the obligation to perform the mission assigned to the intermediary. The obligation to render account incumbent on the financial intermediary follows the same logic. If the analysis of financial intermediation attests to the particularism of the law governing it, the renewed conception of the representation that it has made it possible to formulate confirms at the same time the absence of autonomy of financial law. We therefore hope that the study conducted here may constitute the basis for a reconciliation between legal science and positive law capable of shedding light on the understanding of the mechanism of representation at work in other branches of law.
Keywords: Commission; Droit financier; Financial intermediation; Financial law; Intermédiation financière; Mandat; Representation; Représentation

Compliance et soft law en matière bancaire et financière - Bonnigal, Agathe (Université de Nantes, 2021)
Les normes de soft law, règles ou principes entendus comme les actes non-contraignants pouvant émaner des autorités publiques comme des acteurs privés, permettent d’appréhender ce qu’on appelle communément le droit souple. Classiquement écartées de la panoplie des sources formelles du droit, les normes de soft law sont reléguées le plus souvent au rang de sources nées de la pratique. Cependant, face aux nombreux effets juridiques qu’elles produisent et à la variété de leurs manifestations, on peut raisonnablement penser que les normes de soft law dont la compliance prend sa source, ont une réelle utilité pour encadrer l’activité bancaire et financière. La pertinence de recourir au soft law comme outil de conception de la compliance et de régulation du secteur bancaire et financier fera ainsi l’objet de notre réflexion dans une première partie. Après avoir démontré la diversification des sources dans l’encadrement normatif des activités bancaires et financières, nous analyserons le passé de la régulation. Nous nous interrogerons à cet effet, sur l’intégration du soft law dans l’ordre juridique interne. Puis, nous prolongerons notre réflexion en étudiant plus précisément la pratique de la compliance, qui dissimule un arsenal normatif complexe et des obligations éthiques visant à prémunir les établissements bancaires et financiers contre tout risque de non-conformité. Dès lors, nous tenterons de mesurer l’efficacité du système normatif de régulation dans la défense d’intérêts privés mais également d’enjeux nationaux et déterminerons les progrès restant à parcourir pour lutter contre ses insuffisances. Pour ce faire, nous nous intéresserons dans une seconde partie à la compliance comme expression de la densification normative du soft law en matière bancaire et financière.
Keywords: Banques; Compliance; Conformité; Droit souple; Finances

Securities regulation, enforcement and market integration in the development of sub-Saharan Africa's capital markets - Aziza, Onoriode Reginald (University of Oxford, 2021)
This thesis examines securities market development in sub-Saharan Africa, focusing on securities law, securities law enforcement and securities markets integration. Adopting a primarily comparative methodology, the thesis examines the continued relevance of securities markets in sub-Saharan Africa; the way selected countries in the region regulate their markets and enforce compliance with securities law; and the potential of market integration to promote market development. This thesis advances 4 main claims. First, empirical evidence supports the link between liquid securities markets and economic growth, independent of the level of banking development. In this sense, securities markets can act as good complements to banks in providing capital to the real economy. Second, at the minimum, there is an arguable preliminary case that rules of securities regulation can hinder market development in select countries in sub-Saharan Africa, by imposing high compliance costs and eligibility requirements, without commensurate benefits in greater liquidity or reduced cost of capital. Third, enforcement of securities regulation in sub-Saharan Africa is generally weak. Whilst public regulators often have formal powers, budgets and staff; actual enforcement activity is sometimes limited by inadequate market monitoring and reliance on criminal as opposed to administrative sanctions. Poor public enforcement, in turn, reinforces poor private enforcement, leading to reduced market participation, illiquidity, and ultimately market underdevelopment. Fourth, although increased market integration can go a long way in facilitating market development in the region, integration cannot be a short/medium term solution to market underdevelopment in sub-Saharan Africa, given the significant economic, political and socio-cultural barriers to integration initiatives in the region. Ultimately, to develop their securities markets, policymakers in sub-Saharan Africa must focus their attention on making and credibly enforcing market-friendly rules of securities regulation. The thesis explores some ways this may be realistically accomplished.
Keywords: Africa; Capital Markets; Capital market; Developing countries; Fintech; Going public (Securities); Market Integration; Securities; Securities Law; Securities Law Enforcement; Sub-Saharan Africa

A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa - Baines, Daniel (University of Pretoria, 2021)
A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa', Daniel Baines explores whether South African resident taxpayers' constitutional rights to equality and property are infringed by current laws which tax residents at higher rates than non-residents on rental income and proceeds from the disposal of fixed property. He aptly sets out what the right to equality and property entails and how these relate to taxpayers. He finds that the higher effective tax rates paid by residents violates their constitutional right to equality. The thesis provides valuable insight into a resident's right to equality and property in terms of current tax rates and illustrates how current tax rates are unconstitutional. The recommendations brought forward contribute toward the discussion of how tax rates should be altered in order to ensure that residents' constitutional rights are no longer violated.
URI: https://repository.up.ac.za/handle/2263/82750
Keywords: Immovable property; Income tax; South Africa; Tax treatment

Challenges for Responsible Investment in the retirement benefits sector of Kenya - Mathenge, Elizabeth (Victoria University of Wellington, 2021)
Responsible investment (RI) is the investment strategy that incorporates environmental, social and governance (ESG) factors into the investment decision-making process (Hebb, Hawley, Hoepner, Neher, & Wood, 2015). RI has shifted from what was considered a niche market to become one of the fastest-growing areas of finance in many parts of the world (PRI, 2019b). However, a closer look at the development of RI and adoption rates in countries and regions reveals that RI is not commonly practised in sub-Sahara Africa (except for South Africa). This study explores the critical challenges for RI development in the retirement benefits sector of Kenya and, by engaging with a variety of key stakeholders, proposes how to overcome the identified challenges. It contributes to the literature on challenges for RI in a developing country by offering an in-depth case study of the retirement benefits sector.My study employs qualitative methods to collect and analyse data collected from semi-structured interviews with 22 participants (asset managers, regulators and capital market experts, and a council member of the Association of Retirement Benefits Schemes of Kenya) as well as a collection of published documents by government agencies in Kenya. Also, I analysed 10 annual reports to assess the kind of ESG information that is disclosed by listed companies. My study explores, in particular, how actors in the retirement benefits sector conceptualise RI. It identifies the leading ESG factors in Kenya and draws on the business-case approach to RI to explore whether the participants consider those factors as material risk factors that present both risks and opportunities to the investment decision-making process. Further, my study identifies the specific barriers for RI development and proposes how to overcome them. The findings show that participants define RI using several terminologies. This is consistent with the existing literature. My study finds that all participants consider corporate governance as a material risk factor that can impact the financial returns of a portfolio. However, most of the asset managers do not think that the environmental and social factors can present material risk factors to their investment decision-making process. Although over a third of the asset managers recognise that the environmental and social issues in Kenya present business opportunities to retirement benefits schemes, there is a shortage of well-structured assets in those areas. Further, this study identifies five specific barriers for RI development: diversification challenges; a lack of ESG data; a lack of demand/incentives; short-termism; and the demand for high financial returns and a lack of awareness and expert knowledge of RI practices. My study recommends that the National Treasury of Kenya develops RI policy for the entire finance sector. In addition, the findings support a recommendation for the Capital Markets Authority and the Retirement Benefits Authority to embark on capacity building programmes to educate the actors in the finance sector on RI strategies and to create awareness of the impact of ESG on financial returns in the long run.
Keywords: Investment and Risk Management; Kenya; Responsible investment; Retirement benefits schemes

Governance of non-bank systematically important financial institutions - Morbee, Katrien (University of Oxford, 2021)
This thesis identifies the circumstances under which corporate governance regulation can help gain traction to minimise systemic risk. Systemic risk is the risk that local losses spread through the financial system and badly affect the financial system and the real economy. Excessive risk-taking by financial institutions can contribute to such systemic risk. Prudential regulation and supervision of financial institutions leave corporate decision-makers with room for discretion to increase or decrease systemic risk. The incentives of these decision-makers are not necessarily aligned with minimising systemic risk. The thesis shows that this problem exists across different business models. More specifically, it identifies perverse incentives in the case of systemically important banks, CCPs, mutual funds, and hedge funds. The need for corporate governance regulation therefore lies in the inherent incompleteness of prudential regulation and supervision. Corporate governance regulation can help fill this gap by regulating the environment within which choices are made within these types of institutions. The analysis has three steps. First, it characterises the systemic importance of financial-sector activities carried on outside the context of ‘banks’. The governance literature so far has focused on the ‘systemic externalities’ created by banks. However, our analysis shows that other non-bank SIFIs generate similar systemic externalities with socially harmful consequences. These systemic externalities are not considered by SIFIs when taking business decisions. In a second step, the thesis shows that prudential regulation and supervision are incomplete and leave room for governance regulation to fill in the gaps. The final step shows that a corporate governance framework focused solely on the interests of shareholders will have negative consequences for systemic stability. Given such divergence between the decision-makers’ and society’s interests, corporate governance regulation can complement the traditional prudential framework.
Keywords: Asset managers; Central counterparties; Corporate governance; Finance; Non-bank financial institutions; Systemic risk

Regulatory measures to address bank failures in Zimbabwe - Nyaude, Ashley Batsirai (University of Pretoria, 2021)
The main rationale of prudential bank regulation and supervision of banks has traditionally been to ensure the safety and soundness of banks and protection of depositors. However, best practice standards in bank supervision acknowledge that it is impossible to completely prevent bank failures. Therefore, it is crucial to have regulatory measures in place to deal with banks that fail. Banks are core players in the financial system as the intermediaries between savers and users of capital. In addition, banks provide critical services to consumers, small and medium-sized businesses, large corporate entities and governments who rely on them to conduct their daily business, both at domestic and international level. Banks also fulfil a sui generis role that sets them apart from other financial institutions that are role players in the financial system because, inter alia, they hold “highly” liquid liabilities in the form of deposits that are repayable on demand; they extend long-term loans that may be difficult to sell or borrow against on short notice; they are the back-up source of liquidity to all other institutions (financial and non-financial); and, are also the transmission belt for monetary policy. Unlike other players in the financial system, banks are vulnerable to loss of public confidence and to liquidity risk. Liquidity risk being the risk that a bank will not have sufficient cash to meet short term obligations and the fact that a "run on the bank" by depositors can result in devastating liquidity drainage. Because banks play a special role in the economy and their failure may have a significant impact on financial stability, they need a special approach when they become insolvent or are likely to become insolvent. The 2008 Global Financial Crisis (“GFC”) demonstrated the importance of special resolution regimes for banks; and the need to balance the interests of shareholders, creditors and depositors, while promoting financial stability objectives. Given the critical role of banks in the economy the need is clear for a special resolution regime for banks that provides a legal framework for regulators that avails to them a suite of resolution tools which they can apply to resolve the bank in an orderly manner; to rescue those parts of the bank that may still be viable and to liquidate those parts that are not whilst avoiding a drain on public funds. In order to deal with bank failures in Zimbabwe, the Banking Act [Chapter 24:20] has provided for the mechanism of curatorship since 2000, as a rescue measure aimed at restoring failing banks to economic viability. Curatorship has over the years been applied with mixed success; consequently, Zimbabwe has undertaken a number of reforms which include the enactment of the Troubled Financial Institutions (Resolution) Act in 2005; and the introduction of the problem bank regime via the Banking Amendment Act of 2015. Throughout these reforms, Zimbabwe has elected to retain curatorship, which was once a standalone process in banking legislation to enable bank rescue; and assimilated it into a broader bank resolution framework. This study seeks to determine whether Zimbabwe’s resolution regime requires to be strengthened and if so, to recommend reforms that will align the resolution regime in Zimbabwe with international best practice. For such purpose it will draw upon the Financial Stability Board’s Key Attributes of Effective Resolution Regime as international best practice benchmark. It will further also consider guidance yielded by a comparative study of the resolution regimes in the United Kingdom and South Africa.
URI: https://repository.up.ac.za/handle/2263/80388
Keywords: Bank failure; Bank supervision; Zimbabwe

Allocating rights between nations: Legitimacy and justice in international tax policy - Ozawa Ozai, Ivan (McGill University, 2021)
Although extreme poverty has decreased in the last decades, we are a long way from eradicating global poverty. Similarly, the world has seen a considerable decrease in global inequality due to recent developments in emerging economies, but overall inequality between nations has risen in the last decades. International tax law may have a relevant role in improving or worsening global inequality. Extensive research has shown that the present international tax system was designed in a way that tends to benefit high-income economies. However, there has been no significant discussion about whether and how international tax law rules should be changed to address global inequality. The main goal of this thesis is to analyze the existing legitimacy and distributive justice issues that limit the ability of lower-income countries to raise tax revenues and consider what can be done to make the current international tax regime more aligned with global justice principles.The thesis builds on the contemporary literature in international political economy and global distributive justice and puts forth a normative framework for allocating the international tax base among states. First, it analyzes some of the legitimacy deficits of the present international tax system. In contrast to prevailing views about improving legitimacy, it demonstrates the shortcomings of focusing solely on making international tax policymaking processes more inclusive and argues for a greater focus on global distributive justice. It then analyzes the main tax theories that have defined international tax relations to date and demonstrates some of their limitations. The final part of the thesis puts forth normative principles that integrate distributive justice and considers the practical implications of the proposed normative framework for some of the most recent issues discussed in international tax policy
Identifier: https://escholarship.mcgill.ca/concern/theses/rf55zd52x
Keywords: International tax; International tax policy

Le tourisme des Antilles françaises saisi par le droit économique - Liroy, Axel (Université Côte d'Azur, 2020)
Objet à multiples dimensions juridiques – le commerce, la concurrence, la fiscalité, l’environnement, le salariat, l’urbanisme, les droits et libertés fondamentaux, la valorisation du folklore et des traditions, la formation, la police, la construction notamment –, le tourisme est le terrain de synergie d’acteurs et d’activités publics et privés en lien direct ou indirect avec l’économique. Un lien de subordination ordonnée caractérisé par la privation, relativement motivée, de l’acteur économique d’un accès libre et direct au marché. C’est l’office du pouvoir économique public. Aux Antilles françaises, il est l’artisan d’un protectionnisme juridique, irradiant, variablement éloigné des nécessités économiques par opposition franche à une Caraïbe plus libérale et lacunaire, aux méthodes distorsives de concurrence, éminemment connectée aux nécessités économiques. Propulsées dans la modernité du droit par leur nationalité politique et ses corollaires – il est une identité de droits entre les Antilles françaises, la France continentale et, résolument, l’Union européenne –, les Antilles françaises sont, au niveau de leur région d’extraction, marginales. La conjuration, au moins partielle, de leur marginalité et, par ricochet, de celle de leur tourisme passerait par un changement de paradigme obtenu notamment d’un mouvement de décentration (« sortir de soi »). Ce dernier tire sa subsistance d’une société devenue mondialisée et interdépendante exhortant les petites économies au regroupement pertinent. Un mouvement qui, matériellement confronté à l’ombre menaçante de l’assimilation juridique dans le cas des Antilles françaises, requiert une fine précision. L’intégration régionale, dont la formule contractuelle – méthode alternative d’organisation de l’économie –, en ses force, intensité, diversité, flexibilité et massivité, est la figure de proue, sans prétendre à la panacée, emporte un effet décentriste. Il naît du contrat économique, plus justement de sa force normative. Porté par l’acteur économique public – l’Etat et/ou ses démembrements territoriaux –, le traité ou l’accord international vise notamment la conduite de politiques communes telle qu’en matière environnementale, les optimisation et fluidité circulatoires – des personnes, des biens, des services –, la réduction des écarts de développement, la protection de la concurrence. Porté par l’acteur économique privé – l’exemple des parties à un contrat de franchise –, sous couvert de la poursuite de la satisfaction d’intérêts particuliers, il organise des rapports d’économie confinant au transfert de technologie, au partage de marque, au renforcement de l’offre et de la demande, à la diminution du coût de la vie par la réalisation d’économie d’échelle, de gamme notamment. Maîtrisé, l’effet décentriste de l’intégration régionale pourrait, dans une certaine mesure, constituer un outil efficace pour une économie durable du tourisme des Antilles françaises en marge ou, quand cela est possible, en alternative aux procédés traditionnels. Objet à multiples dimensions juridiques – le commerce, la concurrence, la fiscalité, l’environnement, le salariat, l’urbanisme, les droits et libertés fondamentaux, la valorisation du folklore et des traditions, la formation, la police, la construction notamment –, le tourisme est le terrain de synergie d’acteurs et d’activités publics et privés en lien direct ou indirect avec l’économique. Un lien de subordination ordonnée caractérisé par la privation, relativement motivée, de l’acteur économique d’un accès libre et direct au marché. C’est l’office du pouvoir économique public. Aux Antilles françaises, il est l’artisan d’un protectionnisme juridique, irradiant, variablement éloigné des nécessités économiques par opposition franche à une Caraïbe plus libérale et lacunaire, aux méthodes distorsives de concurrence, éminemment connectée aux nécessités économiques. Propulsées dans la modernité du droit par leur nationalité politique et ses corollaires – il est une identité de droits entre les Antilles françaises, la France continentale et, résolument, l’Union européenne –, les Antilles françaises sont, au niveau de leur région d’extraction, marginales. La conjuration, au moins partielle, de leur marginalité et, par ricochet, de celle de leur tourisme passerait par un changement de paradigme obtenu notamment d’un mouvement de décentration (« sortir de soi »). Ce dernier tire sa subsistance d’une société devenue mondialisée et interdépendante exhortant les petites économies au regroupement pertinent. Un mouvement qui, matériellement confronté à l’ombre menaçante de l’assimilation juridique dans le cas des Antilles françaises, requiert une fine précision. L’intégration régionale, dont la formule contractuelle – méthode alternative d’organisation de l’économie –, en ses force, intensité, diversité, flexibilité et massivité, est la figure de proue, sans prétendre à la panacée, emporte un effet décentriste. Il naît du contrat économique, plus justement de sa force normative. Porté par l’acteur économique public – l’Etat et/ou ses démembrements territoriaux –, le traité ou l’accord international vise notamment la conduite de politiques communes telle qu’en matière environnementale, les optimisation et fluidité circulatoires – des personnes, des biens, des services –, la réduction des écarts de développement, la protection de la concurrence. Porté par l’acteur économique privé – l’exemple des parties à un contrat de franchise –, sous couvert de la poursuite de la satisfaction d’intérêts particuliers, il organise des rapports d’économie confinant au transfert de technologie, au partage de marque, au renforcement de l’offre et de la demande, à la diminution du coût de la vie par la réalisation d’économie d’échelle, de gamme notamment. Maîtrisé, l’effet décentriste de l’intégration régionale pourrait, dans une certaine mesure, constituer un outil efficace pour une économie durable du tourisme des Antilles françaises en marge ou, quand cela est possible, en alternative aux procédés traditionnels.
Keywords: Antilles françaises; Droit économique; French West Indies; Intégration régionale; Legal Protectionism; Protectionnisme juridique; Tourism; Tourisme

La reporting extra-financier en voie de se faire : Une étude herméneutique de l’appropriation d’une comptabilité socio-environnementale - Carn, Clément (Université de Poitiers, 2020)
Le développement de la comptabilité socio-environnementale au cours des dernières années représente un profond changement dans le champ de la comptabilité. Ses promoteurs proposent d'intégrer des éléments concernant le développement durable dans la communication des entreprises. Cette situation offre la possibilité d'étudier les pratiques comptables à un moment où elles ne sont pas encore figées et font encore l'objet de controverses. Notre recherche profite de cette situation pour étudier les processus sociaux qui concourent à façonner les institutions comptables. Nous questionnons plus précisément l'intégration du processus d'appropriation de l'une de ces nouvelles méthodes comptables (la méthode CARE) dans la construction socio-historique. Cette recherche s'inscrit alors logiquement dans le cadre de la théorie de l'appropriation, à laquelle nous proposons d'ajouter une dimension herméneutique. En effet, c'est par cette dimension qu'il est possible d'étudier la compréhension d'un outil à partir des cadres d'interprétations hérités de l'histoire. Cette attention portée à l'historicité nous conduit à proposer une généalogie des méthodes de comptabilité socio-environnementale. Celle-ci nous permet de distinguer le cadre dominant de la comptabilité prométhéenne – qui a vocation à garantir le maintien d'une capacité de production – du cadre critique de la comptabilité orphique qui permet de maintenir les entités écologiques pour elles-mêmes. À partir de cette compréhension théorique, notre étude empirique permet de montrer que, malgré la sensibilité écologique des acteurs, une comptabilité orphique fait systématiquement l'objet de tentative de détournement. Nous en déduisons l'importance des préjugés néoclassiques, c'est-à-dire des précompréhensions de certains concepts au travers du cadre dominant. Les débats scientifiques et politiques semblent toutefois permettre de réduire ces préjugés et conscientiser les choix opérer par les acteurs.
Keywords: Appropriation theory; Comptabilité; Comptabilité socio-Environnementale; Ecological economics.; Environmental economics; Hermeneutics; Herméneutique; Socio-Environmental accounting; Sociologie de la comptabilité; Sociology of accounting; Théorie de l’appropriation; Économie de l'environnement; Économie de l’environnement; Économie écologique

Les saisies de comptes bancaires en matière civile et commerciale : études de droit international - Guerreiro, Elodie (Université Paris 1, 2020)
La thèse est une étude de droit international portant sur le droit français des saisies de comptes bancaires en matière civile et commerciale. Elle définit le principe de territorialité du droit (au sens subjectiviste, normativiste et savignien). Elle distingue l’aspect procédural de la saisie d’un compte bancaire (la signification) de ses aspects substantiels (injonction de communiquer des données, indisponibilité et/ou transfert du solde du compte bancaire). Par observation du droit positif, elle soutient qu’en chacun de ces aspects, ladite saisie commande l’application de principes (subjectivistes) de territorialité distincts (territorialité des voies d’exécution, territorialité des traitements de données, territorialité des opérations de paiement) ; que seule l’analyse différenciée de ces principes permet de comprendre le régime synthétique des saisies des comptes bancaires en droit international. Cette approche analytique est riche d’enseignements. D’un point de vue pratique, elle permet de dégager des conditions potentielles d’invalidité et/ou d’illégitimité des saisies françaises de comptes bancaires étrangers. Par ailleurs, elle contribue à l’étude du régime international : des significations réelles faites à, et des transferts de données réalisés au sein d’une, personne morale ; du statut réel du compte bancaire. D’un point de vue théorique, elle révèle l’existence de conflits hétérogènes de lois et suggère une méthode pour leur résolution ; elle exige que l’approche subjectiviste du droit international, la lecture personnaliste du compte bancaire et des opérations de paiement, et l’analyse fonctionnelle de la monnaie, soient présentées et développées.
Keywords: Bank accounts; Bank secrecy; Banques; Comptes bancaires; Comptes en banque; Conflict of laws (public law); Conflits de lois (droit public); Data processing; Droit international et droit interne; Droit international privé; Droit monétaire; France; Gouvernance des établissements de crédit; Governance of credit institutions; Mesures conservatoires; Money; Monnaie; Opérations de paiement; Payment transactions; Principe de territorialité; Protection de l'information (informatique) – France; Saisie conservatoire; Secret bancaire; Secret professionnel; Seizure proceeding; Service of process to legal entity; Signification à personne morale; Territoriality principle; Theories of international law; Théories du droit international; Traitement de données

Blockchain, criptoativos e os títulos circulatórios do Direito Comercial - Micheli, Leonardo Miessa De (Universidade de São Paulo, 2020)
Na presente tese, busca-se analisar o fenômeno da blockchain e dos criptoativos, desde sua perspectiva genética relacionada ao comportamento social que explicam e justificam seu surgimento e o exponencial crescimento de sua utilização, passando pelas características e soluções técnicas existentes e propostas para as tecnologias de registro distribuído, denominadas Distributed Ledger Technologies, ou simplesmente DLTs, para, finalmente, observar os instrumentos de reflexo econômico suportados em tais plataformas, aqui denominados títulos circulatórios, sob o ponto de vista teórico do Direito Comercial. Para tal objetivo, é proposta uma estruturação teórica sobre os criptoativos, sua natureza jurídica, classificação e o estudo de seu posicionamento em relação a outros institutos do direito, como a moeda, os valores mobiliários e os títulos de crédito, a fim de identificar possíveis enquadramento dos ativos virtuais na tutela jurídica já existente sobre tais tradicionais instrumentos, tanto por sua teoria quanto por sua regulação. Por fim, ainda são analisadas possíveis aplicações da infraestrutura blockchain na criação e circulação de títulos circulatórios tradicionais do Direito Comercial, como valores mobiliários e mercado de capitais, além dos títulos de crédito desmaterializados. Foram utilizadas para o desenvolvimento da pesquisa as metodologias exploratória e empírica, estruturando-se o conteúdo da tese de forma retórica por meio das seguintes grandes premissas: (i) por quê; (ii) como; e (iii) para quê, identificadas nos subtítulos dos 04 Capítulos como: Por que estas tecnologias disruptivas vieram para ficar? Como é possível a tecnologia conferir o elemento essencial da confiança? O que são e em que se aplicam os ativos virtuais e as redes descentralizadas? Quais outros usos das tecnologias de registro descentralizado podem ser úteis aos instrumentos circulatórios de Direito Comercial? Conclui-se, ao final da pesquisa, que a tutela dos criptoativos deve ser considerada com base na função econômica de cada espécie, conforme sugerido nas conclusões, adequando-se as respectivas tutelas regulatórias às peculiaridades de tais instrumentos, tanto genéticas quanto estruturais, sob pena de esvaziamento da própria causalidade existencial dos ativos virtuais.
Keywords: Banco de dados distribuídos; Blockchain; Brasil; China; Circulatory instruments; Criptologia; Crypto-assets; Cryptoactif; Cryptocurrencies; Currency; DLT; Dinheiro eletrônico; Direito Comercial; Direito Comparado; Droit commercial; Estados Unidos; Europa; Mercado de capitais; Moeda (Economia); México; Negotiable instruments; Securities; Título de crédito; Valeurs mobilières

Les enjeux managériaux des entreprises et des organisations culturelles en contexte de diversité culturelle : le cas du Cameroun. - Loembet, Eric (Université Paris-Saclay, 2020)
La question du développement des entreprises et des organisations culturelles (EOCs) s'est intégrée dans les discours des acteurs-entrepreneurs culturels, dans plusieurs pays africains en vue, d'une appropriation des normes les caractérisant. Un discours qui mérite une clarification dans un environnement fusionnant le formel et l'informel dans la création de richesses. Face à une diversité culturelle favorisant la croissance économique et le développement humain, la création des richesses devient une opportunité de rentabilité et du développement de l’économie culturelle, le cas du Cameroun. Ainsi, les EOCs deviennent et se présentent comme des outils de capitalisation des valeurs et des richesses économiques. À cet effet, analyser et évaluer le secteur de l'économie de la culture, c'est définir le rôle, l’importance et l’impact des EOCs à contribuer à la création de richesses et à la croissance économique au Cameroun. Moteur des échanges des biens et des services culturels, ainsi que des capitaux, les EOCs contribuent au développement de l'économie nationale (PIB). En prenant part active à la croissance économique intérieure d'une nation, elles apportent une valeur ajoutée dans la valorisation des richesses, dans la création d'emploi et le développement de l’humain. Le rôle très capital qu'elles jouent dans l'appropriation et la valorisation des richesses, détermine l'intérêt économique dans la créativité artistique et culturelle. De ces transformations qui agissent au sein des EOCs, il est question de déterminer les enjeux managériaux de développement en contexte de diversité culturelle au Cameroun. Ainsi, la réflexion de cette étude se fonde sur ce paradoxe de la pluralité des richesses et de sa faible contribution à la création de richesses, ainsi qu'au développement de l'économie de la culture camerounaise. The question of the development of enterprises and cultural organisations (EOCs) has been integrated into the discourse of actor cultural contractor in several African countries, with a view to appropriating the standards characterising them. A discourse which deserves clarification in an environment merging the formal and the informal in the creation of wealth. Faced with cultural diversity favoring economic growth and human development, the creation of wealth becomes an opportunity for profitability and the development of the cultural economy, the case of Cameroon. Thus, the EOCs become and present themselves as tools for capitalising on economic values and wealth. To this end, analysing and evaluating the cultural economy sector means defining the role, importance and impact of the EOCs in contributing to the creation of wealth and economic growth in Cameroon. Driving the exchange of cultural goods and services, as well as capital, the EOCs contribute to the development of the national economy. By taking an active part in the internal economic growth of a nation, they bring added value in the valuation of wealth, in job creation and human development. the very crucial role that they play in the appropriation and enhancement of wealth, determines the economic interest in artistic and cultural creativity. of these transformations that are taking place within the EOCs, it’s a question of determining the managerial stakes of development in the context of cultural diversity in Cameroon. the reflection of this study will be based on this paradox of the plurality of wealth and it’s low contribution to the creation of wealth, as well as to the development of the economy of Cameroonian culture.
Keywords: Cameroon; Cameroun; Cultural Diversity; Cultural Enterprises; Cultural and Creative; Culture; Diversité culturelle; Diversité culturelle – Cameroun; Economics of Culture; Economie de la culture; Enjeux managériaux; Entreprises (développement); Entreprises culturelles; Industries culturelles; Industries culturelles et créatives; Managerial Issues

The Development of Accounting in Africa in the Era of International Financial Reporting Standards - Agyeman, Charles Gyamf (University of Westminster, 2020)
This thesis consists of two separate, but related studies on the development of accounting in Africa in the era of International Financial Reporting Standards. The first part of this thesis presents the first empirical test of a hypothetical classification of financial reporting in Africa based on de facto or actual practices as opposed to de jure rules. Three multivariate techniques (principal component analysis, cluster analysis, and multidimensional scaling) were used to analyse the accounting policies of large, listed companies in Africa that are required by law to adopt IFRS. It was found that there is a dichotomy between the IFRS policy choices of companies in Francophone and Lusophone countries, on the one hand, and those in common law jurisdictions, on the other, thus confirming the two-group classification schemes proposed by Elad (2015) and Nobes (1983). The results of this study extend previous research by demonstrating that international differences in financial reporting in Africa have survived in the era of IFRS and that pre-IFRS regulations enshrined in national and regional charts of account appear to have influenced IFRS policy choice. Furthermore, companies in common law countries tend to provide more extensive disclosures in their IFRS financial statements than their counterparts in code law countries. These findings have important policy implications, particularly in the context of recent recommendations of the World Bank, the International Monetary Fund, and the Pan-African Federation of Accountants that large entities in Africa adopt IFRS. The systematic differences in the choice of IFRS options between companies in civil law and common law jurisdictions suggest that it would be difficult to achieve internationalcomparability and consistency in financial reporting. The second part of the study uses semi structured telephone interviews to undertake interpretive accounting research (Baker and Bettner, 1997, p.293) to assess the perception of accounting professionals in relation to IFRS adoption and its use in Ghana. It concludes that despite the problems associated with its adoption and implementation, overall, International Financial Reporting Standards are viewed as necessary for the financial reporting needs of the country.
Keywords: Accounting classifications; CFA franc zone; IFRS practices; OHADA accounting system; Plan Comptable Général; SYSCOHADA

Protesto notarial no âmbito do contrato de mútuo bancário - Santos, Reinaldo Velloso dos (Universidade de São Paulo, 2020)
As instituições financeiras exercem um papel de extrema relevância na economia contemporânea, intermediando recursos para concessão de crédito à produção e ao consumo. Para melhor desempenhar essa função precisam de meios que assegurem o cumprimento das obrigações. Dentre esses meios está o protesto notarial, ato de incumbência de um profissional do Direito dotado de fé pública, que documenta solenemente a manifestação da insatisfação do credor, sendo revestido de ampla publicidade. É precedido de intimação do devedor, a quem se concede a oportunidade de voluntariamente adimplir a obrigação. Esse instituto, arraigado na tradição jurídica brasileira, tem-se revelado como uma alternativa ao processo judicial, permitindo a recuperação do crédito de forma mais célere e com custo reduzido. No trabalho é apresentado um panorama dos contratos bancários, incluindo o mútuo, bem como do protesto notarial. Além disso, trata dos principais aspectos relativos ao protesto do contrato de mútuo bancário e da cédula de crédito bancário. Ao final, são apresentadas reflexões do autor sobre o tema. As características peculiares do protesto notarial reforçaram seu papel histórico no Brasil. E as recentes modificações na disciplina do instituto certamente contribuirão para sua utilização de forma mais eficiente pelas instituições financeiras, com a perspectiva de redução das taxas nos empréstimos, beneficiando a produção e circulação de riquezas e, por conseguinte, permitindo o desenvolvimento econômico do país. Financial institutions play a relevant role in contemporary economy, by intermediating credit facilities for production and consumption. Availability of efficient enforcement measures is of the essence in such process. Among these providences is the protest, which consists on a formal proof of dishonor, drawn by a public notary, who is a legal professional vested with public faith. Information about protests is public and can be provided to anyone. The notary sends prior notice to the debtor, thus offering a last opportunity to pay the overdue amount to prevent the protest. This institution, rooted in the Brazilian legal tradition, became an alternative to judicial procedure, making the protest a quick and inexpensive debt recovery tool. This thesis presents an overview of banking agreements, including loans, as well as the notarial protest. In addition, the main aspects related to the protest of loan agreements and the cédula de crédito bancário - a negotiable instrument issued by the borrower - are also contained herein. At the end, the author presents his reflections on the topic. The peculiar characteristics of the notarial protest reinforced its historical role in Brazil. And the recent regulatory changes will certainly contribute to increase the protest's effectiveness, especially for financial institutions, with the prospect of reducing interest rates in loan agreements, thus benefiting the production and circulation of wealth, and bringing forth economic development to Brazil.
Keywords: Banking agreement; Banking loan; Contrat; Contrato bancário; Default; Direito notarial; Inadimplemento das obrigações; Notarial law; Notarial protest; Protesto de título; Protêt notarié; Prêt bancaire

Commercialization of Microfinance in Cameroon : How can Microfinance Institutions manage their dual social and commercial goals? - Singhe, Steffi Sandra (Université de Nantes, 2020)
La commercialisation de la microfinance a mis au premier plan la performance financière des I MF, les IMF adoptant désormais une logique commerciale de rentabilité en plus de leur logique sociale établie de lutte contre la pauvreté. Cela pose un défi de gestion crucial pour les IMF pour équilibrer l'aspect social et commercial de leur mission. Cette thèse vise à analyser comment les IMF surmontent leurs défis pour atteindre leur double objectif social et commercial. Elle s'appuie sur le concept de bricolage comme perspective théorique et sur une approche méthodologique abductive, exploratoire et qualitative. La thèse vise également à fournir une meilleure compréhension du secteur de la microfinance camerounaise, en termes de son histoire et évolution, et des défis spécifiques au secteur. L'étude identifie diverses pratiques de bricolage que les IMF utilisent pour faire avancer la réalisation de leur double mission. Les résultats suggèrent l'utilisation de ces pratiques de bricolage par les IMF pour mobiliser des ressources, renforcer la légitimité et accroître leur ou/reach, dans un contexte caractérisé par des contraintes de ressources. Ces trois résultats de bricolage se renforcent mutuellement pour faciliter la réalisation du double objectif des IMF. Cette recherche a également mis en évidence les quatre phases d'évolution du secteur de la microfinance camerounaise et les cinq principaux défis auxquels sont confrontées les IMF du secteur. Cette thèse contribue à la littérature sur la microfinance. Elle propose un nouvel regard sur la gestion de la double mission des IMF en montrant comment les IMF mobilisent les stratégies de bricolage pour faire avancer leurs objectifs sociaux et commerciaux. Elle met en lumière le lien entre la littérature sur la microfinance et le bricolage. The commercialization of microfinance has brought to the forefront the financial performance of MF!s, with MF!s now adopting a commercial logic of profitability in addition to their established social logic of poverty alleviation. This poses a crucial management challenge for the MF!s in terms of balancing the social and commercial aspect of their mission. The main aim of this thesis is to understand how MFls overcome their challenges so as to achieve their dual social and commercial goals. lt draws on the bricolage concept as a theoretical perspective and on an abductive, exploratory and qualitative research approach. The thesis also aimed to provide a better understanding of the Cameroonian microfinance sector, in terms of its history and evolution, and the challenges specific to the sector. The study identifies various bricolage practices that the MF!s use to advance the fulfilment of their dual mission. The findings suggest the use of these bricolage practices by the MF!s to mobilize resources, build legitimacy, and increase outreach, in a context characterized by resource constraints. These three bricolage outcomes reinforce each other, and they all strengthen the achievement of the MF!s' dual goals. This research also highlighted the four phases of evolution of the Cameroonian microfinance sector and the five main challenges faced by MF!s in the sector. This thesis contributes to the microfinance literature. lt offers a new perspective on MF! dual-mission management by showing how MF!s mobilize bricolage practices to advance their dual social and commercial goals. lt brings light on the link between the literature on microfinance and bricolage.
Keywords: CSR; Cameroun; Microfinance; RSE; Responsabilité sociétale; Régulation (théorie)

Essais sur l'efficience et la fiscalité pétrolière dans les pays en développement - Gab-Leyba, Guy Dabi (Université Clermont Auvergne, 2020)
L’objectif de cette thèse est de mettre en évidence les déterminants de l’efficience des politiques publiques dans les pays en développement. Les résultats relèvent que les pays dotés de ressources naturelles et en situation de fragilité ont tendance à avoir des dépenses publiques d’éducation primaires moins efficientes. Les résultats révelent aussi que l’accroissement de la part des dépenses de santé dans les dépenses totales des ménages, du taux d’incidence de la pauvreté, du taux d’alphabétisation et la localisation en zone considérée comme austère réduisent l’efficience des structures de santé. A l’inverse, la hausse du taux d’incidence du paludisme, du taux de prévalence de la malnutrition améliorent l’efficience des structures de santé. S’agissant de l’efficience des établissements de crédits, les résultats mettent en exergue une amélioration du score d’efficience sur la période 2000-2015 en dépit du fait qu’en moyenne, l’efficience des banques de la zone CEMAC se situe autour de 33 %. Les estimations montrent aussi qu’une taille importante et une forte liquidité améliorent l’efficience technique des établissements de crédits tandis qu’un accroissement du risque bancaire la réduit. Enfin, l’évaluation des régimes fiscaux pétroliers en application au Tchad révèle que les contrats de partage de production permettent à l’Etat de capter une part plus importante de la rente pétrolière comparativement aux contrats basés sur le système de concession. En outre, les contrats basés sur le partage de production présentent la caractéristique d’être progressif. Ces résultats ont des implications en matière de politique économiques. Ainsi, les pays en developpement devraient en priorité améliorer la qualité des dépenses sociales en promouvant la transparence et la bonne gouvernance dans la mise en œuvre des projets de developpement et politiques publiques. En particulier, dans le secteur de la santé, il est urgent d’améliorer la qualité du personnel de santé et une meilleure programmation des dépenses de fonctionnement visant à rendre les infrastructures de santé opérationnelles. Ensuite, pour accroitre la rentabilté des banques dans les pays de la zone CEMAC, il conviendrait de diversifier les structures bénéficiaires des crédits et mettre en œuvre des réformes visant à améliorer le climat des affaires. Enfin, le Gouvernement tchadien devrait réactiver une politique contra-cyclique en vue de se prémunir des fluctuations des recettes pétrolières. The aim of this thesis is to highlight the determinants of the efficiency of public policies in developing countries. The results show that countries with natural resources and in fragile situations tend to have less efficient public spending on primary education. The results also reveal that the increase in the share of health expenditure in total household expenditure, the poverty incidence rate, the literacy rate and the location in areas considered as isolated reduce the efficiency of health structures. Conversely, the increase in the incidence rate of malaria and the prevalence rate of malnutrition improve the efficiency of health structures. Regarding the efficiency of credit institutions, the results highlight an improvement in the efficiency score over the period 2000-2015 despite the fact that on average, the efficiency of banks in the CEMAC zone is around 33%. Estimates also show that a large size and high liquidity improve the technical efficiency of credit institutions while an increase in banking risk reduces it. Finally, the assessment of petroleum tax regimes in force in Chad reveals that production sharing contracts allow to Government to capture a higher share of oil rent compared to contracts based on the concession system. In addition, contracts based on production sharing have the characteristic of being progressive. These results have implications for economic policy. Thus, developing countries should give priority to improving the quality of social spending by promoting transparency and good governance in the implementation of development projects and publics policy. In particular, in the health sector, there is an urgent need to improve the quality of health personnel and better programming of operating expenditure aimed at making health infrastructures operational. Then, to increase the profitability of the banks in the countries of the CEMAC zone, it would be advisable to diversify the structures beneficiary of the credits and to implement reforms aiming at improving the business environment. Finally, the Chadian Government should reactivate a counter-cyclical policy in order to guard against fluctuations in oil revenues.
Keywords: Cash flow model; Concession contrat; Contrat de concession; Contrat de partage de production; Dépenses publiques; Education; Efficency; Efficience; Health; Impôts; Industrie et commerce; Modèle de flux de trésorerie; Natural ressources; Order m; Pays en voie de développement; Politique fiscale; Politique publique; Production sharing contrat; Public spending; Pétrole (exploitation); Ressources naturelles; SFA; Santé

La dématérialisation des valeurs mobilières en zone CEMAC - N'Tchatat Tounya, Fabrice Léonel (Université de Yaoundé 2, 2020)
La dématérialisation des valeurs mobilières a été amorcée par l’OHADA depuis son Acte Uniforme de 1997 où le mécanisme qui jusque-là n’était optionnel que pour les sociétés faisant appel public à l’épargne, a été étendu à toutes les valeurs émises dans l’espace OHADA de façon obligatoire en faveur de l’Acte Uniforme de 2014. Cette réforme d’envergure a également été posée en zone CEMAC de manière ambivalente. D’un côté par le règlement communautaire N° 01/14 du 25 avril 2014 qui limite la portée de cette dématérialisation aux valeurs mobilières qui sont émises dans le cadre d’un appel public à l’épargne et de l’autre par la loi camerounaise N° 2014/007 du 23 avril 2014 et son décret d’application N° 2014/3763 du 17 novembre 2014, ainsi que la loi gabonaise n°027/2016 du 06 février 2017 fixant le régime de la dématérialisation des valeurs mobilières en République Gabonaise qui étendent la dématérialisation à toutes les valeurs mobilières émises sur le territoire national. Aux termes de l’article 1er alinéa 2 de la loi camerounaise précédemment citée, la dématérialisation des valeurs mobilières est une opération de substitution des certificats physiques des titres, par l’inscription en compte des titres sous forme électronique. Il s’agit d’une révolution économique qui facilite la circulation et la conservation des titres, initialement détenus sous la forme matérielle. La dématérialisation des valeurs mobilières est un processus, elle est donc prescriptible. C’est-à-dire que sa mise en œuvre est limitée dans le temps. Ainsi, compte tenu du fait que la dématérialisation est une opération délicate, qui a une échéance et qui affecte le régime juridique des valeurs mobilières, l’étude d’un tel sujet invite à s’interroger sur les effets de la dématérialisation sur les valeurs mobilières et la pertinence des normes ayant vocation à les encadrer dans la sous-région tant dans sa mise en œuvre que dans la gestion des valeurs mobilières dématérialisées. Cette réflexion trouve tout son sens dans la mesure où d’une part, le législateur communautaire restreint le mécanisme de dématérialisation des valeurs mobilières tandis que les législateurs nationaux en font une portée large. D’autre part, les législateurs tant communautaire que nationaux ont ficelés les modalités de dématérialisation sans prendre en compte les réalités de l’activité économique sous régionale telle que l’inexistence des titres physiques. Enfin, à l’instar de l’AUDSCGIE du 30 janvier 2014, les textes en vigueur dans la sous-région rendent désormais obligatoire le régime d’inscription en compte des valeurs mobilières, lequel n’est pas sans effet sur le mode de détention et de circulation de celles-ci en zone CEMAC. The dematerialization of securities has been initiated by OHADA since its Uniform Act of 1997 where the mechanism which until then was optional only for companies making public offerings, has been extended to all the securities issued in the OHADA area on a mandatory basis in favor of the Uniform Act of 2014. This major reform was also applied in the CEMAC zone in an ambivalent manner. On the one hand by Community regulation N ° 01/14 of April 25, 2014 which limits the scope of this dematerialization to transferable securities which are issued within the framework of a public offering and on the other by law Cameroonian N ° 2014/007 of April 23, 2014 and its implementing decree N ° 2014/3763 of November 17, 2014, as well as the Gabonese law n ° 027/2016 of February 06, 2017 establishing the dematerialization regime for securities in Gabonese Republic which extend the dematerialization to all the securities issued on the national territory. Under the terms of article 1, paragraph 2, of the Cameroonian law cited above, the dematerialization of securities is a substitution operation for the physical certificates of the securities, by registering the securities in electronic form. It is an economic revolution which facilitates the circulation and conservation of securities, initially held in physical form. The dematerialization of securities is a process, so it can be prescribed. That is to say, its implementation is limited in time. Thus, given the fact that dematerialization is a delicate operation, which has a deadline and which affects the legal regime of transferable securities, the study of such a subject invites us to wonder about the effects of dematerialization on securities and the relevance of the standards intended to guide them in the sub-region both in its implementation and in the management of dematerialized securities. This reflection finds all its meaning insofar as, on the one hand, the Community legislator restricts the mechanism of dematerialization of securities while the national legislators make a broad scope of it. On the other hand, both Community and national legislators have tied up the dematerialization modalities without taking into account the realities of sub-regional economic activity such as the absence of physical titles. Finally, like the AUDSCGIE of January 30, 2014, the texts in force in the sub-region now make compulsory the system of registration in securities account, which is not without effect on the method of holding and circulation of these in the CEMAC zone.

Deveres de informação e adequação: responsabilidade civil dos intermediários financeiros - Paiva, Rafael Bianchini Abreu (Universidade de São Paulo, 2020)
O objetivo desta tese é apresentar, em perspectiva comparada entre Brasil e União Europeia, quais deveres devem ser impostos aos intermediários financeiros para que seus clientes não profissionais adquiram produtos e serviços adequados aos seus conhecimentos, experiências, necessidades, objetivos e situação financeira e, em caso de descumprimento desses deveres, as hipóteses e a extensão da responsabilidade civil dos intermediários financeiros. Nesse sentido, a crise financeira internacional de 2008 foi um divisor de águas por evidenciar problemas na distribuição de diversos instrumentos financeiros e resultar em diversos processos administrativos e judiciais, bem como reação de reguladores em diferentes jurisdições. Este trabalho está dividido em quatro Capítulos, cuja estrutura é a seguinte: I. Processo decisório e mercados financeiros: 1. As decisões individuais segundo a Teoria Neoclássica; 2. Risco, retorno e a Hipótese dos Mercados Eficientes (HME); 3. Falhas de mercado; 4. Racionalidade limitada: vieses cognitivos e emocionais do processo decisório; 5. Agentes quase racionais e Hipótese da Instabilidade Financeira (HIF); II. Intermediação e inovações financeiras: 1. A atividade de intermediação financeira; 2. Inovações financeiras de primeira geração e ciclo de endividamento privado; 3. Inovações financeiras recentes: moeda eletrônica, pagamentos instantâneos, criptoativos e stablecoins; III. Deveres de informação e adequação (suitability): 1. Princípios gerais e recomendações das organizações internacionais; 2. Deveres de informação e adequação na União Europeia; 2.1. Antes da crise financeira de 2008; 2.2. Reformas a partir da crise financeira de 2008; 3. Deveres de informação e adequação no Brasil; 3.1 Crédito rotativo; 3.2 Jurisprudência; 3.3 Decisões da CVM; IV. Responsabilidade civil. Considerações finais.
Keywords: Complex financial products; Cryptoassets; Cryptocurrencies; Dinheiro eletrônico; E-money; Financial innovations; Financial institutions; Instituição financeira; Intermédiaire financier; Marché financier; Mercado financeiro; Responsabilité civile; Stablecoins; Suitability

Capital market effects of adoption of IFRS - Opare, Solomon (Victoria University of Wellington, 2020)
This thesis examines the impact of adoption of IFRS (International Financial Reporting Standards) on two aspects of the operation of capital markets. Firstly, the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital. Secondly, the impact of adoption of IFRS on seasoned equity offering (SEO) underperformance. To examine the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital, the study used meta-analysis of empirical studies published since 2000. Meta-analysis provides an objective view of the empirical results, in contrast to narrative reviews, which offer subjective conclusions. From meta-analysis of 55 empirical studies with 1,259 effect sizes, the study finds that IFRS adoption has increased financial reporting comparability, market liquidity, and reduced cost of equity. For cost of debt, a decrease is observed only for voluntary adoption. The meta-regression analysis shows how the results differ across mandatory and voluntary adoption of IFRS and that the measurement choices, type of control variables, study design, and strength of empirical results explain the variation in the observed effect of adoption of IFRS. To examine the impact of adoption of IFRS on SEO underperformance the study analyses a large sample of SEOs from 51 countries over the period 1992-2017. Given that the empirical literature on SEOs has established that information asymmetry contributes to SEO underperformance, it is important to assess whether adoption of IFRS has reduced the uncertainties surrounding SEOs and, thus, subsequent underperformance. The study employs a control sample of non-IFRS adoption countries and applies a difference-in-difference (DiD) design to test for the incremental change for IFRS adoption countries over non-IFRS adoption countries. The study finds that SEO underperformance reduces for IFRS adopters relative to non-IFRS adopters in the post-adoption period. The reduction in SEO underperformance is influenced by increased disclosure, increased comparability, and number of accounting changes. The study also finds that the impact of adoption of IFRS on SEO underperformance exists only for firms in countries with strong enforcement, and is conditional on the implementation credibility of countries. The findings are robust to the application of a different measure of SEO underperformance. Overall, the study suggests that IFRS has had a positive impact on capital markets. However, increased disclosure, comparability, and credible implementation play important roles in realising the benefits of adoption of IFRS. Thus, policymakers of weak enforcement countries are encouraged to strengthen their institutional environment in order to reap the benefits that adoption of IFRS can provide to their capital market.
Keywords: Cost of debt; Cost of equity; Enforcement; Financial reporting comparability; IFRS adoption; Market liquidity; Meta-analysis; SEO underperformance; Seasoned equity offering

The Distributional Effects of Value-Added Taxes in OECD Countries - Thomas, Alastair (Victoria University of Wellington, 2020)
Most OECD countries’ value-added tax (VAT) systems apply reduced VAT rates to a selection of expenditure items in order to achieve distributional goals, and – to a lesser extent – social, cultural and employment-related goals. This thesis investigates the distributional effects of the VAT in OECD countries, and the merits of using reduced VAT rates to achieve distributional goals. The research adopts a microsimulation modelling approach that draws on household expenditure microdata from household budget surveys for an unprecedented 27 OECD countries. A consistent microsimulation methodology is adopted to ensure cross-country comparability of results. Non-behavioural VAT microsimulation models are first built to examine the overall distributional impact of the current VAT systems in each country. The research assesses the competing methodological approaches used in previous studies, highlighting the misleading effect of savings patterns on cross-sectional analysis when VAT burdens are measured relative to income. Measuring VAT burdens relative to expenditure – thereby removing the influence of savings – is found to provide a more reliable picture of the distributional impact of the VAT. On this basis, the VAT is found to be either roughly proportional or slightly progressive in most of the 27 OECD countries examined. Nevertheless, results for a small number of countries (Chile, Hungary, Latvia and New Zealand) highlight that broad-based VAT systems that have few reduced VAT rates or exemptions can produce a small degree of regressivity. Results also show that even a roughly proportional VAT can still have significant equity implications for the poor – potentially pushing some households into poverty. Behavioural VAT microsimulation models are then built for 23 OECD countries to investigate whether reduced VAT rates are an effective way to support poorer households, and whether the use of targeted cash transfers would be more effective. The behavioural microsimulation methodology follows the Linear Expenditure System based approach of Creedy and Sleeman (2006). Complementing this approach, a Quadratic Almost Ideal Demand System (QUAIDS) is estimated specifically for New Zealand, thereby providing the first estimates of a QUAIDS model based on New Zealand data. Simulation results show that, as a whole, the reduced VAT rates present in most OECD countries tend to have a small progressive impact. However, despite this progressivity, reduced VAT rates are shown to be a highly ineffective mechanism for targeting support to poorer households: not only do rich households benefit from reduced rates, but they benefit more in aggregate terms than poor households do. When looking at reduced VAT rates applied to specific products, results are found to vary considerably. Reduced VAT rates specifically introduced to support the poor (such as reduced rates on food consumed at home and domestic utilities) are generally found to have a progressive impact, though rich households still receive a larger aggregate benefit than poor households. In contrast, reduced VAT rates introduced to address non-distributional goals (such as reduced rates on restaurants, hotels, and cultural and social expenditure) often have a regressive impact. Additional simulation results show that an income-tested cash transfer will better target support to poorer households than reduced VAT rates in all countries. Furthermore, even a universal cash transfer is found to better target poorer households than reduced VAT rates. However, results also show that it is very difficult for an income-tested cash transfer to fully compensate all poor households for the removal of reduced VAT rates. This is due to the significant variation in the underlying consumption patterns across households. While a small number of poor households lose out from replacing reduced VAT rates with targeted cash transfers, those that receive support are instead determined by income and family characteristics as opposed to consumption tastes – thereby increasing horizontal equity. Furthermore, many households are lifted out of poverty as revenue previously transferred to richer households is now transferred to poorer households. These results empirically confirm the theoretical expectation that, where available, direct mechanisms (whether via the income tax or benefit system) will better achieve distributional goals than reduced VAT rates. Countries that currently employ reduced VAT rates to achieve distributional goals should therefore consider removing these reduced rates and adjusting their income tax or benefit systems to achieve these distributional goals instead. Countries should also consider removing reduced VAT rates aimed at non-distributional goals where a more effective instrument is available to achieve the particular policy goal. At a minimum, the merits of these reduced VAT rates should be reassessed in light of their negative distributional impact.

The effectiveness of the adopted OECD transfer pricing dispute resolution mechanisms in an African context - Kekana, Nelson Doctor (University of Pretoria, 2020)
With the developments happening globally that are aimed at curbing base erosion and profit shifting by multinationals, improving the resolution of transfer pricing disputes has been identified as one of the key issues. This thesis investigates the challenges uniquely faced by African countries that militate against the use of the OECD transfer pricing dispute resolution mechanisms. The thesis starts by reflecting on the effect of transfer pricing manipulation by multinational enterprises in Africa in particular. Transfer pricing manipulation is one of the causes of the so-called tax gap, which is, the gap between anticipated and actual revenue collection. The aggression by revenue authorities against transfer pricing manipulation in order to close this gap has triggered a lot of transfer pricing adjustments. These adjustments have resulted in multiple transfer pricing disputes. In the analysis of the adopted OECD dispute resolution mechanisms, the thesis focuses on the effectiveness of the mutual agreement procedure (MAP), the advance pricing arrangement (APA) and the mandatory binding arbitration (MBA). It identifies the problems that result in the failure of or the delay in the resolution of many transfer pricing disputes by analysing the domestic frameworks that exist in four African countries namely: South Africa, Kenya, Uganda and Ghana. The thesis identifies problems such as the absence of a tax treaty network within the African continent, the use of underdeveloped double tax agreements and the lack of commitment from African countries to subscribe to and ratify multilateral conventions. These problems delay or stifle the resolution of tax treaty disputes. They also cause uncertainty for taxpayers and lead to continued tax avoidance by multinational enterprises that essentially avoid paying tax in African countries where the economic activities of these enterprises take place. The thesis also identifies the importance of other OECD supporting tools such as the exchange of tax information in the resolution of transfer pricing disputes. It focuses on tools such as country by country reports, the master file, the local file and simultaneous tax examination as covered by the Multilateral Convention on Mutual Administrative Assistance in Tax Matters. The thesis contributes to the resolution of the identified problems with transfer pricing dispute resolution in Africa by recommending certain improvements that can be effected. These recommendations entail, regarding the MAP, the expansion of tax treaty networks by African countries and the establishment of a Tax Treaty Dispute Resolution Committee by ATAF. Regarding the APA, it is recommended that African countries should sign the multilateral instrument (MLI) and make use of advance tax rulings (ATRs) as alternatives. With respect to the MBA, this thesis recommends that African countries should use optional arbitration by effectively using article 25(4) of the OECD Model tax convention (MTC). It also recommends that African countries must enhance their tax transparency by ratifying multilateral conventions that seek to address international tax co-operation and to improve compliance with transfer pricing documentation requirements in order to make the resolution of transfer pricing disputes more effective.
https://repository.up.ac.za/handle/2263/80889
Keywords: Dispute resolution; Model Tax Convention; OECD; Transfer pricing

Promoting financial inclusion through mobile money while introducing regulatory solutions to reduce and control money laundering in Lesotho - Taole, T. E. (North-West University, 2020)
Mobile money services have considerable potential in modern economies. They have the potential to increase financial inclusion for poor people and people excluded from formal financial services. This is because mobile money services can be accessed simply using a mobile cellular phone and the majority of people nowadays own mobile phones, including people living in the rural areas. Mobile money can therefore solve the problem of financial exclusion because even the people who live in the rural areas without access to formal financial services can now access financial services thorough mobile money services. Financial inclusion, on the other hand, is simply defined as a situation where every member of the society has access to and is able to use financial services offered by formal financial services institutions, such as banks and insurance companies. Financial inclusion has many benefits, the main benefit being the stimulation of the economy of a country. For mobile money services to operate smoothly and financial inclusion to be achieved, there must be enabling regulation. Regulation must not be so strict as to prevent mobile money service providers from operating. Regulation must allow for innovation and at the same time maintain financial integrity and stability by ensuring that financial crimes, such as money laundering, do not affect mobile money services. Although mobile money services can increase financial inclusion, regulators must be vigilant to ensure that they stop criminals from using mobile money services to commit money laundering offences. This research focuses mainly on mobile money services in the Kingdom of Lesotho. The aim is to find out how regulation can be improved to ensure that mobile money services can help to increase financial inclusion. The aim is also to find out how regulation can help to ensure that mobile money services operate smoothly, and that the crime of money laundering is prevented from affecting mobile money services. To achieve this aim, the research is divided into different chapters and in each chapter the aim is to find ways in which the main aim can be achieved. In the research, mobile money and financial inclusion will be defined and their importance in modern economies will be demonstrated in greater detail. Furthermore, the issues of money laundering will be discussed. The threat of the crime of money laundering will be highlighted. An analysis of the legal regulatory framework of mobile money services and money laundering in Lesotho will be undertaken to determine the extent to which these regulatory frameworks can help realise financial inclusion and promote mobile money services in Lesotho. The same discussion is made in respect of other African countries. The legal regulatory framework of Lesotho will be compared to the framework of other African countries to ascertain how mobile money services and money laundering and financial inclusion issues are regulated in those countries. The countries discussed in this research are South Africa, Malawi, Kenya, Nigeria, Uganda, Tanzania, and Ghana. Based on these discussions, some shortcomings in the legal regulatory framework of mobile money services and money laundering in Lesotho will be identified and the conclusion will be drawn that the two frameworks have to be revisited to ensure that mobile money services will operate smoothly in the Kingdom of Lesotho. Furthermore, recommendations will be made to address the legal shortcomings identified in the framework.
Keywords: Financial inclusion; Lesotho; Mobile money services; Regulatory framework